Garnet materials for Li secondary batteries

JP7608306B2Active Publication Date: 2025-01-06QUANTUMSPACE BATTERY INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021153955
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2014-07-18
Filing Date
2021-09-22
Publication Date
2025-01-06
Estimated Expiration
2034-10-07

Smart Images

  • Figure 0007608306000009
    Figure 0007608306000009
  • Figure 0007608306000010
    Figure 0007608306000010
  • Figure 0007608306000011
    Figure 0007608306000011
Patent Text Reader

Abstract

Garnet material compositions suitable for use as electrolytes and catholytes in solid-state battery applications, lithium-filled garnet thin films, and methods for making and using lithium-filled garnets as catholytes, electrolytes, and / or anolytes for all-solid-state lithium batteries are provided. A composition comprising a lithium-filled garnet and Al2O3, wherein the lithium-filled garnet has an empirical formula Li A Lai B M'i C M''i D Zri E Oi F wherein 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application was filed on October 7, 2013, and is related to a method for forming a garnet material using a sintering process. METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTE No. 61 / 887,451, filed on January 13, 2014, entitled "RING PROCESS," , U.S. Provisional Patent Application No. 61 / 9 entitled GARNET THIN FILM ELECTROLYTE No. 26,910, filed June 4, 2014, which discloses a method for forming garnet materials using reaction sintering. METHODS AND SYSTEMS FOR FORMING GARNET MATERIAL WITH REACTIVE No. 62 / 007,417, filed on July 18, 2014, entitled "SINTERING" Fine Grained Lithium-Ion Conductive Garnet Ceramics Thin Film No. 62 / 026,271, entitled "N CONDUCTING THIN FILM GARNET CERAMICS" and and Garnet catholyte and solid-state electrochemical device and Sintering of Components (Garnet Catholyte and Sintering of Solid State Electrochemical Devices This application claims priority to U.S. Provisional Patent Application No. 62 / 026,440, entitled "METHOD AND COMPONENTS." Each of these provisional patent applications is incorporated herein by reference in its entirety for all purposes. is incorporated into [Background technology]

[0002] BACKGROUND OF THEINVENTION There is a great demand for cleaner forms of stored energy. Clean Energy Storage An example of this is Li + Rechargeable lithium (Li) in which ions move from the negative electrode to the positive electrode ion batteries (i.e. Li-ion secondary batteries). Many applications (e.g. portable electronics For safety and energy density reasons, liquid components (e.g., Uses solid-state Li-ion batteries made of all-solid-state materials, as opposed to batteries that contain flammable liquid electrolytes Solid-state Li-ion batteries incorporating Li-metal anodes have significantly lower It would also be advantageous to have a smaller electrode capacity and a correspondingly increased energy density.

[0003] A crucial component of solid-state batteries is the electrolyte, which electrically isolates the positive and negative electrodes. In many cases, it is intimately mixed with the positive electrode active material to improve ionic conductivity therein. The third important component in some Li-ion batteries is the anode material Anode material (i.e., anode material; e.g., Li-metal) laminated to or in contact with it. However, currently available electrolytes, catholytes, and anolytes Even within the operating voltage range of solid-state batteries, It is also not stable when in contact with metal fluorides.

[0004] Garnets (e.g., Li-filled garnets) are used as catholytes, electrolytes, and or anolytes. However, garnet materials are still available in suitable morphologies (e.g., thin films or nanostructured powders). and to have sufficient conductivity and / or particle connectivity to function well enough. No longer manufactured. Although certain garnet materials and processing techniques are known (e.g., US Patent Nos. 8,658,317, 8,092,941, and 7,901,658; U.S. Patent Application Publication No. 2013 / 00850 55, No. 2011 / 0281175, No. 2014 / 0093785 and No. 2014 / 0170504; further, Bonderer "Free-Standing Ultrathin Ceramic Foils," J. ournal of the American Ceramic Society, 2010, 93(11):3624 - 3631; and Murugan et al. (See Angew Chem. Int. Ed. 2007, 46, 7778-7781), these materials and techniques are Such problems may include, but are not limited to, insufficient conductivity or processing conditions that are not compatible with certain solid-state battery components. It suffers from a variety of defects.

[0005] Therefore, in particular, garnet films and garnet powders as cathode active materials in all-solid-state batteries With respect to the integration of garnet materials, improved methods of making and processing garnet materials are needed. The following disclosure is based in part on these and related arts to which the present disclosure pertains. It offers many solutions to other problems. Summary of the Invention

[0006] (Summary of the invention) Disclosed herein are catholytes, electrolytes, and anolytes for solid-state lithium secondary batteries. Lithium-stuffed garnet in thin film and powder form as light Also disclosed herein are novel and inventive methods of making and using the novel Garnet catholytes, electrolytes, and anolytes, and novel materials incorporating these materials In contrast to known garnets, the method described herein The materials are uniquely designed for electrochemical devices (e.g., solid-state batteries) and are The morphology, conductivity, density, porosity, and surface properties (e.g., roughness, etc.) suitable for use in batteries. , flatness, absence of surface cracks and defects), as well as chemical, temperature, and voltage stability. It has sexuality. [Brief description of the drawings]

[0007] BRIEF DESCRIPTION OF THE DRAWINGS

Figure 1

[0008]

Figure 2

[0009]

Figure 3

[0010]

Figure 4

[0011]

Figure 5

[0012]

Figure 6

[0013]

Figure 7

[0014]

Figure 8

[0015]

Figure 9

[0016]

Figure 10

[0017]

Figure 11

[0018]

Figure 12

[0019]

Figure 13

[0020]

Figure 14

[0021]

Figure 15

[0022]

Figure 16

[0023]

Figure 17

[0024]

Figure 18

[0025]

Figure 19

[0026]

Figure 20

[0027]

Figure 21

[0028]

Figure 22

[0029]

Figure 23

[0030]

Figure 24

[0031]

Figure 25

[0032]

Figure 26

[0033]

Figure 27

[0034]

Figure 28

[0035]

Figure 29

[0036]

Figure 30

[0037]

Figure 31

[0038]

Figure 32

[0039]

Figure 33

[0040]

Figure 34

[0041]

Figure 35

[0042]

Figure 36

[0043]

Figure 37

[0044]

Figure 38

[0045]

Figure 39

[0046]

Figure 40

[0047]

Figure 41

[0048]

Figure 42

[0049]

Figure 43

[0050]

Figure 44

[0051]

Figure 45

[0052]

Figure 46

[0053]

Figure 47

[0054]

Figure 48

[0055]

Figure 49

[0056]

Figure 50

[0057]

Figure 51

[0058]

Figure 52

[0059]

Figure 53

[0060]

Figure 54

[0061]

Figure 55

[0062]

Figure 56

[0063]

Figure 57

[0064]

Figure 58

[0065]

Figure 59

[0066]

Figure 60

[0067]

Figure 61

[0068]

Figure 62

[0069]

Figure 63

[0070] Detailed Description of the Invention The following description is provided to enable one of ordinary skill in the art to make and use the inventions described herein and to The various modifications are presented so that they can be incorporated in the context of a particular application. and various uses for different applications will be readily apparent to one of ordinary skill in the art, and as defined herein. The general principles can be applied to a wide variety of implementations. Thus, the invention is It is not intended to be limited to the embodiments shown, but rather to be construed in accordance with the principles and The broadest scope consistent with the novel features should be allowed.

[0071] The reader is directed to the following: and the contents of all such documents and documents are hereby incorporated by reference. It is incorporated in the specification. Unless otherwise expressly stated, each disclosed feature is only one example of a series of general equivalent or similar features. Moreover, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112.

[0072] Furthermore, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not expressly recite a “means for” performing a particular function or a “step for” performing a particular function should not be construed as a “means” or “step” clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of “step of” or “act of” in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112.

[0073] When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object.

[0074] (I. Definitions) As used herein, the term “NASICON” refers to a sodium (Na) superionic conductor often characterized by the chemical formula Na Zr2Si 1+x Zr2Si x P 3-x O 12 O O, where 0 < x < 3 (optionally, where Na, Zr, and / or Si are replaced by isovalent elements). As used herein, the term “NASICON” refers to a sodium (Na) superionic conductor often characterized by the chemical formula Na

[0075] As used herein, the term “LISICON” refers to a lithium (Li) superionic conductor often characterized by the chemical formula Li Li 2+2x Zn 1-xRefers to a lithium (Li) superionic conductor often characterized by GeO4 vinegar.

[0076] As used herein, the term "positive electrode" refers to the electrode toward which the battery is discharged. and positive ions, e.g., Li + In this specification, the term "electrode" refers to an electrode in a secondary battery through which the electrolyte flows or moves. As used, the term "negative electrode" refers to the electrode from which positive ions, e.g. Ba, Li + Refers to the electrode in a secondary battery through which the lithium flows out or moves. Li-metal electrode and conversion Chemical electrodes (i.e., active materials; e.g., NiF x In a battery consisting of The electrode with the charge chemistry is called the positive electrode. In some common usage, the positive electrode Instead of a negative electrode, a cathode is used, and instead of a negative electrode, an anode is used. When charged, the Li ions are transported to the positive electrode (e.g., NiF x ) towards the negative electrode (Li-metal). When a secondary battery is discharged, Li ions are transferred from the negative electrode (e.g., Li-metal; i.e., the anode) to the positive Polar (e.g., NiF x ; i.e., the cathode).

[0077] As used herein, the term "current collector" refers to a metal that is used to complete an external circuit. A component or layer in a secondary battery through which electrons are conducted into and out of the electrode, In some cases, the current collector is in direct contact with the electrode that conducts current into and out of it. , metals laminated on the positive or negative electrodes (e.g., Al, Cu, or Ni, steel, alloys thereof, or During charging and discharging, electrons move in the opposite direction to the flow of Li ions. , passing through the current collector as it enters or leaves the electrode.

[0078] As used herein, the phrase "at least one member selected from the group" A, B may include a single member from the group, multiple members from the group, or a combination of members from the group. At least one member selected from the group consisting of A, B, or C is, for example, A alone, B alone, or C alone. C only, and A and B, and A and C, and B and C, and A, B, and C, or A, B, and and any other combination of C.

[0079] As used herein, the term "slot casting" refers to casting a solution, liquid, slurry, or etc. adjacent to, in contact with, or on the substrate on which it is deposited or applied. The solution, liquid, slurry, or other material is applied to the substrate by flowing it through a slot or mold of fixed dimensions that is positioned. In some instances, the slotted hole may be used to apply or deposit a layer of a coating or other material. The casting includes a slot opening of about 1 to 100 μm.

[0080] As used herein, the phrases "dip casting" or "dip coating" refer to the process of applying a coating to a substrate. The substrate is moved, often vertically, in and out of a solution, liquid, slurry, etc. The deposition process refers to a deposition process in which a solution, liquid, slurry, etc. is applied or deposited onto a substrate.

[0081] As used herein, the term "depositing" refers to the deposition of one precursor species, e.g. , a layer of a lithium precursor species is successively deposited on the deposition substrate, and then a further layer is deposited on the second A precursor species, e.g., a transition metal precursor species, is used to successively deposit a layer on an already deposited layer. This layering process is repeated to create several layers of the deposited vapor phase. As used herein, the term "stacking" refers to stacking electrodes. A layer containing, for example, a positive electrode or a cathode active material, is coated with another material, for example, a garnet. It also refers to the process of contacting a layer containing an electrolyte. The lamination process involves the use of a material that adheres to the layers being laminated. This involves the reaction or use of a binder that physically maintains contact between the laminated layers. This may also be the case.

[0082] As used herein, the phrase "solid catholyte" or "catholyte" refers to The term refers to a cathode (i.e., positive electrode) active material (e.g., a metal fluoride, optionally including lithium). This refers to an ionic conductor intimately mixed with or surrounded by metal ions (fluorides).

[0083] As used herein, the term "electrolyte" refers to an ionically conductive, electrically insulating The electrolyte refers to the material in which the ions in the electrolyte, e.g. Li + While enabling the conduction of , are useful for electrically insulating the positive and negative electrodes of a secondary battery.

[0084] As used herein, the term "anolyte" refers to an anode material or It may be mixed with, layered on, or stacked on the node current collector. This refers to a layer of ionically conductive material.

[0085] As used herein, the term "green film" refers to garnet material, garnet a precursor of the binder, a solvent, a carbon, a dispersant, or a combination thereof. The term "green membrane" refers to a green membrane that includes at least one component that is bonded to the green membrane.

[0086] As used herein, the phrase "depositing a cathode current collector" is intended to include, but is not limited to, the term "depositing a cathode current collector." Although metals such as copper, nickel, aluminum, or combinations thereof are used as cathodes, Catholyte, or a combination thereof, or anode, anolyte, or a combination thereof The metal is provided in vapor or spray form so as to contact the metal and form an adhesive layer therewith. This process refers to the deposition or supply of a metal layer on the cathode or anode. This results in the formation of a metal layer such that the metal layer and the cathode or anode are in electrical communication.

[0087] As used herein, the term "fabricate" refers to forming a fabricated object. It refers to the process or method of forming or causing to form. For example, Fabricating an energy storage electrode includes a process for forming an electrode for an energy storage device; The end result of the steps that constitute the fabrication of an energy storage electrode is , the creation of a material that functions as an electrode.

[0088] As used herein, the phrase "energy storage electrode" refers to, for example, an energy storage electrode. For use in gas storage devices, e.g. rechargeable lithium batteries or Li-secondary batteries As used herein, such an electrode refers to an electrode suitable for rechargeable batteries. It can conduct the electrons and Li ions necessary for charging and discharging the battery.

[0089] As used herein, the term "provide" refers to the provision of something provided, It refers to the making, offering, or supply of

[0090] As used herein, the phrase "providing a green thin film" refers to the formation of a green thin film. Refers to providing, generating, or presenting, or supplying. For example, providing an unsintered thin film means making the unsintered thin film available or supplying the unsintered thin film so that it can be used as described in the methods described herein. It refers to a process of making an unsintered thin film available or supplying an unsintered thin film.

[0091] As used herein, the term "unsintered thin film" refers to a thin film that contains the components and materials described herein but has not been sintered by the sintering methods described herein. Thin means, for example, a film having an average thickness dimension of about 10 nm to about 100 μm. In some examples, thin refers to a film having a thickness of less than about 1 μm, 10 μm, or 50 μm. It refers to a film having a thickness of less than about 1 μm, 10 μm, or 50 μm.

[0092] As used herein, the term "lithium-filled garnet" refers to an oxide characterized by a crystal structure related to the garnet crystal structure. Lithium-filled garnets include the formulas Li Li A La B M' c M'' D Zr E O F Li A La B M' C M'' D Ta E O F Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 13, and M' and M'' are each, in each case independently, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li Li a La b Zrc Al d Me'' e O f (wherein 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb ) and contains a compound as described herein. The garnets used herein also include the above garnets doped with Al2O3. The garnets used herein also include the above garnets doped such that Al 3+ replaces Li + . As used herein, lithium-filled garnets and garnets usually, but not limited to, contain Li La3(Zr 7.0 + Nb t1 + Ta t2 )O t3 + 0.35Al2O3; where (t1 + t2 + t3 = subscript 2) such that the La:(Zr / Nb / Ta) ratio is 3:2 12 . Also, the garnets used herein usually, but not limited to, contain Li La3Zr2O x + yAl2O3 12 (where x ranges from 5.5 to 9; and y ranges from 0 to 1). In some examples , x is 7 and y is 1.0. In some examples, x is 7 and y is 0.35 . In some examples, x is 7 and y is 0.7. In some examples, x is 7 . In some examples, x is 7 and y is 0.4. Also, the garnets used herein usually, but not limited to, contain Li La3Zr2O x + yAl2O3. 12

[0093] ​As used herein, garnet includes YAG-garnet (i.e., YAG-garnet). Y3Al5O 12 ) is not included. Garnets include pyrope, almandine, spessartine, and grosgrain. Ra, Hessonite, or Cinnamon Stone, Tsavorite, Uvarovite, and Andhite Luddite, and the solid solutions pyrope-almandine-spessarite and Does not include silicate garnets such as barovite, grossular, and andradite Garnets herein include those of the general formula X3Y2(SiO4)3, where X is Ca, Mg, Fe, and / or Mn. and Y is Al, Fe, and / or Cr).

[0094] As used herein, "garnet precursor chemicals" or "garnet-type electrolytes" The phrase "chemical precursor of" refers to a compound that reacts to produce the lithium-loaded garnet compound described herein. These chemical precursors include lithium hydroxide (e.g. Lithium oxide (e.g., LiOH), lithium carbonate (e.g., LiCO3), zirconium oxide nium (e.g., ZrO2), lanthanum oxide (e.g., La2O3), aluminum oxide (e.g., Al2O 3), Aluminum (e.g., Al), Aluminum nitrate (e.g., AlNO3), Aluminum nitrate nonahydrate, niobium oxide (e.g., Nb2O5), and tantalum oxide (e.g., Ta2O5). Not limited to these.

[0095] As used herein, the term "garnet-type electrolyte" refers to any of the garnet-type electrolytes described herein. The term "electrolyte" refers to an electrolyte that contains a garnet or lithium-filled garnet material as an ionic conductor. vinegar.

[0096] As used herein, the phrase "alumina doped" refers to alumina doped with Al2O3. In this case, it means replacing a certain component of another material, e.g. garnet. Al2O3 Lithium-filled garnets are doped with aluminum (Al). A garnet that replaces an element in the formula of carbene (which may be, for example, Li or Zr). This refers to the

[0097] As used herein, the phrase "aluminum reaction vessel" refers to a vessel in which a chemical reaction can take place. Thus, precursor chemicals are used to produce the product, e.g., lithium-loaded garnet material. Refers to the container or receptacle into which something is placed.

[0098] As used herein, the phrase "high conductivity" refers to a conductivity of 10 -5 Exceeds S / cm In some instances, high conductivity refers to a conductivity of 10 at room temperature. -5 Includes conductivities greater than S / cm.

[0099] As used herein, the term "partial replacement of Zr with a higher valence species" refers to The phrase is Zr 4+ and, for example, 5 + or 6 + For example, some Nb 5+ is present at the lattice site in the garnet crystal structure where Zr atoms exist, and 4+ To If possible, partially replace Zr with Nb. This is also called niobium doping. Called.

[0100] As used herein, the subscripts and molar coefficients in the empirical formula are used in the examples given. The phrase "based on the amount of raw material initially batched to make the product" is used as a subscript. Character (e.g., Li7La3Zr2O 12 7, 3, 2, 12, and 0.35 in Al2O3) for a given material. (For example, Li7La3Zr2O 12 ·0.35Al2O3) are used to produce chemical precursors (e.g. LiOH, La2O3, ZrO2, Al2O3).

[0101] As used herein, the phrase "electrochemical device" refers to an energy storage device. devices, such as, but not limited to, electrochemical reactions, e.g., conversion chemistry, for example, [ka] "Li-ion" refers to a Li-ion secondary battery that operates or generates electricity or current.

[0102] As used herein, the phrase "film thickness" refers to the distance between the top and bottom surfaces of a film or refers to the median distance measurement. As used herein, the top and bottom surfaces are the largest surfaces. This refers to the side of the membrane that has an area.

[0103] As used herein, the term "grain" refers to a grain that is separated from the remainder of a material. Refers to a region of material within the bulk of the material that has a distinct physical boundary. For example, some In materials, often there are both crystalline and amorphous components of a material with the same chemical composition. Both are distinguished from each other by the boundary between the crystalline and amorphous components. The approximate diameter of the constituent boundaries is referred to herein as the grain size.

[0104] As used herein, "d 50 The term "diameter" refers to, but is not limited to, scanning electron As measured by microscopy or other particle size analysis techniques such as dynamic light scattering or microscopy. Refers to the median diameter in the diameter distribution. D 50 has 50% of the particles larger than the listed size. Small characteristic dimensions are involved.

[0105] As used herein, the phrase "active electrode material" or "active material" refers to a rechargeable It is suitable for use as a rechargeable Li battery and does not undergo chemical reactions during charge / discharge cycles. For example, an "active cathode material" refers to a material that is used to charge and discharge a rechargeable Li battery. Between the metal and the metal fluoride, which converts to lithium fluoride.

[0106] As used herein, the term "active anode material" is defined above. Anode materials suitable for use in rechargeable Li batteries containing active cathode materials such as In some instances, the active material is lithium metal. In some of the methods used, the sintering temperature is determined by the amount of lithium used as the active anode material. This is high enough to melt lithium metal.

[0107] As used herein, the phrase "conductive additive" refers to an additive that enhances the conductivity of the cathode. This refers to a material that is mixed with the cathode active material to improve the cathode conductivity. Examples include carbon, as well as various Various forms of carbon, e.g., Ketjen Black, VGCF, Acetylene Black, Graphite nanotubes, nanofibers, etc., and combinations thereof. But not limited to these.

[0108] As used herein, the term "solvent" refers to any of the components or A liquid suitable for dissolving or solvating a material. For example, a solvent may be garnet. A liquid suitable for dissolving the components used in the sintering process, e.g., the binder, e.g. For example, toluene can be mentioned.

[0109] As used herein, the phrase "removing the solvent" refers to removing the solvent from the solution as described herein. The term refers to the process of extracting or separating a component or material from the component or material that is being processed. Removing the solvent includes, but is not limited to, evaporating the solvent. This involves using a vacuum or reduced pressure to drive off the solvent from the mixture, e.g., the green film. In some instances, the solvent is evaporated to reveal solvated biomolecules in the thin film after the solvent is removed. The thin film containing the binder and the solvent is heated, or optionally vacuum or It is also placed in a reducing atmosphere environment.

[0110] As used herein, the phrase "sintering a film" refers to the process of densifying (making denser or having reduced porosity) the thin films described herein through the use of thermal sintering or electric field assisted sintering. Sintering is the application of heat and / or pressure to a solid mass of material without melting the solid mass to the point of full liquidity. force The process includes forming the

[0111] As used herein, the term "FAST" refers to an acronym for Electric Field Assisted Sintering. In some instances, FAST also refers to flash sintering.

[0112] As used herein, the phrase "applying a DC or AC electric field" refers to applying a The electric field is altered or created by a power source, and a current flows through the material, producing a direct current (DC) from the power source. The process of electrically connecting a power source to a material so that it produces either alternating current (AC) or alternating current (AC). Refers to...

[0113] As used herein, the term "binder" refers to a material that aids in the adhesion of other materials. For example, as used herein, polyvinyl butyral refers to a garnet It is a binder because it is useful for bonding plastic materials. Other binders include: Polycarbonate. Other binders include polymethyl methacrylate. These examples of binders are not intended to cover the full range of binders contemplated herein. It is not intended to be limiting with respect to the present invention, but merely serves as an example.

[0114] As used herein, the phrase "casting a membrane" refers to the process by which a liquid or slurry is cast onto a membrane. The liquid or slurry is then dispensed into a mold or onto a substrate to form or be formed into a film. Casting refers to the process of feeding or transferring a material to a surface using a doctor blade, a Mayer rod, or a cone. Macota coater, gravure coater, microgravure, reverse comma coater, slot This can be done by die, slip, and / or tape casting, as well as other methods known to those skilled in the art. This can be done.

[0115] As used herein, the phrase "applying pressure" refers to applying pressure to a subject using an external device, e.g. Calendering refers to the process of inducing pressure in another material.

[0116] As used herein, the term "about" refers to the limitation of the number with which it is associated. About, in some instances, means ±5% around the number qualified by the word about. For example, evaporating the solvent at about 80° C. can be achieved by evaporating the solvent at 79° C., 80° C., or 81° C. The method includes evaporating the solvent by evaporation.

[0117] As used herein, the phrase "about 1 to about 600 minutes" refers to a range from 0.1-1.1 to 540-660 minutes. As used herein, "about 10 μm to about 100 μm" refers to a range of minute values ​​and values ​​therebetween. " refers to the range of 9 μm-11 μm to 90 μm-110 μm and integer values ​​therebetween.

[0118] As used herein, the phrase "about 500°C to about 900°C" refers to a temperature range from 450°C to 550°C. It refers to the range of 810℃ to 990℃ and integer temperature values ​​therebetween.

[0119] As used herein, "burning out the binder or calcining the green film" means The phrase "burn out" refers to burning or discharging or removing the binder. Chemical reactions that cause the binder to become denser or less porous, for example, by combustion or by The film containing the binder is treated with an oxidizing species to induce a chemical reaction that sinters the film with the binder. , for example, refers to the process of optionally heating in an environment containing O2.

[0120] As used herein, the phrase "composite electrode" refers to an electrode that is made up of multiple materials. For example, a composite electrode may contain active materials in an intimate mixture or in an ordered layer. a cathode material and a garnet-type electrolyte, or the active material and the electrolyte are interdigitated. Examples of suitable active cathode materials include, but are not limited to, the active cathode materials and garnet-type electrolytes. Not determined.

[0121] As used herein, the phrase "inert setter plate" refers to a generally flat and does not react with the material being sintered. An inert setter plate is These setter plates can be metal or ceramic and are optionally sintered. The material to be sintered is then sintered to provide for the diffusion of gases and vapors through it. , may be porous.

[0122] As used herein, the phrase "operating in a constant voltage amplitude mode" refers to a material While keeping the amplitude of the applied DC voltage or the RMS amplitude of the AC voltage constant, the current This is an electrochemical process that allows the resistance, or impedance, of a material to change as a function of Refers to the process.

[0123] As used herein, the phrase "operating in a constant current amplitude mode" refers to a constant A DC current or an AC current of RMS amplitude flows through a material while an applied voltage changes the resistance, or impedance, of the material. This refers to an electrochemical process that allows the capacitance of the material to change as a function of temperature.

[0124] As used herein, the phrase "free-standing thin film" refers to a thin film that is adhered or supported by an underlying substrate. refers to an unsupported membrane. In some instances, a free-standing thin film has no adhesive or other adhesives attached to it. Free-standing membranes that can be mechanically manipulated or moved without the need for a fixed substrate. It is.

[0125] As used herein, the term "porosity" refers to pores, e.g., nanopores, mesopores, , or a material that contains micropores.

[0126] As used herein, the term "pyrolysis" refers to the process of pyrolysis at high temperatures in the absence of oxygen. Decomposition of organic materials in water refers to the thermochemical decomposition of organic materials at elevated temperatures.

[0127] As used herein, the term "electroplating" refers to the process of depositing a material, e.g., a metal, It refers to the process of deposition in conjunction with the use of electricity.

[0128] As used herein, the phrase "average pore diameter size of about 5 nm to about 1 μm" refers to pores wherein the inner diameter of the pores therein is, for example, about 5 nm for nanopores, or For example, micropores refer to material that are physically spaced apart by approximately 1 μm.

[0129] As used herein, the phrase "the polymer is stable at voltages greater than about 3.8 V" shows destructive chemical reactions when a voltage greater than 3.8 V is applied to it relative to a lithium reference electrode. As used herein, a destructive chemical reaction refers to a polymer that does not undergo a reaction. This refers to a chemical reaction that deteriorates the functionality of the polymer in which it is used. For example, if a polymer If it is ionically conductive and useful as a Li-conductor in a Li battery, the destructive reaction is in S / cm of conductivity over the product's lifetime under useful operating conditions of temperature and cycling When measured, the polymer's ability to conduct Li-ions is reduced or impaired by more than 10%. This is a reaction that causes

[0130] As used herein, the term "permeated" means the penetration of one material into another. It refers to the state of entering into or causing one material to come together with another. For example, when carbon is infiltrated into a porous garnet, this is because the carbon is infiltrated into the porous garnet. It refers to the process of causing a substance to enter and become intimately mixed with it.

[0131] As used herein, the phrase "operating with a ramp voltage" refers to operating with an applied voltage of This refers to an electrical process that gradually or systematically increases or decreases voltage over a period of time.

[0132] As used herein, the phrase "operating at lamp power" refers to operating at or above the applied power. It refers to the process of gradually or systematically increasing or decreasing a quantity over a period of time.

[0133] As used herein, the phrase "operating with a lamp current" refers to operating with an applied current. This refers to an electrical process that gradually or systematically increases or decreases voltage over a period of time.

[0134] As used herein, the terms "nanostructured" or "nano-dimensional" refer to structures Refers to composite materials in which the components are separated by nano-dimensions. For example, may include Li-containing compounds, such as LiF, and Fe-containing compounds, such as Fe; Here, the Fe and LiF regions are visually contrasting regions of various nanodomains. When measured by TEM micrographs according to the identification of , or have a median physical dimension of 2-5 nm, or 5-15 nm, or 5-20 nm, etc.

[0135] (II. Garnet Materials) Disclosed herein are nanostructured lithium-filled garnet-based powders. Also disclosed herein are nanoparticles having physical dimensions less than 10 μm, e.g., d 50 Grain size is 10μm The lithium-filled garnet thin film may also have grains therein that are smaller than 100 nm. In some of these examples, the membranes are less than 50 μm thick. Membranes with thicknesses of less than 50 μm are several meters to several kilometers long. In some instances, the membrane has a high conductivity, which in some instances is greater than 10 -4 S / In some instances, the membrane is strong, has good mechanical integrity, and is lithium-ion. When used as an electrolyte in lithium secondary batteries, it prevents the ingress of lithium dendrites. Some of these membranes contain a cathode active material and, optionally, a binder, a dispersant, , solvents, and other electronic and ionic conductors. Described are methods for making these example membranes.

[0136] In another example, described herein is alumina-doped and highly Several lithium-loaded gallium arsenides have been developed that possess a unique combination of ionic conductivity and small grain size. In some instances, these compositions are lithium-loaded garnets. Lower temperature and shorter reaction time conditions than previously known possible for In some instances, novel sintering methods are utilized, among which Some of the new lithium-filled galvanic batteries utilize an argon gas environment rather than air. Further, in some examples, finely ground garnet powder, and or garnet precursors and / or metal powders to produce unique thin film structures. The present disclosure relates to the incorporation of aluminum therein, e.g., Describes several novel lithium-filled garnet ceramics having <Al2O3> which, conveniently and surprisingly, have the properties of high ionic conductivity and small crystal grain size.

[0137] (a. Lithium-filled garnet) (i. Electrolyte) In one example, the method described herein is Li A La B M' c M'' D Zr E O F Li A La B M' C M'' D T a E O F Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2 , 10 < F < 14 and M' and M' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba , Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 14 and Me'' is a metal selected from Nb, Ta, V , W, Mo, or Sb) and includes a garnet-type electrolyte material .

[0138] In one example, the method described herein is Li A La B M'​c M'' D Zr E O F 、Li A La B M' C M'' D T a E O F 、Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2 、10 < F < 13, and M' and M' are each, independently in each case, Al, Mo, W, Nb, Sb, Ca, Ba 、Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 13, and Me'' is a metal selected from Nb, Ta, V 、W, Mo, or Sb) selected from garnet-type electrolyte materials containing.

[0139] In one example, the method described herein is Li A La B M' C M'' D Nb E O F (where 4 < A < 8 .5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14, and M' and M' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta ) selected from garnet-type electrolytes containing.

[0140] In one example, the method described herein is Li A La B M' C M'' D Nb E O F (where 4 < A < 8 .5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 13, and M' and M' are each, respectively in each case independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta ) and includes a garnet-type electrolyte selected therefrom.

[0141] In one example, the method described herein is Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V, W , Mo, or Sb) and includes a garnet-type electrolyte selected therefrom .

[0142] In one example, the method described herein is Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 13, and Me'' is a metal selected from Nb, Ta, V, W , Mo, or Sb) and includes a garnet-type electrolyte selected therefrom .

[0143] In some embodiments, the garnet material described herein is used as an electrolyte are used. In some of these embodiments, the garnet has the formula [Chemical formula] wherein 5.0 < x < 9 and 0.1 < y < 1.5. In some of these examples , the electrolyte is Li x La3Zr2O 12 ·0.35Al2O3. In other ones of these examples, the electrolyte is Li7La3Zr2O 12 ·0.35Al2O3.

[0144] In some examples where the garnet is the electrolyte, the garnet contains neither Nb, nor Ta, nor W, nor Mo, which means herein that the concentration of these elements (e.g., Nb, Ta, W, or M o) is 10 parts per million (ppm) or less. In some examples , the concentration of these elements (e.g., Nb, Ta, W, or Mo) is 1 part per million (ppm) or less. In some examples, the concentration of these elements (e.g., Nb, Ta, W, or Mo) is 0.1 part per million (ppm) or less.

[0145] In some examples, the lithium-filled garnets described herein generally have the formula Li x A 3B2O 12 (where 5 < x < 7). In some of these examples , A is a large ion that occupies an eight-fold coordination lattice site. In some of these examples , A is La, Sr, Ba, Ca, or a combination thereof. In some examples , B is a smaller, more highly charged ion that occupies an octahedral site. In some of these examples, B is Zr, Hf, Nb, Ta, Sb, V, or a combination thereof. In some of these examples, the composition is Li x A3B2O 12 0.3 to 1 mole per In some of these examples, the composition is doped with Li. x A3B2O 12 The silicon dioxide was doped with 0.35 moles of Al per mole.

[0146] In some instances, the lithium-filled garnet is Li7La3Zr2O 12 (LLZ) and A In some instances, the LLZ is doped with lumina. The reactant is doped by adding Al2O3 to the reactant precursor mixture. The LLZ is doped with aluminum in an aluminum reaction vessel in contact with the LLZ. do.

[0147] In some instances, the alumina-doped LLZ can be, for example, 10 -4 S / cm or more It has high conductivity.

[0148] In some instances, higher conductivity can be achieved by replacing a portion of the Zr with a higher valence species, e.g., It is observed when partially replaced by Nb, Ta, Sb, or a combination of these. The conductivity is 10 at room temperature. -3 It can reach a height of as much as S / cm.

[0149] In some examples, the compositions described herein comprise Li x A3B2O 12 0.35 moles per Al doped Li x A3B2O 12In some of these examples, x is 5. In some other examples, x is 5.5. In still other examples, x is 6.0. In some other instances, x is 6.5. In other instances, x is 7.0. In this example, x is 7.5.

[0150] In some examples, the garnet-based composition comprises Li x A3B2O 12 0.3, 0.35, 0.4, 0. 45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or 1 mole of Al was added. It is being played.

[0151] In some examples, the garnet-based composition comprises Li x A3B2O 12 0.35 moles of Al per dope It is grouped.

[0152] In the examples herein, the subscripts and molar coefficients in the empirical formulas are used to prepare the examples described. The amount of raw material initially batched to prepare the mixture is based on the amount of raw material that is initially batched to prepare the mixture.

[0153] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By characterized in that: <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E≦2、10<F≦13で M′ and M″, independently in each occurrence, are absent or Al, Mo, W, Nb, Sb, Ca, are each independently selected from Ba, Sr, Ce, Hf, Rb, or Ta; and The molar ratio of the net to Al2O3 is 0.05 to 0.7.

[0154] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By characterized in that: <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E≦2、10<F≦13で M′ and M″, independently in each occurrence, are absent or Al, Mo, W, Nb, Sb, Ca, are each independently selected from Ba, Sr, Ce, Hf, Rb, or Ta; and Li: The molar ratio of Al is 0.05 to 0.7.

[0155] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By characterized in that: <A<10、2<B<6、0≦C≦2、0≦D≦2; 0≦E≦3、8<F≦14であり , M', and M'' are each independently either non-existent or each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; and the molar ratio of garnet:Al2O3 is 0.01 - 2.

[0156] In some examples, the present disclosure provides a composition comprising a lithium - filled garnet and Al2O3. In one example, the lithium - filled garnet is doped with alumina. In some examples, the lithium - filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F characterized by, where 2 < A < 10, 2 < B < 6, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E ≤ 3, 8 < F ≤ 14, M', and M'' are each independently either non - existent or each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; and the molar ratio of Li:Al is 0.01 - 2.

[0157] In some examples, the lithium - filled garnet is Li A La B Zr C M' D M'' E O 12 where 5 < A < 7.7, 2 < B < 4, 0 < C < 2.5, M' comprises a metal dopant selected from materials containing Al, 0 < D < 2, and M'' comprises a metal dopant selected from materials containing Nb, Ta, V, W, Mo, Sb, 0 < e < 2. In some examples, the lithium - filled garnet ​​​the entire contents of which are hereby incorporated by reference for all purposes. A method for forming a garnet material using a sintering process, filed on October 7, 2013, METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTERING PROCESS ) is a lithium-filled garnet as described in U.S. Provisional Patent Application No. 61 / 887,451. do.

[0158] In some of the above examples, A is 6. In some other examples, A is 6.5 In another example, A is 7.0. In another example, A is 7.5. In the example, A is 8.0.

[0159] In some of the above examples, B is 2. In some other examples, B is 2.5 In another example, B is 3.0. In another example, B is 3.5. In one example, B is 3.5. In yet another example, B is 4.0.

[0160] In some of the above examples, C is 0.5. In other examples, C is 0.6. In some other instances, C is 0.7. In some other instances, C is 0.8. In some other examples, C is 0.9. In other examples, C is 1.0. In still other examples, In one example, C is 1.1. In another example, C is 1.2. In another example, C is 1.3. In some other instances, C is 1.4. In some other instances, C is 1.5. In some other examples, C is 1.6. In other examples, C is 1.7. In still other examples, In one example, C is 1.8. In another example, C is 1.9. In yet another example, C is 2.0. In some other examples, C is 2.1. In some other examples, C is 2.2. In some other examples, C is 2.3. In some other examples, C is 2.4. In one example, C is 2.5. In yet another example, C is 2.6. In another example, C is 2.7. In still other examples, C is 2.8. In other examples, C is 2.9. In another example, C is 3.0.

[0161] In some of the above examples, D is 0.5. In other examples, D is 0.6. In some other instances, D is 0.7. In some other instances, D is 0.8. In some other examples, D is 0.9. In other examples, D is 1.0. In some instances, D is 1.1. In some instances, D is 1.2. In other instances, D is 1.3. In some other instances, D is 1.4. In some other instances, D is 1.5. In some other examples, D is 1.6. In other examples, D is 1.7. In some instances, D is 1.8. In some instances, D is 1.9. In yet other instances, D is 2.0. In some other examples, D is 2.1. In some other examples, D is 2.2. In some other examples, D is 2.3. In some other examples, D is 2.4. In one example, D is 2.5. In yet another example, D is 2.6. In one example, D is 2.7. In still other instances, D is 2.8. In other instances, D is 2.9. In another example, D is 3.0.

[0162] In some of the above examples, E is 0.5. In other examples, E is 0.6. In some other instances, E is 0.7. In some other instances, E is 0.8. In some other examples, E is 0.9. In other examples, E is 1.0. In still other examples, In some instances, E is 1.1. In some instances, E is 1.2. In other instances, E is 1.3. In some other instances, E is 1.4. In some other instances, E is 1.5. In some other examples, E is 1.6. In other examples, E is 1.7. In still other examples, In some instances, E is 1.8. In some instances, E is 1.9. In yet other instances, E is 2.0. In some other examples, E is 2.1. In some other examples, E is 2.2. In some other examples, E is 2.3. In some other examples, E is 2.4. In one embodiment, E is 2.5. In yet another embodiment, E is 2.6. In another embodiment, E is 2.7. In still other examples, E is 2.8. In other examples, E is 2.9. In another example, E is 3.0.

[0163] In some of the above examples, F is 11.1. In other examples, F is 11.2. In some other instances, F is 11.3. In some other instances, F is 11.4. In certain other instances, F is 11.5. In other instances, F is 11.6. In one example, F is 11.7. In another example, F is 11.8. In another example, F is 11. 9. In some other instances, F is 12. In some other instances, F is 12. In some other examples, F is 12.2. In other examples, F is 12.3. In yet another example, F is 12.3. In one example, F is 12.4. In yet another example, In some other examples, F is 12.5. In other examples, F is 12.6. In some other examples, F is 12. In some other instances, F is 12.8. In some other instances, E is 12. In another example, F is 13.

[0164] In some examples, provided herein is a compound having the empirical formula [ka] wherein 5.0 <x<9かつ0.1<y<1.5である。いく In some examples, x is 5. In other examples, x is 5.5. In some examples, x is 6. In other examples, x is 7. In some examples, x is 7.5. In other examples, x is 8. In some examples, y is 0.3. In some examples, y is 0.35. In other examples, y is 0.4. In some examples, y is 0.45. In some examples, y is 0.5. In other examples, y is 0.55. In some examples, y is 0.6. In some instances, y is 0.7. In some instances, y is 0.75. In other instances, y is 0.8. In some examples, y is 0.85. In other examples, y is 0.9. In some examples, y is 0.95. In other examples, y is 1.0.

[0165] In some examples, provided herein is a compound having the empirical formula Li 7.0 La3(Zr t1 +Nb t2 +Ta t 3) O 12 +0.35Al2O3. In this formula, La and (Zr+Nb +Ta) is 3:2 molar ratio, so that t1 + t2 + t3 = subscript 2.

[0166] In some examples, provided herein is a compound having an empirical formula of Li7La3Zr2O 12 0.35Al2O3 The composition is characterized by:

[0167] In some of the above examples, A is 5, 6, 7, or 8. is 7.

[0168] In some of the above examples, M' is Nb and M'' is Ta.

[0169] In some of the above examples, E is 1, 1.5, or 2. In certain examples, E is 2.

[0170] In some of the above examples, C and D are zero.

[0171] In some examples, provided herein are crystalline ... 0.65〜0.65 In some examples, the Li:Al ratio is 7:0.2~7:1.3. In some examples, the Li:Al ratio is between 7:0.3 and 7:1.2. The ratio is from 7:0.3 to 7:1.1. In some examples, the Li:Al ratio is from 7:0.4 to 7:1.0. In some examples, the Li:Al ratio is 7:0.5 to 7:0.9. The ratio is from 7:0.6 to 7:0.8. In some examples, the Li:Al ratio is about 7:0.7. In that example, the Li:Al ratio is 7:0.7.

[0172] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.15 〜0.55.

[0173] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.25 〜0.45.

[0174] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.35 It is a composition wherein

[0175] In some examples, provided herein are quartz crystals having an Al to garnet molar ratio of 0.35 or less. It is a composition.

[0176] In some examples, provided herein is a lithium-filled garnet having the empirical formula Li7La3Zr2O 12 and being doped with aluminum. do.

[0177] In some instances, the lithium-filled garnet is Li7La3Zr2O 12 (LLZ) and A In some instances, the LLZ is doped with lumina. The reactant is doped by adding Al2O3 to the reactant precursor mixture. The LLZ is doped with aluminum in an aluminum reaction vessel in contact with the LLZ. When the LLZ is doped with alumina, it is possible to obtain a conductive layer that enhances the conductivity of the lithium-loaded garnet. In some instances, this increased conductivity is due to increased ionic conductivity. (For example, Li + ) is called conductivity.

[0178] (ii. Catholyte) Catalytic agents suitable for use with the compositions, devices, and methods described herein The material may be, but is not limited to, Li A La B M' c M'' D Zr E O F , Li A La B M' C M'' D Ta E O F , Li A La B M' C M'' D Nb E O F (where 4 <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E<2、10< F<14, M' and M'' are each, independently in each occurrence, Al, Mo, W, Nb, Sb, Ca, Ba, Sr , Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 <a<7 .7;2 <b<4; 0<c≦2.5; 0≦d<2; 0≦e<2、10<f<14であり、Me''は、Nb、Ta、V、W Garnet materials selected from metals selected from (), Mo, or Sb) are included In some embodiments, the garnet material is Li A La B M' c M'' D Zr E O F is. In In some other embodiments, the garnet material is Li A La B M' C M'' D Ta E O F is. In other In embodiments, the garnet material is Li A La B M' C M'' D Nb E O F is.

[0179] In the above examples, the values of the subscripts (4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14) characterize the ratio of the reactants used to make the garnet material Some deviation from these reactant ratios may be present in the garnet product as well. As used herein, the garnet precursor refers to the reactants used to produce or synthesize the garnet.

[0180] In the above examples, the values of the subscripts (e.g., 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13) characterize the ratio of the reactants used to make the garnet material Some deviation from these reactant ratios may be present in the garnet product as well. As used herein, the garnet precursor is used to produce garnet Refers to the reactants used to cause.

[0181] In the above examples, as the values of the subscripts, 4 < A < 8.5, 1.5 < B < 4, C < 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14 can also be cited. In some examples, C is equal to 1.99 or less than that.

[0182] In the above examples, as the values of the subscripts, 4 < A < 8.5, 1.5 < B < 4, C < 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13 can also be cited. In some examples, C is equal to 1.99 or less than that.

[0183] In one embodiment, the garnet is a lithium-filled garnet.

[0184] In some embodiments, the garnet is Li a La b Zr c Al d Me'' e O f Characterized by where the subscript is characterized by the above values.

[0185] In some embodiments, the lithium-filled garnet is lithium lanthanum zirconium oxide mixed with aluminum oxide. In some of these examples the lithium lanthanum zirconium oxide is characterized by the formula Li La3Zr2O 7.0 La3Zr2O 12 +0.35Al2O3, where the subscripts and coefficients represent the molar ratios determined based on the reactants used to make the garnet. In the formula, the subscripts and coefficients represent the molar ratios determined based on the reactants used to make the garnet. The reactants are based on the reactants used to make the garnet.

[0186] In some embodiments, the ratio of La:Zr is 3:2. Garnet is Li 7.0 La3(Zr t1 +Nb t2 +Ta t3 )O 12 +0.35Al2O3; where La: (Zr / Nb / Ta) (t1+t2+t3=subscript 2) so that the ratio is 3:2.

[0187] In some instances, the garnet is Li x La3Zr2O 12 +yAl2O3, where x is 5.5 1 to 9; and y ranges from 0 to 1. In some examples, x is 7 and y is 0. It is 35.

[0188] The catholytes described herein may, in some embodiments, be formed by adding a carbon electronic conductive additive. A lithium conductive gas filled with an additive, a lithium conductive polymer binder, and an active material. The active material loading is high energy density. In some instances, the volume percent may be greater than 50 to allow for a high degree of uniformity. The garnet is sintered and has a porosity of >70% to allow for the volume of other components. The disclosure herein addresses some of the problems associated with assembling solid-state energy storage devices. The present invention overcomes the above problems, including, but not limited to, the development of a well-developed particle indirect contact points and reduced interparticle spacing allowing for greater current flow without significant voltage drop Sintering the composite electrodes with electrical resistance; also, sintering the entire device (electrodes and electrolyte) in one process. and the use of flammable liquid electrolytes, which may pose a safety hazard. and a method for producing a solid-state energy storage device that eliminates the need for using a FAS membrane. T sintering to reduce process time and cost in electrochemical device fabrication; and FAST Sintering is performed to densify the components of the electrode composite without significant interdiffusion or adverse chemical reactions. There is a way to do this.

[0189] (iii. Composite materials) In some embodiments, disclosed herein is a method of In some examples, the device is a composite electrochemical device manufactured by , an active electrode material, an electrolyte, a conductive additive, and combinations thereof. at least one layer including a garnet-type electrolyte; In some examples, the composite material has the structure shown in FIG.

[0190] In some embodiments, the device comprises at least one active anode material. The active anode material may further include a layer of carbon, silicon, silicon oxide, tin, or the like. and combinations thereof.

[0191] In some embodiments, disclosed herein are anodes and anode current collectors. at least one layer including a garnet solid electrolyte (SSE) in contact with the anode; at least one layer comprising a porous garnet in contact with said garnet SSE; wherein the porous garnet optionally contains carbon, a lithium conductive polymer, an active cathode, At least one member selected from the group consisting of: being; and at least one layer comprising an aluminum cathode current collector in contact with the porous garnet wherein the porous garnet layer is at least 70% porous by volume; wherein the garnet is Li A La B M' c M'' D Zr E O F 、Li A La B M' C M'' D Ta E O F 、Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14, and M' and M'' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f ≤ 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb ), and is selected from the materials); the active electrode material is NCA (lithium nickel cobalt aluminum oxide), LMNO (lithium manganese nickel oxide) , NMC (lithium nickel manganese cobalt oxide), LCO (lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiF x , where x is 0 to 2.5), copper fluoride (CuF y , where where y is 0 to 2.5), or FeF z (where z is selected from 0 to 3.5) In some examples, the layered material is a cathode material for an electrochemical device. The layered structure is substantially as shown in FIG.

[0192] In an embodiment, both sides of the layer comprising the anode and the anode current collector each independently comprise: and each garnet SSE layer is in contact with a porous garnet SSE layer. is in contact with the layer.

[0193] (b. powder) (i. Nanocrystalline Powder) In some instances, the lithium-filled garnet powders described herein are nano-sized. These powders are therefore crystalline or nanostructured. domains, where the median crystalline domain diameter is a domain having a physical dimension (e.g., diameter) of about In some examples, the crystalline domains are about 0.5 nm in diameter. In some other examples, the crystalline domains are about 1 nm in diameter. In one embodiment, the crystalline domains are about 1.5 nm in diameter. In yet another embodiment, the crystalline domains are about 2 nm in diameter. In some instances, the crystalline domains are about 3.0 nm in diameter. In yet another example, the crystalline domains are about 3.5 nm in diameter. The crystalline domains are about 4.0 nm in diameter. In some examples, the crystalline domains are In some other instances, the crystalline domains are about 5.5 nm in diameter. In another example, the crystalline domains are about 6.0 nm in diameter. In another embodiment, the crystalline domains are about 6.5 nm in diameter. In some instances, the crystalline domains are about 7.0 nm in diameter. In yet another example, the crystalline domains are about 8.0 nm in diameter. In some examples, the crystalline domains are about 8.5 nm in diameter. The crystalline domains are about 8.5 nm in diameter. In some other examples, the crystalline domains In another example, the crystalline domain is about 9 nm in diameter. In still other examples, the crystalline domains are about 10 nm in diameter. In some instances, the crystalline domains are about 10.5 nm in diameter. In yet another example, the crystalline domains are about 11.0 nm in diameter. In other examples, the crystalline domains are about 12.0 nm in diameter. In some examples, the crystalline domains are about 12.5 nm in diameter. The crystalline domains are about 13.5 nm in diameter. In yet another example, the crystalline domains are about 14.5 nm in diameter. In other examples, the crystalline domains are about 15.0 nm in diameter. In one embodiment, the crystalline domains are about 15.5 nm in diameter. In another example, the crystalline domains are about 16.0 nm in diameter. In some instances, the crystalline domains are about 17 nm in diameter. In some other instances, the crystalline domains are about 17.5 nm in diameter. The crystalline domains are about 18 nm in diameter. In yet another example, the crystalline domains are In yet another embodiment, the crystalline domains are about 18.5 nm in diameter. In some instances, the crystalline domains are about 19.5 nm in diameter. In one embodiment, the crystalline domains are about 20 nm in diameter. In some instances, the crystalline domains are about 20.5 nm in diameter. In some other instances, the crystalline domains are about 21.5 nm in diameter. In one embodiment, the crystalline domains are about 22.0 nm in diameter. In another embodiment, the crystalline domains are approximately 22.5 nm in diameter. In some instances, the crystalline domains are about 23.0 nm in diameter. In yet another embodiment, the crystalline domains are about 24.0 nm in diameter. In some examples, the crystalline domains are about 24.5 nm in diameter. In some other instances, the crystalline domains are about 25.5 nm in diameter. In another example, the crystalline domains are about 26 nm in diameter. In other instances, the crystalline domains are about 27 nm in diameter. The crystalline domains are about 27.5 nm in diameter. In some examples, the crystalline domains are In yet another example, the crystalline domains are about 28.5 nm in diameter. In other examples, the crystalline domains are about 29.0 nm in diameter. In some other examples, the crystalline domains are about 29.5 nm in diameter. In another example, the crystalline domains are about 30 nm in diameter. In yet another example, the crystalline domains are about 31 nm in diameter. In some instances, the crystalline domains are about 32 nm in diameter. In yet another embodiment, the crystalline domains are approximately 33 nm in diameter. In another example, the crystalline domains are about 35 nm in diameter. In some instances, the crystalline domains are about 40 nm in diameter. In another example, the crystalline domains are about 45 nm in diameter. In yet another embodiment, the crystalline domains are about 55 nm in diameter. In other instances, the crystalline domains are about 60 nm in diameter. In yet another embodiment, the crystalline domains are about 65 nm in diameter. In another example, the crystalline domains are about 70 nm in diameter. In some instances, the crystalline domains are about 85 nm in diameter. In one embodiment, the crystalline domain is about 90 nm in diameter. In yet another example, the crystalline domains are about 100 nm in diameter. In still other examples, the crystalline domains are about 150 nm in diameter. In one embodiment, the crystalline domains are about 200 nm in diameter. The crystalline domains are about 250 nm in diameter. In some instances, the crystalline domains are about 350 nm in diameter. In some other instances, the crystalline domains are about 400 nm in diameter. In yet another embodiment, the crystalline domains are about 450 nm in diameter. In another embodiment, the crystalline domains are about 500 nm in diameter. In some instances, the crystalline domains are about 600 nm in diameter. In one embodiment, the crystalline domain is about 650 nm in diameter. The domains are about 700 nm in diameter. In some instances, the crystalline domains are In some other instances, the crystalline domains are about 800 nm in diameter. In another example, the crystalline domains are about 850 nm in diameter. In another embodiment, the crystalline domains are about 900 nm in diameter. In some instances, the crystalline domains are about 950 nm in diameter. 0nm.

[0194] (ii. Microcrystalline granular powder) Grain size, as used herein, unless otherwise specified, is measured by microscopy, e.g. , by transmission electron microscopy or scanning electron microscopy, or by x-ray diffraction. can be.

[0195] In some examples, provided herein are d less than 10 μm. 50Crystals with diameter In one embodiment, the membrane has grains of less than 9 μm. 50 The grains have a diameter In other examples, the grains have a diameter of d less than 8 μm. 50 In some instances, the diameter , the grain size is less than 7 μm d 50 In some instances, the membrane has a diameter of less than 6 μm. 50 Diameter In another example, the film has grains having a d of less than 5 μm. 50 The grains have a diameter In some instances, the membrane has a d of less than 4 μm. 50 It has grains with a diameter. In the example, the membrane has a thickness of less than 3 μm. 50 In one example, the film has grains having a diameter , d less than 2 μm 50 In another example, the membrane has grains with a diameter of less than 1 μm. 50 straight The grains have a diameter.

[0196] As used herein, the microcrystal grains in the films described herein are between 10 nm and 10 μm d 50 In some examples, the crystallites in the films described herein have a diameter of 1 00nm~10μm d 50 It has a diameter.

[0197] In some examples, the films described herein have a Young's modulus of about 130-150 GPa. In some other examples, the films described herein have a Vickers hardness of about 5-7 GPa. It has a quality.

[0198] In some instances, the membranes described herein have a porosity of less than 20%. In some examples, the membranes described herein have a porosity of less than 10%. In some embodiments, the membranes described herein have a porosity of less than 5%. The membranes described herein have a porosity of less than 3%. In some instances, the porosity is , measured by pycnometry or mercury porosimetry.

[0199] (c.membrane) (i. Uncalcined film) Described herein are films that include garnet precursors, optionally including calcined garnet. These films and powders are then heated or cooled to form lithium-loaded garnets. These films and powders are then cooled to room temperature before sufficient time has passed for the precursors to react to form the In some instances, several layers of lithium-loaded garnet are fabricated. In order to obtain lithium-loaded garnet films, the following garnet precursor slurries were mixed and calcined: In some instances, the calcined lithium-loaded garnet is layered, deposited, or laminated. A slurry of the following garnet precursors was added to the mold so that it would penetrate into the open or porous spaces within the mold: is overlaid, deposited or laminated onto the calcined film of lithium loaded garnet.

[0200] In some instances, the present disclosure relates to a garnet precursor or optionally a pseudomorph. In some examples, the thin, free-standing garnet film includes a fused garnet. These films are made of at least one selected from a binder, a solvent, a dispersant, or a combination thereof. In some examples, the garnet solids loading is at least 30% by weight. (w / w). In some instances, the membrane thickness is less than 100 μm.

[0201] In certain instances, the dispersant is fish oil, Mehaden Blown Fish Oil, phosphate esters, rhodal ine(trademark), Rhodoline 4160, phospholan-131(trademark), BYK(trademark) 22124, BYK-22146(trademark) ), Hypermer KD1™, Hypermer KD6™, and Hypermer KD7™.

[0202] In some instances, the membrane includes a substrate attached thereto. The material is a polymer, a metal foil, or a metal powder. In some of these examples, the The substrate is a metal foil. In some examples, the substrate is a metal powder. In some of the above, the metal is Ni, Cu, Al, steel, an alloy thereof, or a combination thereof. is selected from the combination.

[0203] 2. The membrane of claim 1, wherein the solids loading is at least 35% w / w.

[0204] In some instances, the membrane has a solids loading of at least 40% w / w. In some embodiments, the membrane has a solids loading of at least 45% w / w. In another embodiment, the solids loading is at least 50% w / w. In some other examples, the solids loading is at least 60 In some instances, the solids loading is at least 65% w / w. In some other instances, the solids loading is at least 70% w / w. The solids loading is at least 75% w / w. In some instances, the solids loading is less than 75% w / w. At most 80% w / w.

[0205] In some instances, the uncalcined membrane has a thickness of less than 75 μm and greater than 10 nm. In some examples, the uncalcined membrane has a thickness of less than 50 μm and more than 10 nm. In the uncalcined membrane, the particles are less than 1 μm in their maximum physical dimension. In some instances, the uncalcined membrane has a median grain size of 0.1 μm to 10 μm. In the examples, the uncalcined film is not adhered to any substrate.

[0206] In some instances, the present disclosure relates to a garnet precursor or optionally a pseudomorph. In some examples, the thin, free-standing garnet film includes a fused garnet. These films are made of at least one selected from a binder, a solvent, a dispersant, or a combination thereof. In some examples, the garnet solids loading is at least 30% by volume. (v / v). In some instances, the membrane thickness is less than 100 μm.

[0207] In some instances, the membrane has a solids loading of at least 40% v / v. In some embodiments, the membrane has a solids loading of at least 45% v / v. In another embodiment, the membrane has a solids loading of at least 50% v / v. In some other examples, the solids loading is at least 60 In some instances, the solids loading is at least 65% v / v. In some other instances, the solids loading is at least 70% v / v. The solids loading is at least 75% v / v. In some instances, the solids loading is less than 75% v / v. At most 80% v / v.

[0208] (a. Calcined membrane) The uncalcined membrane described in this specification is a membrane that is heated to about 200° C. to 1200° C. for about 20 minutes to 10 hours or crystallized. The calcination can be carried out by heating until polymerization occurs.

[0209] (ii. Unsintered Membrane) In some instances, the garnet-based films are unsintered, referred to as "green" films. and is several kilometers long.

[0210] In one embodiment, the disclosure herein provides a method for making an energy storage electrode. providing a green thin film, wherein the green thin film comprises a garnet-type electrolyte; , an active electrode material, a conductive additive, a solvent, a binder, and combinations thereof. removing solvent if present in the green thin film; optionally laminating the film to a surface; removing the binder, if present in the film. sintering the film, where sintering can be by thermal sintering or electric field assisted sintering (FAST). wherein thermal sintering the film includes sintering the film at a temperature ranging from about 700° C. to about 1200° C. for about 1 to about 600° C. 1 min and in an atmosphere having an oxygen partial pressure of 1e-1 atm to 1e-15 atm; and ST sintering is a process in which the film is heated to a temperature range of about 500°C to about 900°C and DC or The method includes applying an AC electric field.

[0211] In some of the methods disclosed herein, the green thin film may be from about 10 μm to about 100 μm. In some other of the methods disclosed herein, The green thin film has a thickness of about 20 μm to about 100 μm. In some cases, the green thin film has a thickness of about 30 μm to about 100 μm. In other of the methods described, the green thin film has a thickness of about 40 μm to about 100 μm. In yet another method disclosed herein, the green thin film has a thickness of about 50 μm to about 100 μm. In still other methods disclosed herein, the green thin film has a thickness of about 60 μm. In still other methods disclosed herein, the method further comprises: The green thin film has a thickness of about 70 μm to about 100 μm. In some cases, the green thin film has a thickness of about 80 μm to about 100 μm. In some other of the methods described, the green thin film is about 90 μm to about 100 μm. It has a thickness.

[0212] In some of the methods disclosed herein, the green thin film may be from about 10 μm to about 90 μm. In some other of the methods disclosed herein, The green thin film has a thickness of about 20 μm to about 80 μm. In the present invention, the green thin film has a thickness of about 30 μm to about 70 μm. In other of the methods, the green thin film has a thickness of about 40 μm to about 60 μm. In yet another method disclosed herein, the green thin film has a thickness of about 50 μm to about 90 μm. In still other methods disclosed herein, the green thin film has a thickness of about 60 μm to about 90 μm. In still other methods disclosed herein, the green thin film has a thickness of The thickness of the film is about 70 μm to about 90 μm. In the method disclosed herein, the green thin film has a thickness of about 80 μm to about 90 μm. In some others of these, the green thin film has a thickness of about 30 μm to about 60 μm.

[0213] In some instances, the green film is about 50 percent larger in volume than the sintered film. In some examples, the sintered membrane has a thickness of about 1 to 150 μm. In some instances, the sintered film has a thickness of about 1 μm. In some other instances, the sintered film has a thickness of about 1 μm. In one embodiment, the sintered membrane has a thickness of about 3 μm. In some examples, the sintered film has a thickness of about 4 μm. In some instances, the sintered membrane has a thickness of about 6 μm. In some of the examples, the sintered film has a thickness of about 7 μm. In some other examples, the sintered film has a thickness of about 9 μm. In one example, the sintered membrane has a thickness of about 10 μm.

[0214] In some instances, sintering can extend the length of the film by about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 , 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25% The thickness of the film is reduced by about 50, about 40, about 30, about 20, about 10, or about 5% without any increase in the thickness. As used herein, thickness refers to the average thickness in the z-direction (as shown in FIG. 23). As used herein, length refers to the average length in either the x- or y-direction (as shown in FIG. 23). In some instances, the sintering described herein occurs in a manner that is proportionally greater in the z-direction than in the x- or y-directions. In some cases, sintering occurs primarily in the x- or y-direction, resulting in a decrease in the thickness of the film in the x- or y-direction (as shown in FIG. 23). reduces the film thickness in the z-direction proportionally more than in either the y-direction. In this example, sintering reduces the length of the film in either the x- or y-direction proportionally more than sintering reduces the length of the film in either the x- or y-direction. This substantially reduces the thickness of the membrane in the z-direction (as shown in FIG. 23). Substantially greater is at least 50%, at least 60%, at least 70%, Examples of the chromatic aberration include, but are not limited to, at least 80%, at least 90%, or at least 100%.

[0215] (iii. Sintered film) In some of these examples, the sintered film has a thickness of about 10 nm. In another example, the sintered film has a thickness of about 11 nm. In one example, the sintered film has a thickness of about 12 nm. In some other instances, the sintered film has a thickness of about 13 nm. In some examples, the sintered film has a thickness of about 14 nm. In some of these examples, the sintered film has a thickness of about 16 nm. In some examples, the sintered film has a thickness of about 17 nm. In one example, the sintered film has a thickness of about 18 nm. In another example, the sintered film has a thickness of about 19 nm. In some of these examples, the sintered film has a thickness of about 20 nm. In some other examples, the sintered film has a thickness of about 21 nm. In some other examples, the sintered film has a thickness of about 23 nm. In some other examples, the sintered film has a thickness of about 24 nm. has a thickness of about 25 nm. In some instances, the sintered film has a thickness of about 26 nm. In some of these examples, the sintered film has a thickness of about 27 nm. In some other examples, the sintered film has a thickness of about 28 nm. In some examples, the sintered film has a thickness of about 30 nm. In some of these, the sintered film has a thickness of about 31 nm. In one example, the sintered film has a thickness of about 32 nm. In another example, the sintered film has a thickness of about 33 nm. In certain other instances, the sintered film has a thickness of about 34 nm. The sintered film has a thickness of about 35 nm. In some examples, the sintered film has a thickness of about 36 nm. In some of these examples, the sintered film has a thickness of about 37 nm. In some examples, the sintered film has a thickness of about 38 nm. In some other examples, the sintered film In one example, the sintered film has a thickness of about 40 nm. In some of the examples, the sintered film has a thickness of about 41 nm. In one example, the sintered film has a thickness of about 42 nm. In another example, the sintered film has a thickness of about 43 nm. In certain other examples, the sintered film has a thickness of about 44 nm. In some instances, the sintered film has a thickness of about 45 nm. In some instances, the sintered film has a thickness of about 46 nm. In some of these examples, the sintered film has a thickness of about 47 nm. In some instances, the sintered film has a thickness of about 48 nm. The sintered film has a thickness of about 49 nm. In one example, the sintered film has a thickness of about 50 nm. In some of these examples, the sintered film has a thickness of about 51 nm. In one example, the sintered film has a thickness of about 52 nm. In one example, the sintered film has a thickness of about 53 nm. In some other examples, the sintered film has a thickness of about 54 nm. In some examples, the sintered film has a thickness of about 55 nm. In some of these examples, the sintered film has a thickness of about 57 nm. In some examples, the sintered film has a thickness of about 58 nm. In one example, the sintered film has a thickness of about 59 nm. In another example, the sintered film has a thickness of about 60 nm. do.

[0216] In some of these examples, the sintered membrane has a thickness of about 11 μm. In another example, the sintered film has a thickness of about 12 μm. In some other examples, the sintered membrane has a thickness of about 14 μm. In some other instances, the sintered film has a thickness of about 15 μm. The membrane has a thickness of about 16 μm. In some of these examples, the sintered membrane has a thickness of about 17 μm. In some examples, the sintered membrane has a thickness of about 18 μm. In some other examples, the sintered membrane has a thickness of about 19 μm. In some of these examples, the sintered membrane has a thickness of about 21 μm. In some other examples, the sintered film has a thickness of about 22 μm. In one embodiment, the sintered membrane has a thickness of about 23 μm. In another embodiment, the sintered membrane has a thickness of about 24 μm. In some other examples, the sintered membrane has a thickness of about 25 μm. In some examples, the sintered membrane has a thickness of about 26 μm. In some instances, the sintered membrane has a thickness of about 27 μm. In some instances, the sintered membrane has a thickness of about 28 μm. In some other examples, the sintered membrane has a thickness of about 29 μm. In some of these examples, the sintered film has a thickness of about 30 μm. The sintered membrane has a thickness of about 31 μm. In some other examples, the sintered membrane has a thickness of about 32 μm. In one example, the sintered membrane has a thickness of about 33 μm. In some instances, the sintered membrane has a thickness of about 34 μm. In some other instances, the sintered membrane has a thickness of about 35 μm. In some examples, the sintered membrane has a thickness of about 36 μm. In some of the examples, the sintered film has a thickness of about 37 μm. In some instances, the sintered membrane has a thickness of about 38 μm. In some other instances, the sintered membrane has a thickness of about 39 μm. In some examples, the sintered membrane has a thickness of about 40 μm. In some examples, the sintered film has a thickness of about 41 μm. The sintered membrane has a thickness of about 42 μm. In one example, the sintered membrane has a thickness of about 43 μm. In some other examples, the sintered membrane has a thickness of about 44 μm. In some instances, the sintered membrane has a thickness of about 45 μm. In some instances, the sintered membrane has a thickness of about 46 μm. In some of these examples, the sintered membrane has a thickness of about 47 μm. In some examples, the sintered membrane has a thickness of about 48 μm. In one example, the sintered membrane has a thickness of about 49 μm. In another example, the sintered membrane has a thickness of about 50 μm. In some of these examples, the sintered membrane has a thickness of about 51 μm. In some other examples, the sintered membrane has a thickness of about 52 μm. In some instances, the sintered membrane has a thickness of about 53 μm. In other instances, the sintered membrane has a thickness of about 54 μm. In some other examples, the sintered membrane has a thickness of about 55 μm. The conjunctiva has a thickness of about 56 μm. In some of these examples, the sintered membrane has a thickness of about 5 In some instances, the sintered membrane has a thickness of about 58 μm. In some other examples, the sintered membrane has a thickness of about 59 μm. , having a thickness of about 60 μm.

[0217] In some of these examples, the sintered membrane has a thickness of about 61 μm. In another example, the sintered membrane has a thickness of about 62 μm. In some other examples, the sintered membrane has a thickness of about 64 μm. In some other instances, the sintered membrane has a thickness of about 65 μm. The membrane has a thickness of about 66 μm. In some of these examples, the sintered membrane has a thickness of about 67 μm. In some examples, the sintered membrane has a thickness of about 68 μm. In some other examples, the sintered membrane has a thickness of about 69 μm. In some of these examples, the sintered membrane has a thickness of about 71 μm. In some other examples, the sintered membrane has a thickness of about 72 μm. In one embodiment, the sintered membrane has a thickness of about 73 μm. In another embodiment, the sintered membrane has a thickness of about 74 μm. In some other examples, the sintered membrane has a thickness of about 75 μm. In some examples, the sintered membrane has a thickness of about 76 μm. In some instances, the sintered membrane has a thickness of about 77 μm. In some instances, the sintered membrane has a thickness of about 78 μm. In some other examples, the sintered membrane has a thickness of about 79 μm. In some of these examples, the sintered membrane has a thickness of about 80 μm. The sintered membrane has a thickness of about 81 μm. In some other examples, the sintered membrane has a thickness of about 82 μm. In one example, the sintered membrane has a thickness of about 83 μm. In some instances, the sintered membrane has a thickness of about 84 μm. In some other instances, the sintered membrane has a thickness of about 85 μm. In some examples, the sintered membrane has a thickness of about 86 μm. In some of the examples, the sintered membrane has a thickness of about 87 μm. In some examples, the sintered membrane has a thickness of about 88 μm. In some other examples, the sintered membrane has a thickness of about 89 μm. In some examples, the sintered membrane has a thickness of about 90 μm. In some examples, the sintered film has a thickness of about 91 μm. The sintered membrane has a thickness of about 92 μm. In one example, the sintered membrane has a thickness of about 93 μm. In some other examples, the sintered membrane has a thickness of about 94 μm. In some instances, the sintered membrane has a thickness of about 95 μm. In some instances, the sintered membrane has a thickness of about 96 μm. In some of these examples, the sintered membrane has a thickness of about 97 μm. In some examples, the sintered membrane has a thickness of about 98 μm. In one example, the sintered membrane has a thickness of about 99 μm. In another example, the sintered membrane has a thickness of about 100 μm. do.

[0218] In certain other examples, the sintered film has a thickness of about 100 nm. In some other examples, the sintered film has a thickness of about 1 μm. In some examples, the sintered film has a thickness of about 2 μm. In some other instances, the sintered film has a thickness of about 2 μm. In some examples, the sintered film has a thickness of about 5 μm. The membrane has a thickness of about 3 μm. In another example, the sintered membrane has a thickness of about 4 μm. In some examples, the sintered film has a thickness of about 300 nm. In some instances, the sintered film has a thickness of about 200 nm. .

[0219] In some of these examples, the sintered membrane has a thickness of about 101 μm. In another example, the sintered membrane has a thickness of about 102 μm. In some instances, the sintered membrane has a thickness of about 103 μm. In some other examples, the sintered film has a thickness of about 105 μm. The conjunctiva has a thickness of about 106 μm. In some of these examples, the sintered membrane has a thickness of about In some instances, the sintered membrane has a thickness of about 108 μm. In some other examples, the sintered membrane has a thickness of about 109 μm. In some of these examples, the sintered membrane has a thickness of about 111 μm. In some other instances, the sintered membrane has a thickness of about 112 μm. In some instances, the sintered membrane has a thickness of about 113 μm. In some other examples, the sintered membrane has a thickness of about 115 μm. In some examples, the sintered membrane has a thickness of about 116 μm. In some cases, the sintered membrane has a thickness of about 117 μm. In some other examples, the sintered membrane has a thickness of about 119 μm. In some examples, the sintered membrane has a thickness of about 120 μm. In some instances, the sintered membrane has a thickness of about 121 μm. In some other instances, the sintered membrane has a thickness of about 121 μm. In one example, the sintered membrane has a thickness of about 123 μm. In other examples, the sintered membrane has a thickness of about 124 μm. The membrane has a thickness of about 125 μm. In some examples, the sintered membrane has a thickness of about 126 μm. In some of these examples, the sintered membrane has a thickness of about 127 μm. In some instances, the sintered membrane has a thickness of about 128 μm. The conjunctiva has a thickness of about 129 μm. In one example, the sintered membrane has a thickness of about 130 μm. In some of these examples, the sintered membrane has a thickness of about 131 μm. In another example, the sintered membrane has a thickness of about 132 μm. In some instances, the sintered membrane has a thickness of about 133 μm. In some other examples, the sintered membrane has a thickness of about 135 μm. The conjunctiva has a thickness of about 136 μm. In some of these examples, the sintered membrane has a thickness of about In some instances, the sintered membrane has a thickness of about 138 μm. In some other examples, the sintered membrane has a thickness of about 139 μm. has a thickness of about 140 μm.

[0220] In some of these examples, the sintered membrane has a thickness of about 141 μm. In another example, the sintered membrane has a thickness of about 142 μm. In some instances, the sintered membrane has a thickness of about 143 μm. In some other examples, the sintered membrane has a thickness of about 145 μm. The conjunctiva has a thickness of about 146 μm. In some of these examples, the sintered membrane has a thickness of about In some instances, the sintered membrane has a thickness of about 148 μm. In some other examples, the sintered membrane has a thickness of about 149 μm. has a thickness of about 150 μm.

[0221] (iv. Nanocrystalline Films and Microcrystalline Granular Films) In some examples, provided herein are nanoparticles having a d of less than 10 nm. 50 Crystals with diameter In one embodiment, the film has grains of less than 9 nm. 50 Has grains with a diameter In other examples, the grains have a diameter of less than 8 nm. 50 In some instances, the result The grain size is less than 7 nm. 50 In some instances, the membrane has a diameter of less than 6 nm. 50 Has a diameter In another example, the film has grains with a d of less than 5 nm. 50 having grains with diameter In some instances, the film has a d of less than 4 nm. 50 It has grains with a diameter. The film has a d of less than 3 nm. 50 In one example, the film has grains having a diameter of: d less than 2nm 50 In another example, the film has grains with a diameter of less than 1 nm. 50 diameter The crystal grains have the following structure:

[0222] In some examples, provided herein are d less than 10 μm. 50 Crystals with diameter In one embodiment, the membrane has grains of less than 9 μm. 50 The grains have a diameter In other examples, the grains have a diameter of d less than 8 μm. 50 In some instances, the diameter , the grain size is less than 7 μm d 50 In some instances, the membrane has a diameter of less than 6 μm. 50 diameter In another example, the film has grains having a d of less than 5 μm. 50 Grains with diameter In some examples, the membrane has a d of less than 4 μm. 50 having grains with diameter In other examples, the membrane has a d of less than 3 μm. 50 It has grains with a diameter. In one example The membrane has a d of less than 2 μm. 50In another example, the film has grains having a diameter of 1 μm. d less than m 50 It has grains having a diameter.

[0223] As used herein, the microcrystal grains in the films described herein are between 10 nm and 10 μm d 50 In some examples, the crystallites in the films described herein have a diameter of 1 00nm~10μm d 50 It has a diameter.

[0224] (v. free-standing membrane) In some instances, the present disclosure provides a method for the preparation of a medicament for use in ... describes a free-standing thin film garnet-type electrolyte fabricated by

[0225] In some embodiments, disclosed herein is a method of The electrolyte is a free-standing thin film garnet-type electrolyte manufactured by Sigma-Aldrich.

[0226] In some embodiments, the free-standing membrane has a thickness of less than 50 μm. In some embodiments, the thickness of the membrane is less than 40 μm. In some other embodiments, the membrane is less than 20 μm thick. In an embodiment, the thickness of the membrane is less than 10 μm. The thickness is less than 5 μm.

[0227] In some embodiments, the membrane has a thickness of less than 45 μm. In some embodiments, the thickness of the membrane is less than 35 μm. In some embodiments, the thickness of the membrane is less than 25 μm. In some other embodiments, the membrane has a thickness of less than 15 μm. In some embodiments, the thickness of the membrane is less than 5 μm. It is less than 1 μm.

[0228] In some embodiments, the thickness of the membrane is from about 1 μm to about 50 μm. In some embodiments, the thickness of the film is about 10 μm to about 50 μm. In some other embodiments, the thickness of the membrane is about 20 μm to about 50 μm. In another embodiment, the thickness of the membrane is about 40 μm to about 50 μm. do.

[0229] In some embodiments, the thickness of the membrane is from about 1 μm to about 40 μm. In some embodiments, the thickness of the film is about 10 μm to about 40 μm. In some other embodiments, the thickness of the membrane is about 20 μm to about 40 μm. In another embodiment, the thickness of the membrane is about 20 μm to about 30 μm. do.

[0230] In some examples, described herein are thin, free-standing sintered garnets. a film, wherein the film thickness is less than 50 μm and greater than 10 nm, and the film is substantially flat. and the garnet optionally includes a metal or metal powder on at least one side of the film. It is bonded to the current collector (CC) membrane.

[0231] In some instances, the thin, free-standing sintered garnet film is less than 20 μm or less than 10 μm. In some instances, the thin, free-standing sintered garnet film has a thickness of less than 5 μm. In some instances, the thin, free-standing sintered garnet film has a surface roughness of less than 100 nm. In some instances, the thin, free-standing sintered garnet is The sintered glass film has a surface roughness of less than 2 μm. In some examples, the sintered glass film is thin and free-standing. The garnet film has a surface roughness of less than 1 μm. In one example, the garnet has a surface roughness of less than 0.1 μm. In one example, the garnet has a median grain size of 2.0 μm to 5.0 μm. The median grain size is

[0232] (vi. Films bound to substrates) In some of the membranes described herein, the membrane is made of a polymer, glass, or metal. In some of these examples, the membrane is attached to a substrate selected from the group consisting of: In some of these examples, the substrate to which the film is bonded is a current collector (CC). consists of nickel (Ni), copper (Cu), steel, stainless steel, combinations of these, and alloys of these. In some of these examples, the film comprises a metal selected from the group consisting of: In some other examples, the membrane is bonded to a metal current collector (CC) on one side of the membrane. In yet another example, the CC is bonded to two garnet films at the side. is disposed between and in contact with the

[0233] (vii. Bilayers and Trilayers) In some examples, described herein are two different lithium-loaded garnets. A triple layer including a metal foil or metal powder disposed between and in contact with a thin metal film. In some instances, the middle layer is a metal foil. In some other instances, The middle layer is a metal powder. In some instances, the metal is Ni. In other instances, In some instances, the metal is Al. In other instances, the metal is Fe. In some instances, the metal is The metal is steel or stainless steel. In some examples, the metal is Ni, Cu, Al, or Fe. In some examples, the triple layer has the structure shown in FIG. In some examples, the triple layer has the structure shown in FIG. In some examples, the triple layer has the structure shown in FIG. The overlay has the structure shown in Figure 44(E)(F).

[0234] In some examples, described herein are methods for contacting lithium-filled garnet thin films. In some instances, the bilayer comprises a metal foil or metal powder disposed in contact with the substrate. One layer of the bilayer is a metal foil. In another embodiment, one layer of the bilayer is a metal powder. In some examples, the metal is Ni. In other examples, the metal is Al. In other examples, the metal is Fe. In some examples, the metal is steel or stainless steel. In some examples, the metal is an alloy or combination of Ni, Cu, Al, or Fe. In some instances, the bilayer has the structure shown in Figure 44(C)(D). In some instances, the bilayer has the structure shown between the sintered plates in FIG. 20 or FIG. do.

[0235] In some of the bilayers and trilayers described herein, garnet has the following formula: LiALaBM'cM''DZrEOF, LiALaBM'CM''DTaEOF, LiALaBM'CM''DNbEOF (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13, and M' and M'' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or LiaLabZrcAldMe''eOf (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f ≤ 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb); LiALaBM'cM''DZrEOF (where Al 2 O 3 for garnet the molar ratio is 0.05 to 0.7); or LigLa3Zr2O12 - Al2O3 (where 5.5 < g < 8.5 and Al 2 O 3 for garnet the molar ratio is 0.05 to 1.0), and is characterized by one of them.

[0236] (viii. Multilayer) In some examples, described herein are numerous stacks or combinations of the aforementioned layers, bilayers, and / or trilayers. In some examples, two or more bilayers are stacked in a continuous combination. In some other examples, two or more trilayers are stacked in a continuous combination. In some examples, inserted between these continuous combination stacks are the cathode active material, anode active material, and / or current collector.

[0237] (ix. Film Dimensions) In some examples, the thin films described herein have a thickness of less than 50 μm. In some ​​In some other examples, the thin films described herein are less than 45 μm in thickness. In some embodiments, the thin films described herein are less than 40 μm thick. In some instances, the thin films described herein are less than 35 μm in thickness. The thin films described herein are less than 30 μm in thickness. The thin films described herein are less than 25 μm in thickness. In another embodiment, the thin films described herein are less than 20 μm thick. In some instances, the thin films described herein have a thickness of less than 15 μm. In some other examples, the thin films described herein have a thickness of less than 5 μm. In certain instances, the thin films described herein are less than 0.5 μm in thickness. In still other instances, the thin films described herein are less than 0.1 μm in thickness.

[0238] In some examples, provided herein are nanoparticles having a thickness of about 100 nm to about 100 μm. In some instances, the thickness is less than 50 μm. In other instances, the thickness is less than 40 μm. In some instances, the thickness is less than 30 μm. In other instances, the thickness is less than 20 μm. In some instances, the thickness is less than 10 μm. In other instances, the thickness is less than 5 μm. In some instances, the thickness is less than 1 μm. In yet another example, the thickness is 0.5 μm.

[0239] In some of these examples, the membrane is 1 mm in length. In some others, the membrane is 5 mm in length. The membrane is 10 mm in length. In another embodiment, the membrane is 15 mm in length. In one embodiment, the membrane is 25 mm in length. In another embodiment, the membrane is 30 mm in length. In some instances, the membrane is 35 mm in length. In some other instances, the membrane is In another embodiment, the membrane is 40 mm in length. In another embodiment, the membrane is 45 mm in length. In some instances, the membrane is 50 mm in length. In other instances, the membrane is 30 mm in length. In some instances, the membrane is 55 mm in length. In some other instances, the membrane is 60 mm in length. In yet another embodiment, the membrane is 65 mm in length. In some instances, the membrane is 70 mm in length. In other instances, the membrane is 75 mm in length. In some instances, the membrane is 80 mm in length. In some instances, the membrane is 85 mm in length. In another embodiment, the membrane is 90 mm in length. In yet another embodiment, the membrane is 95 mm in length. In one example, the membrane is 100 mm in length. In another example, the membrane is is 30mm.

[0240] In some instances, the membrane is 1 cm in length. In another embodiment, the membrane is 2 cm in length. In another embodiment, the membrane is 3 cm in length. In some instances, the membrane is 4 cm in length. In some instances, the membrane is 5 cm in length. In one embodiment, the membrane is 6 cm in length. In yet another embodiment, the membrane is 7 cm in length. In some other instances, the membrane is 8 cm in length. The membrane is 9 cm in length. In another example, the membrane is 10 cm in length. In some examples, the membrane is 11 cm in length. In some other examples, the membrane is 12 cm in length. In another embodiment, the membrane is 13 cm in length. In yet another embodiment, the membrane is In some instances, the membrane is 14 cm in length. In other instances, the membrane is 15 cm in length. In one embodiment, the membrane is 16 cm in length. In yet another embodiment, the membrane is 17 cm in length. In some other examples, the membrane is 18 cm in length. In some examples, the membrane is 19 cm in length. In other examples, the membrane is 20 cm in length. In some instances, the membrane is 21 cm in length. In some other instances, the membrane is 22 cm in length. In another embodiment, the membrane is 23 cm in length. In yet another embodiment, the membrane is In some instances, the membrane is 24 cm in length. In other instances, the membrane is 25 cm in length. The membrane is 26 cm in length. In yet another example, the membrane is 27 cm in length. In another embodiment, the membrane is 28 cm in length. In yet another embodiment, the membrane is In some embodiments, the membrane is 29 cm in length. In other embodiments, the membrane is 30 cm in length. The membrane is 31 cm in length. In some other examples, the membrane is 32 cm in length. In one example, the membrane is 33 cm in length. In yet another example, the membrane is 34 cm in length. In some instances, the membrane is 35 cm in length. In other instances, the membrane is In yet another example, the membrane is 37 cm in length. In one embodiment, the membrane is 38 cm in length. In yet another embodiment, the membrane is 39 cm in length. In other examples, the membrane is 40 cm in length. In some examples, the membrane is In some other examples, the membrane is 42 cm in length. In one embodiment, the membrane is 43 cm in length. In yet another embodiment, the membrane is 44 cm in length. In some instances, the membrane is 45 cm in length. In other instances, the membrane is In yet other examples, the membrane is 47 cm in length. In one embodiment, the membrane is 48 cm in length. In yet another embodiment, the membrane is 49 cm in length. In other instances, the membrane is 50 cm in length. In some instances, the membrane is In some other examples, the membrane is 52 cm in length. In one embodiment, the membrane is 53 cm in length. In yet another embodiment, the membrane is 54 cm in length. In some instances, the membrane is 55 cm in length. In other instances, the membrane is 56 cm in length. In still other examples, the membrane is 57 cm in length. The membrane is 58 cm in length. In yet another embodiment, the membrane is 59 cm in length. In some examples, the membrane is 60 cm in length. In some examples, the membrane is 61 cm in length. In some other examples, the membrane is 62 cm in length. In yet another example, the membrane is 63 cm in length. In another example, the membrane is 64 cm in length. In an example, the membrane is 65 cm in length. In another example, the membrane is 66 cm in length. In yet other instances, the membrane is 67 cm in length. In some other instances, the membrane is In yet another embodiment, the membrane is 69 cm in length. In some instances, the membrane is 70 cm in length. In some instances, the membrane is 71 cm in length. In some other instances, the membrane is 72 cm in length. In yet another embodiment, the membrane is 74 cm in length. In one embodiment, the membrane is 75 cm in length. In another embodiment, the membrane is 76 cm in length. In other instances, the membrane is 77 cm in length. In some other instances, the membrane is In yet another embodiment, the membrane is 78 cm in length. In yet another embodiment, the membrane is 79 cm in length. In some instances, the membrane is 80 cm in length. In some instances, the membrane is 81 cm in length. In some other examples, the membrane is 82 cm in length. In other examples, the membrane is 83 In yet other examples, the membrane is 84 cm in length. The membrane is 85 cm in length. In another example, the membrane is 86 cm in length. In some instances, the membrane is 87 cm in length. In some other instances, the membrane is 88 cm in length. In yet another embodiment, the membrane is 89 cm in length. In some instances, the membrane is 90 cm in length. In some instances, the membrane is 91 cm in length. In another embodiment, the membrane is 92 cm in length. In another embodiment, the membrane is 93 cm in length. In yet another embodiment, the membrane is 94 cm in length. In some embodiments, the membrane is In another embodiment, the membrane is 96 cm in length. In some other examples, the membrane is 97 cm in length. In other examples, the membrane is 98 cm in length. In yet another embodiment, the membrane is 99 cm in length. In some instances, the membrane is 101 cm in length. In one example, the membrane is 102 cm long. In another example, the membrane is 103 cm long. In yet other examples, the membrane is 104 cm in length. In some examples, the membrane is In another example, the membrane is 106 cm in length. In some instances, the membrane is 107 cm in length. In some other instances, the membrane is 108 cm in length. In yet another embodiment, the membrane is 109 cm in length. In some instances, the membrane is 110 cm in length. In some instances, the membrane is 111 cm in length. In another embodiment, the membrane is 112 cm long. In another embodiment, the membrane is 113 cm long. In yet other examples, the membrane is 114 cm in length. The membrane is 115 cm in length. In another example, the membrane is 116 cm in length. In some examples, the membrane is 117 cm in length. In some other examples, the membrane is 1 In yet another embodiment, the membrane is 119 cm in length. The membrane is 120 cm long.

[0241] In some instances, garnet-based films can be used as monoliths useful in lithium secondary battery cells. In some of these cells, the garnet-based film form factor is , about 10cm 2In one cell, the membrane has an upper surface area of ​​about 100 cm 2 The upper surface area of The shape element of the garnet-based film having the above structure.

[0242] In some examples, the films described herein have a Young's modulus of about 130-150 GPa. In some other examples, the films described herein have a Vickers hardness of about 5-7 GPa. It has a quality.

[0243] In some instances, the membranes described herein have a porosity of less than 20%. In some examples, the membranes described herein have a porosity of less than 10%. In some embodiments, the membranes described herein have a porosity of less than 5%. The membranes described herein have a porosity of less than 3%.

[0244] (x. Composite materials) For Li secondary battery applications, the energy density depends on the electrolyte, catholyte, and alumina that may be present. The amount of electrolyte, catholyte, or anolyte material used is inversely proportional to the amount of anolyte. As a given battery capacity is used, more positive electrode active material (e.g., FeF3, CoF2 , NiF2, CoF2) and more anode materials (e.g., Li-metal) can be incorporated into the same capacity. This can increase the energy density of the battery, e.g., the energy per unit capacity. Thus, in some instances, the diameter may be less than 500 μm but greater than 1 nm. or less than 450 μm but more than 1 nm, or less than 400 μm but more than 1 nm, or is less than 350 μm but more than 1 nm, or less than 300 μm but more than 1 nm, or 250 Less than 1 nm but more than 1 nm, or less than 200 μm but more than 1 nm, or less than 150 μm Less than 1 nm but more than 1 nm, or less than 100 μm but more than 1 nm, or less than 50 μm but more than 1 nm, or less than 45 μm but more than 1 nm, or less than 40 μm but more than 1 nm m, or less than 30 μm but more than 1 nm, or less than 35 μm but more than 1 nm or less than 25 μm but more than 1 nm, or less than 20 μm but more than 1 nm, or Less than 15 μm but more than 1 nm, or less than 10 μm but more than 1 nm, or less than 9 μm but more than 1 nm, or less than 8 μm but more than 1 nm, or less than 7 μm but More than 1 nm, or less than 6 μm but more than 1 nm, or less than 5 μm but more than 1 nm or less than 4 μm but more than 1 nm, or less than 3 μm but more than 1 nm, or Less than μm but more than 1 nm, or less than 1 μm but more than 1 nm, or less than 90 nm but more than 1 nm, or less than 85 nm but more than 1 nm, or less than 80 nm but more than 1 nm More than 75 nmμm, or less than 75 nmμm but more than 1 nm, or less than 70 nm but more than 1 nm or less than 60 nm but more than 1 nm, or less than 55 nm but more than 1 nm, or less than 50 Less than 1 nm but more than 1 nm, or less than 45 nm but more than 1 nm, or less than 40 nm but more than 1 nm, or less than 35 nm but more than 1 nm, or less than 30 nm but more than 1 nm or less than 25 nmμm but more than 1 nm, or less than 20 nm but more than 1 nm or less than 15 nm but more than 1 nm, or less than 10 nm but more than 1 nm, or 5 nm m but more than 1 nm, or less than 4 nm but more than 1 nm, or less than 3 nm The present invention relates to a method for producing a film thickness of less than 2 nm but more than 1 nm, or less than 2 nm but more than 1 nm. It is advantageous to use the method described.

[0245] In certain instances, the garnet materials described herein are combined with a polymer. In these examples, the polymers include polyethylene oxide (PEO), polypropylene Polypropylene oxide (PPO), PEO-PPO block copolymer, styrene-butadiene, polystyrene (PS ), acrylates, diacrylates, methyl methacrylate, silicones, acrylamides , t-butylacrylamide, styrenics, t-alpha methylstyrene, acrylo These include, but are not limited to, nitrile, and vinyl acetate.

[0246] The present invention relates to a method for preparing a binder, the method comprising the steps of: In the examples of the specification, the binder is polypropylene (PP), polyvinyl butyral (PVB) , polyvinylpyrrolidone (PVP), atactic polypropylene (aPP), isotactic tactive) Polypropylene Ethylene Propylene Rubber (EPR), Ethylene Pentene Copolymer (EP C), Polyisobutylene (PIB), ZEON (trademark), Styrene butadiene rubber (SBR), Polyolefin Polyethylene-co-poly-1-octene (PE-co-PO); PE-co-poly(methylenecyclopentane )(PE-co-PMCP); stereoblock polypropylene, polypropylene polymethylpentene co The polymer may be selected from the group consisting of: polymers, and silicones.

[0247] (II. Lithium secondary batteries) In some examples, the disclosure herein provides a method for producing the lithium-loaded garnet described herein. The present invention describes a battery having a catholyte, electrolyte, and / or anolyte, the battery being composed of a There are.

[0248] (a. Battery structure) In some examples, the batteries described herein may include a current collector substrate coated on both sides. In these examples, the garnet electrolyte contains a positive electrode (e.g., cathode) active material. It may also be applied to or within the cathode active material.

[0249] In some instances, the disclosure herein provides a method for producing a compound according to the invention, comprising the steps of: The present application describes a composite electrochemical device comprising: an active electrode material, lithium The group consisting of: ruthenium-filled garnet electrolyte or catholyte; conductive additives; and combinations thereof. In some examples, the device includes at least one layer including a material selected from the group consisting of The material also includes at least one layer that includes a garnet-type electrolyte.

[0250] In another embodiment, the present disclosure provides herein an anode and an anode current collector. at least one layer comprising a garnet solid electrolyte (SSE); at least one layer comprising a garnet solid electrolyte (SSE); at least one layer comprising a porous garnet in contact with the SSE; The batts may optionally be made of carbon, lithium conducting polymers, active cathode materials, and combinations thereof. and the porous garnet is permeated with at least one member selected from the group consisting of: comprising at least one layer comprising an aluminum cathode current collector in contact with a substrate, wherein the porous garnet layer is at least 70% porous by volume; the garnet is Li A La B M ' c M'' D Zr E O F 、Li A La B M' C M'' D Ta E O F 、Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4 、0 ≦ C ≦ 2, 0 ≦ D ≦ 2; 0 ≦ E < 2, 10 < F < 14, and M' and M'' are each, in each case independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≦ 2.5; 0 ≦ d < 2; 0 ≦ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb) is a selected material; and the active electrode material is NCA (lithium nickel cobalt aluminum oxide), LMNO (lithium manganese nickel oxide), NMC (lithium nickel manganese cobalt oxide), LCO (lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiF x 、where x is 0 to 2.5), copper fluoride (CuF y 、where y is 0 to 2.5), or FeFz ( where z is selected from the group consisting of 0 to 3.5. In some examples, 10 <F<13である。いくつかの In the example, 0 <c≦2である。

[0251] (b) A garnet catholyte, an electrolyte, and a battery composition suitable for use with the catholyte minutes) Suitable current collectors for use with the garnet materials described herein include gold. Metal foils, metal sheets, metal wires, and metal powders, where the metal is aluminum. Aluminum, copper, gold, nickel, cobalt, steel, stainless steel, lithium metal, and alloys thereof , a mixture, or a combination. Provided herein is a lithium doped alumina as described herein. Electrochemical devices having electrolytes composed of filled garnets. In accordance with the present invention, there is provided a method for producing alumina-doped quartz crystals, as described herein. The present invention relates to an electrochemical device having a catholyte composed of lithium-loaded garnet.

[0252] In some embodiments disclosed herein, the electrode comprises a conductive additive that is carbon. In one embodiment, the carbon is selected from the group consisting of Ketjen black, VGCF, acetylene black, graphite, graphene, nanotubes, nanofibers, and combinations thereof In one embodiment, the carbon is a member selected from the group consisting of ketjen. In some other embodiments, the carbon is VGCF. In another embodiment, the carbon is graphite. In some embodiments, the carbon is graphene. In some embodiments, the carbon is a nanotube. In other embodiments, the carbon is a nanofiber.

[0253] c. Cathode Materials Suitable for Use with the Garnet Materials Described Herein The garnet materials described herein are compatible with a variety of cathode or positive electrode active materials. In particular, garnets are suitable for use in conversion chemistry cathode activity. Materials, such as, but not limited to, electrochemical conversion NANOSTRUCTURED MATERIALS FOR ELECTROCHEMICAL CONVERSION REA No. 13 / 922,214, filed May 8, 2014, entitled "Compounds of a Polymeric Material"; PROTECTIVE COATINGS FOR CONVERSION MATERI No. 14 / 272,518, filed on July 23, 2014, entitled "AL CATHODES"; In addition, hybrid electrodes (H) having both intercalation and conversion materials YBRID ELECTRODES WITH BOTH INTERCALATION AND CONVERSION MATERIALS) Patent application Ser. No. 62 / 027,908; and also Ser. No. 2006 / 023 / 014, filed Nov. 26, 2013, for use in energy storage. Iron Oxyfluoride Electrodes for Energy Storage Provisional Patent Application No. 14 / 090,990; also filed on Oct. 25, 2013, entitled "Metals for Self-Forming Batteries" METAL FLUORIDE COMPOSITIONS FOR SELF-FORMED BATTERIES The active materials described in US Patent Application No. 14 / 063,966 are chemically compatible with the active materials described in US Patent Application No. 14 / 063,966. The subject matter of these patent applications is useful as sols and electrolytes. No. 6,399,433, which is incorporated herein by reference in its entirety.

[0254] The garnet materials described herein are compatible with other catholyte and electrolyte materials, e.g. Li, filed on May 15, 2014, is not yet determined. A MP B S C (M=Si, Ge, and / or Sn) SOLID STATE CATHOLYTE OR ELECTROLYTE FOR BATT ERY USING Li A MP B S C (M = Si, Ge, and / or Sn)) The present invention is also suitable for use with the catholyte and electrolyte materials described in US Pat. No. 6,399,363.

[0255] Active electrodes suitable for use with the compositions, devices, and methods described herein The material may be, but is not limited to, NCA (lithium nickel cobalt aluminum oxide) Lithium Nickel Manganese Cobalt Oxide (NMC), Lithium Manganese Nickel Oxide (LMNO) Lithium cobalt oxide (LiCoO2), LCO (Lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiFx, where x is 0 to 2.5), copper fluoride (CuF y, where y is 0 to 2.5), or FeF z (here and z is selected from 0 to 3.5. In one embodiment, the active electrode material is In one embodiment, the active cathode electrode material is NCA (LiCu). In certain other embodiments, the active material is a tungsten nickel cobalt aluminum oxide. The active cathode electrode material is LMNO (lithium manganese nickel oxide). In embodiments, the active cathode electrode material is LCO (lithium cobalt oxide, i.e., Li In yet another embodiment, the active cathode electrode material is NMC. In certain other embodiments, the active cathode electrode material is nickel fluoride (NiF x , where , x is 0 to 2.5. In some other embodiments, the active cathode electrode material is copper fluoride (CuF y In another embodiment, the The active cathode electrode material is FeF z (wherein z is selected from 0 to 3.5).

[0256] III. METHODS OF MAKING THE MATERIALS DETAILED DESCRIPTION (a. Thin-film lithium conductive powder material derived from deposition flux) In some examples, described herein are ceramic electrolyte materials (e.g., A process for making a battery component including lithium-loaded garnet powder or film, comprising the steps of: The ceramic is then heated on or around the substrate using one or more flux materials having a melting point lower than The process involves mixing, dissolving, and / or densifying the mixture.

[0257] In some instances, the ceramic electrolyte powder material, or components thereof, may be prepared by subjecting the ceramic electrolyte powder material to two or more flash The fluxed powder material is mixed with the fluxed powder material at a temperature below 400°C to form the fluxed powder material. The fluxed powder material is compacted and reheated at temperatures below 400°C to produce a high density lithium conductor. A conductive material is formed.

[0258] The deposition methods described herein are directed to deposition materials such as, but not limited to, garnet, Suitable for lithium filled garnet, perovskite, NASICON and LISICON structures.

[0259] In some examples, the deposition method includes depositing a lithium conductive ceramic powder material in a specified amount. In one example, the powder has an average particle size of about 100 nm to 10 μm. In some examples, the powder is characterized by, or is ground to, an average particle size of: The average particle size is between 800 nm and 2 μm. In some of these examples, the flux material is provided in a second defined amount and density. In one example, the second provided flux The material is less than 51% (w / w) of the first powder material. This flux material is typically heated to about 500° C. A lithium-containing material that melts at ~800°C. Additional flux material is provided in the reaction mixture. In some examples, various combinations of powder and flux materials may be provided. In some of these examples, the eutectic mixture is In some further examples, the eutectic mixture has a melting point of about 100-50 The mixture is heated to a temperature of 0° C. In some instances, the heated mixture is mixed. In examples, the mixture is then heated and formed into, but not limited to, a sheet, thick film (greater than 100 μm thick), , thin film (thickness less than 100μm), roll, sphere, disk, sheet, pellet, and cylinder After a reaction period and / or further heating, the powder and flux materials are Optionally, the flux is cooled. In some examples, the flux is dissolved in a solvent, such as, but not limited to, The product formed therein is dissolved in water, acetone, ethanol, or a combination thereof. In some instances, further heating is performed to a temperature of less than 500°C. This method, and variations thereof, produce high density lithium conductive ceramic powders. This often results in a density that is 20% higher than the starting density of the reactants and / or flux. In some instances, the powder and flux materials include formed garnet, e.g. For example, Li7La3Zr2O 12 , and oxides such as LiOH, La2O3, and ZrO2. In one embodiment, the garnet powder is a garnet precursor, such as, but not limited to, Not limited to, but includes LiOH, L2CO3, La2O3, ZrO2, Nb2O5, Ta2O5, Al nitrate, Al nitrate hydrate, or These combinations are formed by mixing.

[0260] In some examples, the garnet materials described herein can be prepared by the addition of a garnet precursor For example, but not limited to, LiOH, La2O3, ZrO2, Nb2O5, Ta2O5, Al nitrate, or any of these. The mixture is then heated to 600° C. , 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150 ℃, 1200 ℃, 1250 ℃, 1300 ℃, 1350 ℃, 1400 ℃, or 1450 ℃. In the example, the mixture is heated at 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., or 1100° C. In some examples, the mixture is calcined at 800° C. In some instances, the mixture is calcined at 850° C. In some instances, the mixture is calcined at 900° C. In some examples, the mixture is calcined at 950° C. In some examples, the mixture is calcined at 1 In some examples, the mixture is calcined at 1000° C. In some examples, the mixture is calcined at 1050° C. In some of these examples, the mixture is calcined at 1100° C. The mixture is calcined for 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 hours. The mixture is calcined for 4, 5, 6, 7, or 8 hours. In some examples, the mixture is calcined for 4 hours. In some examples, the mixture is calcined for 5 hours. The mixture is calcined for 6 hours. In some examples, the mixture is calcined for 7 hours. In this case, the calcination temperature is achieved by a heat ramp rate of about 1 C / min or about 5 C / min or about 10 C / min. In some of these examples, the calcined mixture is then crushed to produce a mixture agglomerate. In some of these examples, the calcined mixture is then crushed and flattened. In one example, the milled calcined mixture is then heated at 600° C. for 6 50℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, Sintering at temperatures of 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or 1450°C. Some examples In this case, sintering was performed at 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, and 1350°C. , 1400° C., or 1450° C. In some examples, sintering is performed at temperatures of 1000° C., 1200° C., 1400° C., or 1450° C. In these examples, sintering is performed at a temperature of 1, 2, 3, 4, 5, 6, 7 , 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, It lasts for 28, 29 or 30 minutes.

[0261] In some instances, the flux may be an inorganic salt, such as lithium, sodium, potassium, or the like. Some examples include LiF, LiCl, LiBr, and / or LiI. In the present invention, the flux includes inorganic oxides such as LiOH and Li2CO3. Also include alkali metal hydroxides, chlorides, nitrates, sulfates, and combinations thereof. Specific combinations that are useful are LiOH, LiCl, LiBr, LiI, LiNO3, LiSO4, Li2O-SiO2, Li2O -B2O3, Li2O-PbO, Li2O-Bi2O3, NaOH, NaCl, NaNO3, NaSO4, NaBr, Na2CO3, KOH, KCl, K A mixture of any one or more members selected from the group consisting of NO3, KSO4, KBr, and K2CO3 include.

[0262] The flux comprises a eutectic mixture of materials, where the eutectic mixture is made up of the constituents of the mixture. For example, a mixture of 0.3 LiOH and 0.7 NaOH has a melting point lower than that of either The mixture melts at around 250° C., which is lower than the melting point of either LiOH or NaOH.

[0263] In some examples, the powder, flux, and reaction mixture are applied to a current collector, a positive electrode, a negative electrode, , or deposited in the electrolyte.

[0264] In some instances, the powders synthesized herein may be dissolved in a flux component. The powder is then mixed with the flux components. The mixture is cast onto a plate to form a film having a thickness of about 10 nm to about 250 μm. The casting onto the substrate can be by slot casting, doctor blade casting, or by casting the substrate through a flame. This is achieved by dip coating into the glass.

[0265] In some other instances, the compositions described herein may be combined to produce a slurry of these components. The resulting powder is mixed with the flux components and also mixed with a liquid or solvent. The mixture is cast onto a substrate to form a film having a thickness of about 10 nm to about 250 μm. In the method, the casting onto the substrate is performed by slot casting, doctor blade casting, or by casting the substrate. This is achieved by dip-coating the flux with the slurry. The slurry is then dried to The solvent is removed, and the flux components and powders are optionally melted and mixed. Heating is at about 200° C., or about 250° C., or about 300° C., or about 350° C., at 1° C. / min. A temperature of about 350° C., or about 400° C., or about 450° C., or about 500° C. is achieved. In order to completely dissolve the powder in the flux, more In other instances, not all of the powder in the flux is dissolved. To avoid this, a more synthetic powder is used than a flux.

[0266] In some examples, the positive electrode active material is mixed with garnet powder and also with the flux components. The mixture is then applied to one, two or more of the current collectors. The flux can be treated as described herein and optionally deposited on the side. When the garnet material is removed, the intimate mixture of garnet and active material is in direct contact with the current collector. Remains at.

[0267] In any of these examples, the substrate, e.g., the current collector, may be a garnet, a garnet precursor, By dip-applying a flux having a precursor, an active material, or a combination thereof, The substrate can be coated with a garnet material, optionally including a positive electrode active material. In any of the examples, the substrate, e.g., the current collector, is provided with a garnet, a garnet precursor, an active A flux having a conductive material, a conductive material, or a combination thereof is cast on the substrate. Garnet material, optionally including active material, can be applied. The casting can be doctor blade casting. In these examples, the casting is performed by a slot In these examples, the casting can be dip coating. .

[0268] In some examples, the methods herein include providing a lithium conductive ceramic powder material in one or more providing a eutectic mixture of the above flux materials; heating said mixture at a temperature of about 400°C to about 800°C. Optionally, casting the flux material; and forming a high density lithium conductive gas. In some instances, the formed material includes forming a net material. In some examples, the first flux is at least 20% denser than the precursor. H, LiCl, LiBr, LiNO3, LiSO4, or combinations thereof; The second flux is NaOH, NaCl, NaNO3, NaSO3, NaSO4, NaBr, Na2CO3, or a combination thereof. Two flux materials are used, one or more of which are selected from the following: In some examples, the powder material is a lithium-filled garnet. The powder material optionally comprises a perovskite material. In some examples, the powder material comprises: In some instances, the third filler may be a NASICON, LISICON, or tungsten / bronze material. A lux is provided in this manner, selected from KOH, KCl, KNO3, KSO4, KBr, and / or K2CO3. It is one or more materials that can be used.

[0269] Further details, examples and embodiments of these methods for making garnet materials can be found in, for example, , the contents of which are incorporated herein by reference in their entirety for all purposes, 2013 A method and system for forming garnet materials using a sintering process, filed on October 7, Titled "METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTERING PROCESS" No. 61 / 887,451, filed on Dec. 13, 2003.

[0270] In some instances, the precursors are optionally ground and mixed with the flux, as shown in FIG. The precursors are mixed together (step a) and heated to dissolve the precursors in the flux (step b). The flux containing the material is cast (step c) and calcined (step d) to react the precursor material and form a more The resulting particles are made larger and more crystalline (step e), which are then densified by the flux. In some instances, the flux is removed (step f).

[0271] (b. Solutions and Slurries) In some examples, the methods herein involve the steps of: casting or depositing a solution and a spray onto a substrate; In some instances, the garnet precursor may be a powder as described herein. In some instances, these precursors are formulated into a slurry. In some instances, these ground precursors are formulated into a slurry. After milling, in some instances, the precursor is mixed with a coating formulation, such as a binder and a solvent. These slurries and formulations, solvent, binder, dispersant, and a surfactant. In some instances, the binder is polyvinyl butyral (PVB). The solvent is toluene and / or ethanol and / or diacetone alcohol. In some instances, PVB is both a binder and a dispersant. The binders include PVB, PVP, ethyl cellulose, cellulose, PVA, and PVDF. In some examples, the dispersing agent may be a surfactant, a fish oil, a fluorinated surfactant, or a mixture thereof. Activators include Triton, PVB, and PVP. In some slurries, 10% to 60% by weight The slurry is a solid precursor. The binder and dispersant each have some In this slurry, the slurry may comprise 50% w / w of the slurry, with the solvent making up the remaining weight percentage. Includes content.

[0272] In some examples disclosed herein, the slurry contains a conductive additive that is carbon. In one embodiment, the carbon is Ketjen black, VGCF, acetylene black. , graphite, graphene, nanotubes, nanofibers, etc., and combinations thereof In one embodiment, the carbon is a member selected from the group consisting of Ketchenbuffer. In some other embodiments, the carbon is VGCF. In one embodiment, the carbon is acetylene black. In another embodiment, the carbon is graphite. In some embodiments, the carbon is graphene. The carbon is a nanotube. In another embodiment, the carbon is a nanofiber.

[0273] In some examples, the solvent is toluene, ethanol, toluene:ethanol, or In some embodiments disclosed herein, the binder may be selected from any of the above combinations. In some embodiments disclosed herein, the polymer is polyvinyl butyral (PVB). The binder is polypropylene carbonate. In this case, the binder is polymethyl methacrylate.

[0274] In some examples, the solvent is toluene, ethanol, toluene:ethanol, or In some instances, the binder is polyvinyl butyral (PVB In another embodiment, the binder is polypropylene carbonate. In the example, the binder is polymethyl methacrylate.

[0275] In some embodiments disclosed herein, removing the solvent comprises evaporating the solvent. In some of these embodiments, removing the solvent includes evaporating the solvent. In some embodiments, the removing step comprises heating the film. In yet another embodiment, the removing includes using a vacuum to In yet another embodiment, the removing step comprises heating the film to remove the solvent. , involving driving off the solvent using a vacuum.

[0276] (c. Catholyte) As shown in FIG. 25, one method of making an embodiment of the invention disclosed herein is to depositing a dense solid separator electrolyte for the node and optionally sintering the electrolyte. In some embodiments, the method includes depositing a porous garnet catholyte; and sintering the catholyte to achieve a porosity of greater than 70%. The method comprises the steps of: forming a film by a method selected from chemical vapor deposition (CVD), pyrolysis, or related techniques; This includes filling the porous catholyte with less than 10% by volume of carbon. In one embodiment, the method includes providing a porous catholyte with an ion-conducting material, such as a liquid, gel, or polymer. In some embodiments, the method further comprises filling the conductive flowable material with an active material. In some embodiments, the method includes loading the active material with greater than 40% by volume. In some embodiments, the method further comprises laminating or evaporating a cathode current collector. This also includes putting them on.

[0277] In some embodiments, disclosed herein are methods for producing integrated electrochemical devices. The method of manufacturing an anode layer includes the steps of: providing an anode layer including an anode current collector; providing a garnet-type solid electrolyte (SSE) layer in contact with at least one side of the node layer; optionally, sintering the SSE; providing a porous garnet layer in contact with the SSE layer; and optionally sintering the porous garnet layer; optionally, adding carbon, lithium, or the like to the porous garnet layer. A small amount of a conductive polymer selected from the group consisting of an active cathode material, a conductive polymer having a conductivity of about 100 to about 1000 nm, a conductive polymer having a conductivity of ... and contacting the porous garnet layer with at least one cathode assembly. In some examples, the method includes, in any order, providing a dielectric layer. The steps are performed sequentially in the order in which they are listed.

[0278] In some examples, the methods described herein include a method for producing a garnet-type solid electrolyte (SSE) on two independent sides of the anode current collector layer.

[0279] In some examples, sintering includes thermal sintering or electric field assisted sintering (FAST). Here, thermal sintering refers to sintering garnet at a temperature in the range of about 800°C to about 1200°C for about 1 to about 600 minutes. and FAST sintering the garnet in the range of about 600°C to about 800°C. This involves heating and applying a DC or AC electric field to the garnet.

[0280] In some instances, infiltrating the porous garnet layer with carbon may be accomplished by chemical vapor deposition (CVD). This includes using chemical vapor deposition (CVD) or pyrolysis.

[0281] In some instances, infiltrating the porous garnet layer with the active material may be a vapor / liquid This includes using plasma deposition or electrophoretic deposition.

[0282] In some instances, providing a cathode current collector in contact with the porous garnet layer. The current collector is laminated, electroplated, or vapor-deposited onto the porous garnet layer. include.

[0283] In some instances, the porous garnet layer, after it is sintered, is at least about 1000 nm in volume. It is also 70% porous.

[0284] In some instances, the porous garnet layer is characterized by a Li conductivity of 1e-3 S / cm or greater at 60° C. In some examples, the lithium conductive polymer has a Li conductivity of 1e-4 S / cm or more at 60°C. The materials described herein are characterized by a Li conductivity of 1e-4 S / cm or greater at 60° C. In some examples, the conductivity is a measure of bulk conductivity. In this case, the conductivity is not affected by the porosity of the material, although the conduction occurs within the material. It is measured as follows.

[0285] In some examples, the porous garnet layer has an average pore diameter size of about 5 nm to about 1 μm. It has a hole through which

[0286] In some instances, the polymer is stable at voltages greater than about 3.8V.

[0287] In some examples, the porous garnet layer has a melting point of about σ i >1e-3S / cm conductivity It is a sign.

[0288] In some examples, the porous garnet layer contains more than 40% by volume of active cathode material. In some instances, the porous garnet layer is infiltrated with more than 55% by volume of The active cathode material is infiltrated.

[0289] In some instances, the garnet is stable at a voltage between about 1.3V and about 4.5V.

[0290] In some examples, the garnet is Li A La B M' c M'' D Zr E O F , Li A La B M' C M'' D Ta E O F , Li A La B M' C M'' D Nb E O F (where 4 <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E<2、10< F<13, and M' and M'' are each, independently in each occurrence, Al, Mo, W, Nb, Sb, Ca, Ba, Sr , Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 <a<7 .7;2 <b<4; 0<c≦2.5; 0≦d<2; 0≦e<2、10<f<13であり、Me''は、Nb、Ta、V、W , Mo, or Sb).

[0291] In some instances, the active electrode material is NCA (lithium nickel cobalt aluminum). Lithium manganese nickel oxide), LMNO (lithium manganese nickel oxide), LCO (lithium cobalt oxide, LiCoO2), NMC, nickel fluoride (NiF x , where x is 0 to 2.5), copper fluoride (Cu F y , where y is 0 to 2.5), or FeF z (where z is selected from 0 to 3.5) It is a cathode material used in

[0292] In some examples, disclosed herein are methods for producing a medicament for the treatment of a cancer, comprising the steps of: The electrochemical device is manufactured using the above process.

[0293] As shown in FIG. 27 and FIG. 29, the method herein includes, prior to the sintering process, dissolving electrolyte particles in a sintered state. The present study describes a process for fabricating composite electrodes for solid-state batteries that consist of active electrode materials interspersed with nanoparticles. In some embodiments, the layer contains a conductive additive (e.g., carbon). It is also possible.

[0294] As shown in FIG. 31, the electrolyte and electrode materials have improved interfacial contact after sintering. In some embodiments, the free-standing bilayer or trilayer described herein comprises The Li-garnet interface in these examples is In addition, they have a low area specific resistance (ASR). In some examples, the ASR is less than 5 ohm cm at 80°C. 2 Not yet In some examples, the ASR is less than 100 ohm cm at 80°C. 2 Less than some In the example, the ASR is approximately 1 ohm cm at 80°C. 2 In some examples, the ASR is 6 ohms cm 2 is less than.

[0295] In some embodiments, Li is added to the sintered garnet film (free-standing bilayer or trilayer). It is deposited or laminated and has a low ASR. In some examples, the ASR is 5 ohm cm at 80° C. 2 In some examples, the ASR is less than 100 ohm cm at 80° C. 2 Less than. Some In this example, the ASR is approximately 1 ohm cm at 80°C. 2 In some examples, the ASR is 6 ohms cm 2 is less than.

[0296] As shown in Figs. 15, 16, 17, 20, 21, and 28, a setter plate is used. In some instances, AC current may be applied, and in some other instances, DC current. A power supply can be used to sinter the particles.

[0297] As shown in FIG. 4, an electrochemical device is fabricated by the sintering method described herein. In FIG. 4, for example, electrolyte powder, catholyte particles (e.g., garnet tocasolite), and active electrode particles (e.g., cathode active particles) are layered and mixed, It can then be sintered according to the novel methods described herein.

[0298] In some examples, the membranes described herein are prepared using an organic binder-solvent system (e.g., Powdered ceramic component(s) (polyvinyl butyral in toluene:ethanol) For example, electrolyte: lithium-filled garnet, lithium lanthanum, zirconium oxide; electrodes: By producing a slurry of lithium-nickel-manganese-cobalt oxide, In some examples of composite electrodes, In addition to the electrolyte and active electrode materials, conductive additives such as carbon black are added to This can also increase the electrical conductivity of the final product. It can be cast as a thin layer of any thickness and the solvent is allowed to evaporate, leaving behind a flexible film. The membrane is easy to handle and can be easily sintered at moderate temperatures (80°C) and low pressures (<1000 psi). For example, Li conductive garnet can be stacked on top of other such layers by A green composite thin film of a lithium electrolyte and a high voltage cathode material (NMC) is shown, for example, in FIG. There are.

[0299] Some of the example methods described herein involve thermal sintering.

[0300] In some instances, after a binder burnout step to remove the binder (e.g., PVB) 2. Heat the composite electrode, for example the composite electrode shown in FIG. 27, to a high temperature (for example, 800 to 1200° C.); Holding for a period of time (1-600 min) induces sintering of the particles, forming a much higher density matrix. In some of these examples, the bonds between the individual components can be formed. The grains fuse together, significantly increasing their contact area, as shown, for example, in FIG. In some instances it may be advantageous to use finely divided powders, particularly for the electrolyte components. This is because it increases the sintering reaction rate and allows densification at lower temperatures. To maintain the flatness of the thin film under this process, the film is covered with a porous zirconia. The membrane can be sandwiched between an inert setter plate, such as a ferroelectric. This helps to keep the membrane in a layered form. Not only does it retain the binder, it also provides a route for the release of binder decomposition products. The microstructure of the sintered electrode composite material is shown, for example, in FIGS.

[0301] Some of the example methods described herein involve electric field assisted sintering (i.e., FAST) sintering. This includes concluding.

[0302] One disadvantage of the traditional sintering process is that it operates at high temperatures where several detrimental phenomena can occur. For example, lithium is a highly volatile species and requires long dwell times. , evaporates from the solid electrolyte material, thereby reducing its ionic conductivity and creating a highly resistive surface. This can induce plane depletion or even cause material decomposition. In the case of composite layers, once the grains Once fused, the electrolyte and electrode components continue to interact and they The components can interdiffuse to such an extent that their electrochemical properties are lost, i.e., the electrolyte loses its ionic The electrode may lose its ionic conductivity or its ability to store active ions (e.g., lithium). Therefore, to overcome all these problems, the sintering process can be In some instances, this can be achieved using electric field assisted sintering. This is achieved through

[0303] 16, 17, 18, 19, 20, 21, and 22 show the conventional sintering process disclosed herein. Lower temperatures (e.g., 600 to 800°C or less) than the process (up to 1100°C) or (400 to 1000°C) 1 shows a schematic diagram of the setup for FAST sintering of an electrolyte membrane at 1000 K (1000 sintering temperature). The membrane is then bonded to two conductive metal plates. Place the plate between the plates and heat in an oven at a moderate temperature (800C) where lithium evaporation is not noticeable. An electric field is then applied to the sample to induce FAST sintering. The electric field can be a DC field or In some instances, the ionic species may not separate significantly under the stimulus. AC electric fields are advantageous because the frequency can be chosen high enough to avoid separation. The power supply to the sample must be controlled to avoid excessive Joule heating of the material. In some instances, this is initially operated in a constant voltage amplitude mode, where sintering begins and the sample This can be achieved by switching to a constant current when the impedance of the Sintering the electrolyte membrane to full density in a much shorter time and at a lower temperature than conventional processes. It can be sintered at .

[0304] In some instances, FAST sintering also overcomes the problem of interdiffusion in composite electrode layers. FIG. 29 shows a schematic diagram of the layout of a complete solid-state battery configuration under FAST sintering. Before sintering, the electrolyte The advantage of the FAST sintering process is that the voltage drop (i.e. the electric field) is preferentially compared to high impedance areas that are always poorly contacted (i.e. non-calcined areas) Therefore, when two types of particles are sintered together, the contact between the constituent particles is The contact improves and the resistance drops. As a result, the electric field distribution moves to the adjacent unsintered particles. Thus, the driving force for sintering is transferred from the already fused grains to the additional phases. Interdiffusion is limited.

[0305] These sintering methods have the advantages of fast sintering times, limited interdiffusion between the components in the composite electrode, and Additionally, the ability to prepare complete solid-state battery configurations allows for solid-state batteries without liquid electrolytes and and its components.

[0306] d. Doped Compositions In some examples, provided herein are aluminum doped lithium A method for making an aluminum-filled garnet comprising providing garnet precursors in a predetermined combination. In some examples, the method includes incubating the combination for 5 to 10 hours. In another example, the method further comprises grinding the combination in a vessel at about 500° C. The method further includes calcining the mixture at about 1,200° C. for about 4 to about 10 hours to form garnet. In an example, the method further comprises: 50 Grind until particle size is 200-400 nm In another example, the method further comprises: Some of these examples further include mixing the binder to form a slurry. In some cases, prior to sintering the slurry, the method includes casting the slurry as a film. In another example, the method includes providing a green film by: In yet another embodiment, the method further comprises filtering the filtered slurry. In some of these examples, the method further includes providing a pellet of the Prior to sintering the slurry, the method includes forming a green film by casting the slurry. In still another embodiment, the method includes sintering the filtered slurry. In an embodiment of sintering the slurry, the sintering step further comprises a setting press. applying pressure to the slurry using a pressure gauge; heating the slurry under flowing inert gas at 140° C. Heat at 400°C for about 1 to about 6 hours, and then perform thermal sintering or electric field assisted sintering for about 10 minutes to about 10 hours. This includes:

[0307] In one example, the garnet precursor is made from LiOH, La2O3, ZrO2, and Al(NO3)3.9H2O. Be selected.

[0308] In some examples, the garnet precursor is calcined in a vessel at 900° C. for 6 hours. In an example, the vessel is an alumina (ie, Al2O3) vessel.

[0309] In certain instances, crushing the formed garnet may include crushing the formed garnet. d 50 In some other examples, the formed garnet is ground. The crushing step is carried out to obtain the d 50 This is continued until the particle size is about 100 nm. In one example, crushing the formed garnet reduces the d5 In one example, the formed garnet is crushed until the grain size is about 200 nm. This means that the d 50 This is continued until the particle size reaches approximately 250 nm. The crushing of the formed garnet reduces the d of the formed garnet. 50 Particle size is about 350 In one example, the grinding of the garnet is performed until the garnet is 0.1 nm. -Net's d 50 This is continued until the particle size reaches about 400 nm.

[0310] In some instances, the crushed formed garnet is mixed with a binder to form a slurry. The forming of the binder comprises about 4% w / w of a binder. In some examples, the binder is polyvinyl butyral.

[0311] In some instances, filtering the slurry includes filtering the slurry using an 80 mesh sieve. This includes:

[0312] In some instances, providing pellets of the filtered slurry includes pellets having a diameter of 13 mm. In some examples, the pellet has a diameter of 10 mm, It has a diameter of 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm.

[0313] In some instances, applying pressure to the slurry using a setting plate In some other examples, the setting Pressuring the slurry with a plate exerts a pressure of 2 metric tons. In some instances, pressure is applied to the slurry using a setting plate. In some instances, setting Pressurizing the slurry with a plate exerts a pressure of 3.5 metric tons. Includes.

[0314] In some examples, the setter plate is a Pt setter plate. In one embodiment, the setter plate is a garnet setter plate. In yet another embodiment, the setter plate is a porous setter plate. In yet another embodiment, the setter plate is a porous garnet setter plate. The plate is a porous zirconia setter plate.

[0315] In some examples, the method includes using a flow rate of 315 sccm of argon gas. Contains inert gas.

[0316] In some examples, the methods described herein involve treating the slurry under flowing inert gas. This involved heating the mixture at 160° C. and 330° C. for two hours (hr), respectively, under a stream of humidified argon. Includes various dwells.

[0317] (e. Microcrystalline Lithium-Filled Garnet) In some examples, provided herein are alumina doped lithium A method for producing thin films using fine grains of filled garnet. In some cases To produce these fine grains, the films described herein are heated to a maximum temperature of 1150° C. In some instances, to produce these fine grains, the methods described herein are The resulting film is thermally sintered at a maximum temperature of 1150° C. for a period of up to six hours. To produce these fine grains, the films described herein are thermally sintered at a maximum temperature of 1075° C. In some instances, the methods described herein are used to create these fine grains. The resulting film is thermally sintered at a maximum temperature of 1075° C. for a period of up to 6 hours. In one example, the film is thermally sintered for 15 minutes. If only sintering is performed, a thermal sintering temperature of up to 1200° C. is used.

[0318] As the temperature increases, the grains grow larger. Also, at a given temperature, As the crystal grows larger, the dwell time at that temperature increases. The method described in the above involves thermal sintering at a temperature of less than 1200°C, or less than 1150°C, or less than 1075°C. In some of these examples, the methods described herein include In some examples, the method includes thermally sintering the composition at a temperature of from 100 to 200° C. for a period of 6 hours or less. The methods described include heat sintering for a period of 15 minutes or less. In some other examples, the methods described herein include thermal sintering at 1050° C. In some other examples, the method described herein involves thermal sintering at 1000° C. In the present invention, the method described herein includes thermal sintering at 950° C. In some examples, the methods described herein include thermal sintering at 900° C. In another example, the methods described herein include thermal sintering at 850° C. In some other examples, the methods described herein include thermal sintering at 800°C. In some other examples, the methods described herein include thermal sintering at 750° C. In some other examples, the methods described herein include thermal sintering at 700° C. In some other examples, the methods described herein include thermal sintering at 650° C. In some other examples, the methods described herein include thermal sintering at 600° C. In some other examples, the methods described herein include thermally treating the substrate at 550° C. In some other examples, the methods described herein include sintering at 500° C. In some other examples, the methods described herein include thermally sintering the mixture at 45 In some other examples, the methods described herein include thermal sintering at 0° C. In some other examples, the methods described herein include thermally sintering the mixture at 400° C. The method includes thermal sintering at 350° C. In some other examples, the methods described herein include The method includes thermal sintering at 300° C. In some other examples, the method described herein The method described herein includes thermal sintering at 250° C. The method described involves thermal sintering at 200° C. The method described in the document involves thermal sintering at 150°C.

[0319] In some instances, the lower amount of Li in the lithium-loaded garnet is This results in fewer grains in the films described.

[0320] (f. Casting) In some examples, the slurries described herein are applied by slot die coating, slot casting, doctor blade casting, mold casting, roll coating, gravure, microgravure A. Using casting techniques, including screen printing, flexography, and / or other related methods; Deposit onto a substrate.

[0321] Another method for casting garnet materials using a sintering process is disclosed in US Pat. No. 6,393,433, filed Oct. 7, 2013. METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH No. 61 / 887,451, filed on January 13, 2014, entitled "SINTERING PROCESS" In a U.S. Provisional Patent Application entitled "GARNET THIN FILM ELECTROLYTE," No. 61 / 926,910, filed June 4, 2014, which is incorporated herein by reference, and which is incorporated herein by reference in its entirety. METHODS AND SYSTEMS FOR FORMING GARNET MATERIAL WITH RET No. 62 / 007,417, filed on July 18, 2014, entitled "ACTIVE SINTERING" Fine grained lithium ion conductive thin film garnet ceramics U.S. Provisional Patent Application No. 62 / 026,271, entitled "Ium-Ion Conducting Thin Film Garnet Ceramics" No. 2006 / 013661 and No. 2006 / 013665, filed on July 18, 2014, Garnet Catholyte and Solid-State Electrochemical Device GARNET CATALYTE AND SINTERING OF SOLID STATE ELECTROCHEMICAL D This is described in U.S. Provisional Patent Application No. 62 / 026,440, entitled "Compound Devices and Components." Each of these provisional patent applications is incorporated herein by reference in its entirety for all purposes. can be.

[0322] (g. Sintering Method) The particular solid ionic conductor was pressed into a small pellet approximately 10 mm in diameter and 2 mm thick. Although it can be sintered by conventional processes, thin films of garnet-based materials can be Known methods for fabricating 100 nm thick films for battery applications require membrane lateral dimensions of approximately 10 cm and thicknesses of 100 nm to 50 μm. is insufficient.

[0323] Applying current and voltage can be used to form thin films, particularly garnets (e.g., lithium-filled garnets). It is inherently difficult to sinter films containing ferroelectrics. Resistive heating occurs within the net material as it flows through it, thereby resulting in a sintering effect. Related: For example, sintering garnets using electricity, as is done in FAST sintering The electricity resistively heats and sinters the garnet material, which is where the impedance becomes maximum. As the garnet sinters, the impedance decreases, and the current through the garnet The resistance heat associated with the garnet material is also reduced. The impedance is reduced in certain parts of the garnet material, So, the current flows mainly along the path of least resistance (i.e. the path with the smallest impedance). This avoids resistive heating of the unsintered part of the garnet, which has a significantly higher impedance. As more garnet sinters and the impedance decreases, the remaining garnet It becomes more difficult to sinter the green part, and the impedance is at its highest. This is particularly difficult due to the garnet portion having the lowest impedance.

[0324] To overcome this difficulty, cylindrical shaped elements, such as those shown in FIG. Some have proposed a method for transferring an applied current between spaced electrodes at the extreme longitudinal ends of a cylinder. By doing so, these people overcome the above mentioned difficulties because the electric current However, as used herein and in this patent application, For some of the applications considered for this, thin film form factors are required. In some instances, this form element is rectangular in shape. In the example, the form element is rectangular-like in shape. The rectangular and rectangular shaped elements are difficult to sinter, in part because the electrodes through which the current is applied For thin films, the applied current is: Through the z-direction of the membrane, which is one of the shorter paths through the bulk of the material.

[0325] In addition to the difficulties mentioned above, for many applications, thin films must be primarily aligned in the x- or y-direction. Densification in the z-direction is preferred (as shown in Figure 23), because shrinkage of the membrane occurs primarily in the z-direction. This means that the axial displacement is greater than that occurring in either the x- or y-direction. Achieving densification and shrinkage is also a challenge addressed by the present application. Several sintering methods are described which overcome these and other sintering difficulties.

[0326] As shown in FIG. 24 or FIG. 45, an exemplary sintering method is to apply current through the film in the z-direction. In this manner, FAST sintering includes disposing an electrode on a thin film shaped element. It is utilized according to the sintering method described.

[0327] Another exemplary sintering method involves the use of a sintering plate, as shown in FIG. In some examples, the applied current is passed through the sintering plate. During the passage through the sintering plate, pressure is applied according to the pressure values ​​listed herein and above in this application. In some other instances, the setter plate is , independently, apply pressure according to the pressure values ​​recited herein and above in this application. In another embodiment, one or more metal foil layers are interposed between the setter plate and the thin film to apply pressure. An electric current is applied to the inserted metal foil. Figure 20 shows how the metal foil is connected to the sintered membrane and the setter plate. 13 shows an example in which the stencil is placed between the stencil and the stencil.

[0328] In some instances, the metal powder is a garnet film to be sintered with the setter plate. In some of these examples, as the garnet film sinters, As the metal powder sinters into the sintered film, it adheres to the film. 1 shows an example in which the semiconductor laser is arranged between two semiconductor laser plates.

[0329] In some of these examples, the setter plate is a porous setter plate. In some of these examples, the setter plate is a garnet-based setter. In some of these examples, the setter plate is a perforated In some of these examples, the setter plate is a garnet-based A setter plate is a metal setter plate. As used herein, garnet The setter plate may include a setter plate comprising the garnet material described herein. Examples include

[0330] As shown in FIG. 17, in some instances, the sintering and optionally the application of pressure are The plates used for this purpose are aligned so that the applied current is directed to specific locations on the film being sintered. It is possible to have individually addressable contact points. As shown in FIG. The tapered ends of the contours (100) represent these individually addressable contact points. As used herein, individually addressable means controllably addressable to separate contact points. A controllable and individual current or voltage can be applied to one contact point, which may be different from the applied current or voltage. This refers to the ability to apply

[0331] In some instances, a pressurized material is used to sinter and optionally apply pressure. The port may have a grid structure. In some examples, the grid structure It can be positioned on the sintering membrane at various positions during the sintering process. It is movable.

[0332] As shown in FIG. 18, in some instances, the thin film form element is formed by calendering. In these examples, the calender rollers are sintered as they move through the calender. Apply pressure according to the pressure value specified in the manual, and apply the current or also provides a conduit for the applied voltage. The arrows on either side indicate the direction of movement of the sintered film as it moves through the calender rollers. is.

[0333] As shown in FIG. 19, an example in which thin film features are sintered while moving through the calender rollers. In some of the calender rollers, the current or voltage is applied at various positions during sintering. The individually addressable contacts are provided so that the electrical current can be controllably and individually applied to the membranes. It has contact points (200).

[0334] As shown in FIG. 19, an example in which thin film features are sintered while moving through the calender rollers. In some of the present invention, one of the calender rollers is a ground electrode.

[0335] As shown in FIG. 22, an example in which thin film features are sintered while moving through the calender rollers. In some of the calenders, one of the calender rollers rotates about its longitudinal axis and The spiral design allows the printhead to move parallel to the longitudinal axis of the printhead. This allows an applied current or voltage to be directed to the film during sintering.

[0336] (i. Reaction Sintering) In some examples, described herein are reactive sintering processes. In these examples, the garnet precursors are mixed to form a mixture. Precursors include the garnet precursors described in this patent application. In some examples, the mixture is milled according to the milling methods described in this patent application. In one embodiment, the mixture is formulated as a slurry of milled precursor materials, and the slurry is In some instances, the slurry is then applied to, but not limited to, a doctor. The coating is applied onto the substrate by methods such as blade casting, slot casting, or dip coating. In some other examples, the slurry is applied to a substrate according to the casting methods described in this patent application. In some of these examples, the slurry is then dried to In some instances, the dried slurry is then cooled to remove any solvent or liquid therein. In some further examples, the dried slurry is applied to other layers of the battery components. In some of these examples, pressure is applied to bond or adhere the laminated layers together. In some instances, the dried slurry layer is subjected to pressure and then bonded to the adhesive layer as described herein. The sintering is carried out according to the method described in the present application. In the example carried out using a garnet precursor, sintering is carried out by chemically reacting the garnet precursor. This occurs simultaneously, resulting in the formation of sintered garnet.

[0337] In some instances, reaction sintering converts a garnet precursor into a preformed garnet. powder and sintering the mixture using temperature and / or applied current. In some instances, the ratio of garnet precursor to garnet powder is 10:90. In some instances, the ratio of garnet precursor to garnet powder is 20:80. In some instances, the ratio of garnet precursor to garnet powder is 25:75. In some instances, the ratio of garnet precursor to garnet powder is 50:50. In some examples, the ratio of garnet precursor to garnet powder is 60:40. In some examples, the ratio of garnet precursor to garnet powder is 70:30. In the example, the ratio of garnet precursor to garnet powder is 75:25. In the examples, the ratio of garnet precursor to garnet powder is 80:20. In this example, the ratio of garnet precursor to garnet powder is 90:10.

[0338] (ii. Tape Casting) In some examples, described herein are methods for producing thin films using tape casting. In these processes, ceramic powder is mixed with a dissolved binder and optionally a binder. The powder is dispersed in a liquid or solvent containing the powder to form a homogeneous mixture. The thick mixture or "slip" is cast onto a substrate using a doctor blade casting method. In some examples, the substrate may be a coated material such as, but not limited to, silicone coated MYLAR. The liquid or solvent is then evaporated to form a dry "green film." In some instances, the green film is peeled off of the MYLAR and molded into a particular shape, e.g. For example, the material is cut into a square, rectangular, circular, or oval shape. A metal powder is optionally incorporated into the membrane or adhered to one side of the membrane. In these examples, the metal powders are Ni, Cu, Ni-garnet mixture, C In some examples, the ZnO-ZnO mixture is selected from the group consisting of ZnO, ... Tape casting involves the use of an aperture of about 1 to 100 μm through which the tape is cast during deposition. The extension will be carried out.

[0339] (iii. Hot pressing) In some examples, described herein are methods for producing thin garnet films. In these examples, the green tape is processed as shown in FIG. In some cases, the binder is first removed and then sintered. In these particular examples, the binder is heated to a temperature of about 200, 300, 400, 500, or 600° C. The binder can be removed by burning at 40°C. The film is heated to a sintering temperature of about 800°C to about 1200°C under a uniaxial loading pressure of about 10 to about 100 MPa. In these examples, the applied pressure is such that the membrane does not deform or warp during sintering. Further improvements in the sintering direction perpendicular to the membrane surface and in the production of dense membranes. Provides the driving force.

[0340] In some instances, green films are prepared by first casting the film onto a metal foil. In some cases, sintering is performed after the binder is burned out. In some of these examples, sintering involves bonding the film to one of the metal foil substrates under pressure. This involves heating the substrate to a temperature below the melting point of the metal or metals. When using a Cu-substrate, a higher sintering temperature can be used compared to when using a Cu-substrate. can.

[0341] (iv. Constrained Sintering) In some instances, the green film is heated by placing it between setter plates. Although it can be sintered by applying a small amount of pressure, it is possible to constrain the membrane and initiate the sintering process. These examples prevent inhomogeneities that can stress the membrane and cause it to warp during the process. In some of the above, the setter plate is porous, e.g., porous yttria It is advantageous to fabricate stabilized zirconia. The binder diffuses out of the film during the burnout or sintering process. In some cases, the burnout and sintering processes are performed in part to remove these porous setter plates. In some cases, a slight amount of pressure can be applied to the sintering process. During the sintering process, a pressure plate was placed on the green film without any further pressure from the outside. The pressure exerted by the weight of the setter plate is The constrained sintering is carried out substantially as shown in FIG. 4 and / or FIG.

[0342] (v. Vacuum sintering) In some instances, sintering is carried out as described above, but during sintering in a vacuum chamber. In this example, a vacuum is applied to trap the gas within the ceramic during sintering. In some of these cases, trapped gases are expelled from the ceramic. The pumped gas fills the pore spaces that can prevent the sintering ceramic from densifying beyond a certain point. By applying pressure to the inside of the ceramic, it is prevented from sintering further. The trapped gas is removed by sintering the pores that contained the gas and removing the trapped gas from the vacuum system. densification beyond what would be possible if the trapped gas was not expelled can be done.

[0343] (vi. Electric Field Assisted Sintering, FLASH Sintering, and FAST Sintering) Electric field assisted sintering technology (FAST) sintering can enhance the sintering reaction rate. That is, electrons, holes, and / or ions in the sintering material move, and as a result, the material is later heated by Joule heating. The heating is concentrated at the point where the resistance is maximum (P = I R, where I 2 is the current and R is the resistance). This point tends to be at the particle-particle neck portion. Since these points are exactly the places where sintering is desirable, FAST sintering can be particularly effective. The standard garnet sintering procedure may take 6 to 36 hours at 1050 - 1200°C in some examples. In contrast, FAST sintering of garnet can be carried out at 600°C and less than 5 minutes . The advantages are lower-cost processing (higher throughput), lower reactivity (at lower temperatures, garnet is less likely to react with other components), and less lithium loss (lithium evaporation is a major failure mode that hinders effective sintering). FAST sintering of garnet is most effective with low current and short time [inserted data]. Since garnet materials have high ionic conductivity, low current is preferred, similar to AC current, so that bulk transport of ions does not occur. The parameters can range from: 1 minute < time < 1 hour, 500 < temperature < 1050°C , 1 Hz < frequency < 1 MHz, 1 V < VAC rms < 20 V. In some examples, FAST sintering is combined with hot pressing that includes uniaxial pressing of the film during sintering. In some examples , FAST sintering is combined with hot pressing onto a permanent substrate, for example, a metal, such as a current collector. In some examples , FAST sintering is combined with constrained sintering that fixes or physically constrains the film without applying a significant amount of pressure. In some examples, FAST sintering is combined with two -layer sintering (and three-layer sintering, for example, electrolyte-metal-electrolyte) to provide mechanical support and ​​​​​​ In some instances, FAST sintering is used to remove pores and form a current collector simultaneously in one step. To facilitate this, it is used in conjunction with vacuum sintering, where sintering is carried out under low absolute pressure.

[0344] In some embodiments, disclosed herein is a method of making a thin film. providing a green thin film by annealing the garnet; The composite material is made of a mixture of a crystalline electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and a combination thereof. In some examples, the method includes at least one member selected from the group consisting of: If present in the green thin film, further comprising removing the solvent. The method optionally includes laminating a membrane to the surface. In some examples, the method includes: and removing the binder, if present in the film. includes sintering the film, where the sintering can be thermal sintering or electric field assisted sintering (FAST). In some of these examples, the thermal sintering includes sintering the film for about 70 In the range of 0°C to about 1200°C, for about 1 to about 600 minutes, and * 10 -1 ~1 * 10 -15 The partial pressure of oxygen in the atmospheric range In another example, the FAST sintering step comprises heating the film in an atmosphere having a temperature of about 500. The process involves heating the thin film at temperatures ranging from 0.4 °C to about 900 °C and applying a DC or AC electric field to the thin film.

[0345] In some embodiments, disclosed herein is a method of making a membrane, comprising: providing a green thin film; wherein the green thin film is a garnet electrolyte, active electrode (e.g., cathode) material, conductive additives, solvents, binders, and In some examples, the composition includes at least one member selected from the group consisting of combinations of the above. In some cases, the method further includes removing the solvent, if present in the green thin film. In some examples, the method optionally includes laminating a membrane to the surface. In some embodiments, the method includes removing the binder, if present in the membrane. In the method, the method includes sintering the film, wherein the sintering includes thermal sintering. In some of these examples, thermal sintering includes heating the film to about 700° C. to about 700° C. In the range of about 1200°C, for about 1 to about 600 minutes, and * 10 -1 ~1 * 10 -15 It has an oxygen partial pressure in the atmospheric range. This includes heating in an atmosphere containing

[0346] In some embodiments, disclosed herein is a method of making a membrane, comprising: providing a green thin film; wherein the green thin film is a garnet The composite material comprises a conductive electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and combinations thereof. In some examples, the method includes at least one member selected from the group consisting of: It further includes removing the solvent, if present in the sintered thin film. The method optionally includes laminating a membrane to the surface. In some examples, the method includes laminating a membrane and removing the binder, if present in the composition. In some examples, the method includes and sintering the film, where the sintering comprises electric field assisted sintering (FAST). In some of these examples, FAST sintering is performed by sintering the film at temperatures ranging from about 500°C to about 900°C. This involves heating and applying a DC or AC electric field to the thin film.

[0347] In any of the methods described herein, the green thin film is a lithium-loaded garnet. In any of the methods described herein, the method may include a catalyst electrolyte or a precursor thereof. The green thin film may include an alumina doped lithium loaded garnet electrolyte.

[0348] In any of the methods described herein, the thermal sintering may comprise heating the film to a temperature of about 400° C. to about 400° C. About 1200°C; or about 500°C to about 1200°C; or about 900°C to about 1200°C; or about 1000°C to about 1200°C; or This may include heating in the range of about 1100°C to about 1200°C.

[0349] In any of the methods described herein, the method includes heating the membrane for about 1 to about 600 minutes. In any of the methods described herein, the method may include removing the membrane from the membrane for about 20 minutes. In any of the methods described herein, the method may include heating for about 600 minutes. The method may include heating the membrane for about 30 to about 600 minutes. In any case, the method may include heating the film for about 40 to about 600 minutes. In any of the methods described in the above, the method includes heating the film for about 50 to about 600 minutes. In any of the methods described herein, the method may include separating the membrane from about 60 to about 600 In any of the methods described herein, the method may include heating the Any of the methods described herein may include heating the film for about 70 to about 600 minutes. In the method, the method may include heating the film for about 80 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 90 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 100 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about In any of the methods described herein, the method may include heating for about 120 to about 600 minutes. The method may include heating the membrane for about 140 to about 600 minutes. In any of the above, the method may include heating the membrane for about 160 to about 600 minutes. In any of the methods described in the document, the method includes heating the film for about 180 to about 600 minutes. In any of the methods described herein, the method may include separating the membrane from about 200 to about 6 In any of the methods described herein, the method may include heating for 00 minutes. Any of the methods described herein may include heating the membrane for about 300 to about 600 minutes. In the method, the membrane may be heated for about 350 to about 600 minutes. In any of the methods described herein, the method may include heating the film for about 400 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 450 to about 600 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating for about 500 to about 600 minutes. The method may include heating the membrane for about 1 to about 500 minutes. In any of the above, the method may include heating the film for about 1 to about 400 minutes. In any of the methods described above, the method includes heating the film for about 1 to about 300 minutes. In any of the methods described herein, the method includes heating the membrane for about 1 to about 200 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating the mixture for about 1 to about 100 minutes. The method can include heating the membrane for about 1 to about 50 minutes.

[0350] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may involve heating in the range of about 1200° C. and applying a DC or AC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 400° C. to about 900° C. and applying a DC or AC electric field to the thin film. The method involves heating the film to a temperature range of about 600°C to about 1150°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering includes applying a temperature of about 700° C. to about 9 These include heating the thin film in the range of 00°C and applying a DC or AC electric field to the thin film. In this example, FAST sintering involves heating the film to a temperature in the range of about 800°C to about 900°C and In some instances, FAST sintering involves applying a DC or AC electric field to the film. The method involves heating the film to a temperature range of about 500°C to about 800°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering includes sintering the film at a temperature in the range of about 500° C. to about 700° C. These include heating the thin film with a high voltage and applying a DC or AC electric field to the thin film. FAST sintering involves heating the film to a temperature range of about 500°C to about 600°C and applying DC or involves applying an AC electric field.

[0351] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may involve heating in the range of about 1000° C. and applying a DC electric field to the thin film. In this example, FAST sintering involves heating the film to a temperature in the range of about 600°C to about 900°C and In some instances, FAST sintering includes applying a DC electric field to the film. This involves heating the thin film to a temperature in the range of about 600°C to about 900°C and applying a DC electric field to the thin film. In some examples, FAST sintering involves heating the film to a temperature range of about 700°C to about 900°C. and applying a DC electric field to the thin film. In some examples, FAST sintering includes: This involves heating the film in the range of about 800° C. to about 900° C. and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 800°C. and applying a DC electric field to the thin film. In some examples, FAST sintering may be used. The method involves heating the film to a temperature range of about 500°C to about 700°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 600°C. This involves applying a DC electric field to the thin film.

[0352] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may include heating in the range of about 1000° C. and applying an AC electric field to the thin film. In any of the methods described above, the FAST sintering may be performed by sintering the film at a temperature in the range of about 500°C to about 900°C. This may include heating the thin film in a vacuum and applying an AC electric field to the thin film. FAST sintering involves heating the film to a temperature range of about 600°C to about 900°C and applying an AC electric field to the thin film. In some examples, FAST sintering includes applying a temperature of about 700° C. to about 9 These include heating the thin film in the range of 00°C and applying an AC electric field to the thin film. In this case, FAST sintering involves heating the film at a temperature in the range of about 800°C to about 900°C and applying AC to the thin film. In some examples, FAST sintering involves applying an electric field to the film at about 500° C. These include heating the thin film to temperatures in the range of 1000 to 8000°C and applying an AC electric field to the thin film. In an example, FAST sintering involves heating the film to a temperature in the range of about 500° C. to about 700° C. and In some examples, FAST sintering involves applying an AC electric field to the film. This involves heating in the range of 500°C to about 600°C and applying an AC electric field to the thin film.

[0353] In certain instances, the methods described herein may be performed according to the casting methods described in this disclosure. The method includes providing a green thin film by casting a film.

[0354] In some of the methods disclosed herein, sintering is performed using an inert setter plate. In some instances, sintering is performed between inert setter plates. When the pressure is applied to the membrane during sintering, the pressure is applied by a setter plate. The pressure is between 1 and 1000 pounds per square inch (PSI). In some examples, the pressure is 1 PSI In another example, the pressure is 10 PSI. In another example, the pressure is 20 PSI. In some other instances, the pressure is 30 PSI. In some instances, the pressure is 40 PSI. In yet other instances, the pressure is 50 PSI. In some instances, the pressure is 60 PSI. In yet another embodiment, the pressure is 70 PSI. In one embodiment, the pressure is 80 PSI. In another example, the pressure is 90 PSI. In yet another example, the pressure is 100 PSI. In some instances, the pressure is 110 PSI. In other instances, the pressure is 120 PSI. In other instances, the pressure is 130 PSI. In some other instances, the pressure is 140 PSI. In one example, the pressure is 150 PSI. In yet another example, the pressure is 160 PSI. In some instances, the pressure is 170 PSI. In yet other instances, the pressure is 180 PSI. In one example, the pressure is 190 PSI. In another example, the pressure is 200 PSI. In another example, the pressure is 210 PSI.

[0355] In some of the above examples, the pressure is 220 PSI. In other examples, the pressure is 23 In some other examples, the pressure is 240 PSI. The force is 250 PSI. In one example, the pressure is 260 PSI. In yet another example, the pressure is In some instances, the pressure is 280 PSI. In other instances, The pressure is 290 PSI. In some instances, the pressure is 300 PSI. In other instances, the pressure is 31 0 PSI. In yet another example, the pressure is 320 PSI. In some examples, the pressure In another example, the pressure is 340 PSI. In yet another example, the pressure is 35 In some other instances, the pressure is 360 PSI. In some instances, the pressure is In still other examples, the pressure is 380 PSI. In some examples, the pressure is The force is 390 PSI. In yet another example, the pressure is 400 PSI. In one example, the pressure In another example, the pressure is 420 PSI. In yet another example, the pressure is In some other instances, the pressure is 440 PSI. In yet another example, the pressure is 460 PSI. The pressure is 470 PSI. In yet another example, the pressure is 480 PSI. In another example, the pressure is 500 PSI. In yet another example, the pressure is is 510 PSI.

[0356] In some of the above examples, the pressure is 520 PSI. In other examples, the pressure is 53 In some other examples, the pressure is 540 PSI. The force is 550 PSI. In one example, the pressure is 560 PSI. In yet another example, the pressure is In some instances, the pressure is 570 PSI. In some instances, the pressure is 580 PSI. In still other instances, The pressure is 590 PSI. In some instances, the pressure is 600 PSI. In other instances, the pressure is 61 0 PSI. In yet another example, the pressure is 620 PSI. In some examples, the pressure In another example, the pressure is 640 PSI. In yet another example, the pressure is 65 In some other instances, the pressure is 660 PSI. In some instances, the pressure is In still other examples, the pressure is 680 PSI. In some examples, the pressure is The force is 690 PSI. In yet another example, the pressure is 700 PSI. In one example, the pressure In another example, the pressure is 720 PSI. In yet another example, the pressure is In some other instances, the pressure is 740 PSI. In yet another example, the pressure is 760 PSI. The pressure is 770 PSI. In yet another example, the pressure is 780 PSI. In another example, the pressure is 800 PSI. In yet another example, the pressure is is 810 PSI.

[0357] In another example, the pressure is 820 PSI. In one such example, the pressure is 830 PSI. In other instances, the pressure is 840 PSI. In some other instances, the pressure is 850 PSI. In one example, the pressure is 860 PSI. In yet another example, the pressure is 870 PSI. In some instances, the pressure is 880 PSI. In yet other instances, the pressure is 890 PSI. In one example, the pressure is 900 PSI. In another example, the pressure is 910 PSI. In yet other instances, the pressure is 920 PSI. In some instances, the pressure is 930 PSI. In another embodiment, the pressure is 940 PSI. In yet another embodiment, the pressure is 950 PSI. In some other instances, the pressure is 960 PSI. In some instances, the pressure is 970 PSI. In yet other instances, the pressure is 980 PSI. In some instances, the pressure is 990 PSI. In yet another example, the pressure is 1000 PSI.

[0358] In some instances, the setter plate can be porous. In other examples, the setter plate is not porous. The lithium activity in the plate is relatively high, i.e., the lithium concentration is higher in the setter than in the In another embodiment, the setter plate is at least 10 atomic percent of the SiO 2 . In some examples, the setter plate may be made of a garnet material. The setter plate may be a porous garnet setter plate. The plate may be made of zirconia. In some examples, the setter plate The setter plate may be a porous zirconia setter plate. The plate may be made of a metallic material as described herein. , the setter plate can be a porous metal setter plate.

[0359] In some instances, garnet-based setter plates provide beneficial surface properties for sintered films. These beneficial surface properties include flatness and surface roughness useful in battery applications. These beneficial properties include the prevention of Li evaporation during sintering. These beneficial properties include a preference for specific garnet crystal structures. In some methods disclosed herein, the inert setter plate may be porous. The conductive material is selected from conductive zirconia, graphite, or conductive metal plates. In some others, the inert setter plate is graphite. In yet another method, the inert setter plate is a conductive metal plate.

[0360] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The membrane is operated in a constant current mode, and then switched to constant current mode when the impedance of the membrane decreases by at least one order of magnitude. This includes operating in width mode.

[0361] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by an order of magnitude, the constant current amplitude mode is used. This includes operating in a

[0362] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by two orders of magnitude, the constant current amplitude mode is used. This includes operating in a

[0363] In some of the methods disclosed herein, the FAST sintering is performed by constant voltage oscillation. The impedance of the sintered film is then reduced by three orders of magnitude, at which point the impedance is switched to constant current amplitude mode. This includes operating in a

[0364] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The impedance of the sintered film is then reduced by four orders of magnitude, at which point the impedance is switched to constant current amplitude mode. This includes operating in a

[0365] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The impedance of the sintered film is then reduced from 1-100 Megaohm-cm to about 1-10 Once the resistance has been reduced to 1,000 ohm-cm, the device is operated in a constant current amplitude mode.

[0366] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant voltage.

[0367] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at constant power at 100 .mu.m.

[0368] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant current at .

[0369] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. until the film has a density at least 20, 30, 40, or 50% greater than that of the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. and operating at constant power until the mixture has a high density. In some cases, FAST sintering results in a film that is at least as thick as the film before sintering occurred. Also includes operating at a constant current until the mixture has a density that is 20, 30, 40, or 50% greater.

[0370] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than that which the membrane had before freezing occurred. In some of the methods disclosed herein, the method includes operating at a constant voltage until the In this case, FAST sintering results in a film that is at least 1 to 2 times thinner than the film had before sintering occurred. This includes operating at constant power until the device has an impedance that is 3, 4, or 5 orders of magnitude lower. In some of the disclosed methods, FAST sintering is performed after the membrane is sintered. Apply constant voltage until the membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than it had before. This involves operating in a current.

[0371] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. An impedance at least one order of magnitude lower or at most ten orders of magnitude lower than the membrane had before sintering occurred. Some of the methods disclosed herein include operating at a constant voltage until the In the present invention, FAST sintering is performed to provide a film with at least a tensile strength greater than the film had before sintering was performed. This includes operating at constant power until the device has an impedance that is one order of magnitude lower or at most ten orders of magnitude lower. In some of the methods disclosed herein, FAST sintering is performed to ensure that the film is sintered. The membrane has an impedance at least one order of magnitude lower than that of the membrane before the This involves operating at a constant current until

[0372] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. Operate at constant voltage until the membrane has an impedance approximately two orders of magnitude lower than it would have before fusion occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance approximately two orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method includes operating at constant power at FAST sintering results in a film with an impedance approximately two orders of magnitude lower than the film had before sintering occurred. This involves operating at a constant current until the device has a constant current capability.

[0373] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. Operate at constant voltage until the membrane has an impedance approximately six orders of magnitude lower than it would have before fusion occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance approximately six orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method includes operating at constant power at FAST sintering results in a film with an impedance approximately six orders of magnitude lower than the film had before sintering occurred. This involves operating at a constant current until the device has a constant current capability.

[0374] In some of the methods disclosed herein, FAST sintering is performed at a constant voltage. In some of the methods disclosed herein, FAST sintering is performed. Some of the methods disclosed herein include operating at constant power. In the present invention, FAST sintering involves operating at a constant current.

[0375] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The membrane is operated in a constant current mode, and then switched to constant current mode when the impedance of the membrane decreases by at least one order of magnitude. This includes operating in width mode.

[0376] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is at least twice the median dimension of the unsintered garnet grains. Among the methods disclosed herein, the method includes operating at a ramp voltage until the In some cases, FAST sintering is used to separate the garnet particles from the garnet particles prior to sintering. The lamp power should be operated until the particles have a median dimension at least twice that of the toner particles. In some of the methods disclosed herein, the FAST sintering includes: The garnet grains are at least twice as large as the median dimension of the garnet grains before sintering. This involves operating the lamp at a current until it has a median dimension equal to or greater than 100 nm.

[0377] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the thickness of the membrane. In some instances, sintering is applied until the film is 50 μm thick. In another example, sintering is applied until the film is 40 μm thick. In another example, sintering is applied until the film is 20 μm thick. In another embodiment, sintering is applied until the film is 10 μm thick. In one embodiment, sintering is applied until the film is 5 μm thick. In another embodiment, sintering is continued until the film is 0.5 μm thick. As used in this paragraph, thickness refers to the average dimension of the membrane in the z-direction (see FIG. 23). (Refers to this.)

[0378] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the conductivity of the membrane. For example, Sintering can be applied until the film has a conductivity of 1e-4 S / cm. Sintering can be applied until the film has a conductivity of 1e-5 S / cm. can be applied until the film has a conductivity of 1e-6 S / cm. In another example, sintering , can be applied until the film has a conductivity of 1e-7 S / cm. It can be applied until the film has a conductivity of 1e-8 S / cm.

[0379] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the impedance of the membrane. For example, sintering can be applied until the impedance of the film is 500 ohm-cm.

[0380] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include grain size within the film.

[0381] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the density of the film.

[0382] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the optical density of the film.

[0383] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the temperature of the film. Sintering can be applied until the membrane has a temperature of 50° C. In another example, sintering In another example, sintering may be applied until the film has a temperature of 150° C. In another example, sintering can be applied until the film has a temperature of 200° C. In another example, sintering can be applied until the film has a temperature of 250° C. In another example, sintering can be applied until the membrane has a temperature of 300° C. In another example, sintering is applied until the membrane has a temperature of 350° C. In another example, sintering can be applied until the membrane has a temperature of 400° C. In another example, sintering can be applied until the film has a temperature of 450° C. In another example, sintering can be applied until the film has a temperature of 500° C. In one example, sintering can be applied until the membrane has a temperature of 550° C. In another embodiment, sintering is applied until the membrane has a temperature of 600° C. In another embodiment, sintering may be applied until the membrane has a temperature of 650° C. In another example, sintering may be applied until the film has a temperature of 700° C. In another example, sintering may be applied until the film has a temperature of 800° C. In another example, sintering can be applied until the film has a temperature of 850° C. In another example, sintering can be applied until the film has a temperature of 900° C. In another example, sintering can be applied until the film has a temperature of 950° C. In another example, sintering can be applied until the film has a temperature of 1000° C. In another example, sintering can be applied until the membrane has a temperature of 1150° C. In another example, sintering can be applied until the film has a temperature of 1200° C. In another example, sintering can be applied until the film has a temperature of 1250° C. In one example, sintering can be applied until the membrane has a temperature of 1300° C. In this case, sintering can be applied until the membrane has a temperature of 1350°C.

[0384] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The run is continued until the membrane has a density at least 20, 30, 40, or 50% greater than the membrane before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. The method disclosed herein further comprises operating the lamp at a high lamp power until the lamp has a high density. In some cases, FAST sintering results in a film that is less porous than the film before sintering occurred. This includes operating at a lamp current until the lamp has a density that is at least 20, 30, 40, or 50% greater. In some of the methods disclosed herein, FAST sintering may be used to form a sintered membrane. The impedance is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the membrane had before The method of the present invention includes operating at a ramp voltage until the device has a constant current. In some cases, FAST sintering allows the film to have a thickness greater than the film had before sintering occurred. Operate lamps with 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower impedance In some of the methods disclosed herein, FAST sintering is means that the film has 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 more pores than the film had before sintering occurred. This involves operating the lamp current until it has an order of magnitude lower impedance.

[0385] In some of the methods disclosed herein, the FAST sintering is performed using a lamp current. In some of the methods disclosed herein, the FAST firing step includes operating at high pressure. The sintering step includes operating at lamp power. In some, FAST sintering involves operating with a lamp current.

[0386] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The membrane is operated in a constant current mode, and then switched to constant current mode when the impedance of the membrane decreases by at least one order of magnitude. In some of the methods disclosed herein, the method includes operating in a width mode. FAST sintering is performed by operating in a constant voltage amplitude mode, after which the impedance of the sintered film is 1 If the current is reduced by an order of magnitude, this includes operating in a constant current amplitude mode. In some of these, FAST sintering is performed by operating in a constant voltage amplitude mode and then sintering. This involves operating in constant current amplitude mode once the impedance of the membrane has decreased by two orders of magnitude. In some of the methods disclosed herein, the FAST sintering is performed in a constant voltage amplitude mode. Then, when the impedance of the sintered film decreases by three orders of magnitude, operate in constant current amplitude mode. In some of the methods disclosed herein, FAST sintering is The impedance of the sintered film is reduced by four orders of magnitude when it is operated in a constant voltage amplitude mode. This involves operating in a constant current amplitude mode.

[0387] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The impedance of the sintered film is then reduced from 1-100 Megaohm-cm to about 1-10 Once the resistance has been reduced to 1,000 ohm-cm, the device is operated in a constant current amplitude mode.

[0388] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant voltage.

[0389] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at constant power at 100 .mu.m.

[0390] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant current at .

[0391] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. until the film has a density at least 20, 30, 40, or 50% greater than that of the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. and operating at constant power until the mixture has a high density. In some cases, FAST sintering results in a film that is at least as thick as the film before sintering occurred. Also includes operating at a constant current until the mixture has a density that is 20, 30, 40, or 50% greater.

[0392] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than that which the membrane had before freezing occurred. In some of the methods disclosed herein, the method includes operating at a constant voltage until the In this case, FAST sintering results in a film that is at least 1 to 2 times thinner than the film had before sintering occurred. This includes operating at constant power until the device has an impedance that is 3, 4, or 5 orders of magnitude lower. In some of the disclosed methods, FAST sintering is performed after the membrane is sintered. Apply constant voltage until the membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than it had before. This involves operating in a current.

[0393] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. An impedance at least one order of magnitude lower or at most ten orders of magnitude lower than the membrane had before sintering occurred. Some of the methods disclosed herein include operating at a constant voltage until the In the present invention, FAST sintering is performed to provide a film with at least a tensile strength greater than the film had before sintering was performed. This includes operating at constant power until the device has an impedance that is one order of magnitude lower or at most ten orders of magnitude lower. In some of the methods disclosed herein, FAST sintering is performed to ensure that the film is sintered. The membrane has an impedance at least one order of magnitude lower than that of the membrane before the This involves operating at a constant current until

[0394] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. Operate at constant voltage until the membrane has an impedance approximately two orders of magnitude lower than it would have before fusion occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance approximately two orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method includes operating at constant power at FAST sintering results in a film with an impedance approximately two orders of magnitude lower than the film had before sintering occurred. This involves operating at a constant current until the device has a constant current capability.

[0395] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. Operate at constant voltage until the membrane has an impedance approximately six orders of magnitude lower than it would have before fusion occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance approximately six orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method includes operating at constant power at FAST sintering results in a film with an impedance approximately six orders of magnitude lower than the film had before sintering occurred. This involves operating at a constant current until the device has a constant current capability.

[0396] In some of the methods disclosed herein, FAST sintering is performed at a constant voltage. In some of the methods disclosed herein, FAST sintering is performed. Some of the methods disclosed herein include operating at constant power. In the present invention, FAST sintering involves operating at a constant current.

[0397] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The membrane is operated in a constant current mode, and then switched to constant current mode when the impedance of the membrane decreases by at least one order of magnitude. This includes operating in width mode.

[0398] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is at least twice the median dimension of the unsintered garnet grains. Among the methods disclosed herein, the method includes operating at a ramp voltage until the In some cases, FAST sintering is used to separate the garnet particles from the garnet particles prior to sintering. The lamp power should be operated until the particles have a median dimension at least twice that of the toner particles. In some of the methods disclosed herein, the FAST sintering includes: The garnet grains are at least twice as large as the median dimension of the garnet grains before sintering. This involves operating the lamp at a current until it has a median dimension equal to or greater than 100 nm.

[0399] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the thickness of the membrane. In some instances, sintering is applied until the film is 50 μm thick. In another example, sintering is applied until the film is 40 μm thick. In another example, sintering is applied until the film is 20 μm thick. In another embodiment, sintering is applied until the film is 10 μm thick. In one embodiment, sintering is applied until the film is 5 μm thick. In another embodiment, sintering is continued until the film is 0.5 μm thick. As used in this paragraph, thickness refers to the average dimension of the membrane in the z-direction (see FIG. 23). (Refers to this.)

[0400] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the conductivity of the membrane. For example, Sintering can be applied until the film has a conductivity of 1e-4 S / cm. Sintering can be applied until the film has a conductivity of 1e-5 S / cm. can be applied until the film has a conductivity of 1e-6 S / cm. In another example, sintering , can be applied until the film has a conductivity of 1e-7 S / cm. It can be applied until the film has a conductivity of 1e-8 S / cm.

[0401] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the impedance of the membrane. For example, sintering can be applied until the impedance of the film is 500 ohm-cm.

[0402] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include grain size within the film.

[0403] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the density of the film.

[0404] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the optical density of the film.

[0405] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, power, or current meets a certain predetermined value during sintering. In some instances, these values ​​include the temperature of the film. Sintering can be applied until the membrane has a temperature of 50° C. In another example, sintering In another example, sintering may be applied until the film has a temperature of 150° C. In another example, sintering can be applied until the film has a temperature of 200° C. In another example, sintering can be applied until the film has a temperature of 250° C. In another example, sintering can be applied until the membrane has a temperature of 300° C. In another example, sintering is applied until the membrane has a temperature of 350° C. In another example, sintering can be applied until the membrane has a temperature of 400° C. In another example, sintering can be applied until the film has a temperature of 450° C. In another example, sintering can be applied until the film has a temperature of 500° C. In one example, sintering can be applied until the membrane has a temperature of 550° C. In another embodiment, sintering is applied until the membrane has a temperature of 600° C. In another embodiment, sintering may be applied until the membrane has a temperature of 650° C. In another example, sintering may be applied until the film has a temperature of 700° C. In another example, sintering may be applied until the film has a temperature of 800° C. In another example, sintering can be applied until the film has a temperature of 850° C. In another example, sintering can be applied until the film has a temperature of 900° C. In another example, sintering can be applied until the film has a temperature of 950° C. In another example, sintering can be applied until the film has a temperature of 1000° C. In another example, sintering can be applied until the membrane has a temperature of 1150° C. In another example, sintering can be applied until the film has a temperature of 1200° C. In another example, sintering can be applied until the film has a temperature of 1250° C. In one example, sintering can be applied until the membrane has a temperature of 1300° C. In this case, sintering can be applied until the membrane has a temperature of 1350°C.

[0406] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The run is continued until the membrane has a density at least 20, 30, 40, or 50% greater than the membrane before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. The method disclosed herein further comprises operating the lamp at a high lamp power until the lamp has a high density. In some cases, FAST sintering results in a film that is less porous than the film before sintering occurred. This includes operating at a lamp current until the lamp has a density that is at least 20, 30, 40, or 50% greater.

[0407] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The impedance is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the membrane had before freezing occurred. The method disclosed herein includes operating with a ramp voltage until the device has a capacitance. In some cases, FAST sintering allows the film to retain more heat than the film had before sintering occurred. Operate the lamp at 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower impedance. This includes creating

[0408] In some of the methods disclosed herein, FAST sintering is performed to ensure that the membrane is sintered. The impedance is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the membrane had before freezing occurred. This involves operating the lamp current until it has a

[0409] In some of the methods disclosed herein, the FAST sintering is performed using a lamp current. In some of the methods disclosed herein, the FAST firing step includes operating at high pressure. The sintering step includes operating at lamp power. In some, FAST sintering involves operating with a lamp current.

[0410] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may involve heating in the range of about 1000° C. and applying a DC or AC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500° C. to about 900° C. and applying a DC or AC electric field to the thin film. The method involves heating the film to a temperature range of about 600°C to about 900°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering includes applying a heat treatment to the film at about 700° C. to about 900° C. These include heating the thin film in the range of °C and applying a DC or AC electric field to the thin film. In an example, FAST sintering involves heating the film to a temperature in the range of about 800° C. to about 900° C. and In some examples, FAST sintering includes applying a DC or AC electric field to the The thin film is heated to a temperature in the range of about 500° C. to about 800° C. and a DC or AC electric field is applied to the thin film. In some examples, FAST sintering includes sintering the film at a temperature in the range of about 500° C. to about 700° C. This includes heating and applying a DC or AC electric field to the thin film. FAST sintering involves heating the film to a temperature range of about 500°C to about 600°C and applying DC or It involves applying an AC electric field.

[0411] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may involve heating in the range of about 1000° C. and applying a DC electric field to the thin film. In this example, FAST sintering involves heating the film to a temperature in the range of about 600°C to about 900°C and In some instances, FAST sintering includes applying a DC electric field to the film. This involves heating the thin film to a temperature in the range of about 600°C to about 900°C and applying a DC electric field to the thin film. In some examples, FAST sintering involves heating the film to a temperature range of about 700°C to about 900°C. and applying a DC electric field to the thin film. In some examples, FAST sintering includes: This involves heating the film in the range of about 800° C. to about 900° C. and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 800°C. and applying a DC electric field to the thin film. In some examples, FAST sintering may be used. The method involves heating the film to a temperature range of about 500°C to about 700°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 600°C. This involves applying a DC electric field to the thin film.

[0412] In any of the methods described herein, FAST sintering the film at about 400° C. to about 500° C. This may include heating in the range of about 1000° C. and applying an AC electric field to the thin film. In any of the methods described above, the FAST sintering may be performed by sintering the film at a temperature in the range of about 500°C to about 900°C. This may include heating the thin film in a vacuum and applying an AC electric field to the thin film. FAST sintering involves heating the film to a temperature range of about 600°C to about 900°C and applying an AC electric field to the thin film. In some examples, FAST sintering includes applying a temperature of about 700° C. to about 9 These include heating the thin film in the range of 00°C and applying an AC electric field to the thin film. In this case, FAST sintering involves heating the film at a temperature in the range of about 800°C to about 900°C and applying AC to the thin film. In some examples, FAST sintering involves applying an electric field to the film at about 500° C. These include heating the thin film to temperatures in the range of 1000 to 8000°C and applying an AC electric field to the thin film. In an example, FAST sintering involves heating the film to a temperature in the range of about 500° C. to about 700° C. and In some examples, FAST sintering involves applying an AC electric field to the film. This involves heating in the range of 500°C to about 600°C and applying an AC electric field to the thin film.

[0413] In certain instances, the methods described herein include forming a green thin film by casting a film. This includes providing

[0414] (vii. Composite materials) In another embodiment, the disclosure provides herein a method for making a composite electrochemical device. The method includes the steps of: providing an anode layer comprising an anode current collector; providing a garnet-type solid electrolyte (SSE) layer in contact with at least one side of the oxide layer; and optionally sintering the SSE; providing a porous garnet layer in contact with the SSE layer; and optionally sintering the porous garnet layer; optionally, adding carbon, A lithium conducting polymer, an active cathode material, and a combination thereof. and contacting the porous garnet layer with at least one member; The method described herein includes the steps of, in any order, providing a current collector layer.

[0415] In some examples, described herein are thin, free-standing garnet films. A method for sintering comprising the steps of: casting a garnet slurry to form a garnet powder; providing a garnet tape, wherein the slurry comprises a garnet precursor, a garnet, a barium oxide, At least one selected from the group consisting of binders, solvents, plasticizers, dispersants, and combinations thereof. The step of sintering the green tape between setter plates is optionally wherein the sintering comprises, in order, thermal sintering, spark plasma sintering, or and sintering the membrane using the setter plate. Optionally, applying pressure to the

[0416] In some of these aforementioned examples, the slurry is ground and calcined gallium. In some instances, the solids loading of the green tape is at least 30%. In some examples, the solids loading of the green tape is at least 40% w / w. In some instances, the solids loading of the green tape is at least 50% w / w. In some instances, the solids loading of the green tape is at least 60% w / w. In some instances, the solids loading of the green tape is at least 70% w / w. In some of these examples, the membrane is sintered directly to the metal. In some examples, the metal is a metal powder or a metal foil. It is between and in contact with one side of the loop and one setter plate. In this example, the metal powder layer is disposed between and in contact with two green tapes. wherein the green tape is between and in contact with the setter plates. In some examples, the metal powder is Ni or Cu powder. In some, a source of Li is placed near the film being sintered during sintering. In particular examples, the setter plate may be made of YSZ, graphite, YSZ, Mg-SZ, zirconia. , porous zirconia, SiO2, SiO2 sand, Al2O3, Al2O3 powder, Al2O3 paper, nickel, Nickel powder, garnet, garnet powder, sacrificial garnet film, LiAlO2, LiLaO2, Li2ZrO 3. In some instances, two different setter plates are used. In some of these examples, the zirconia setter plate comes into contact with the metal powder. In some examples, the applied pressure is between 0.001 MPa and 200 MPa.

[0417] (viii. Two-layer and three-layer sintering) In some instances, the sintered film is then contacted with a metal layer that is in contact with the garnet-electrolyte layer. A non-limiting example is shown in FIG. show.

[0418] (ix. Thermal Sintering) In some embodiments, disclosed herein is a method for producing an energy storage electrode. A method comprising providing a green thin film; The membrane comprises a garnet-type electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and In some examples, the composition includes at least one member selected from the group consisting of: In some embodiments, the method further includes removing the solvent, if present in the green thin film. In some examples, the method optionally includes laminating the film to a surface. In the method, the method includes removing the binder, if present in the film. In some examples, the method includes sintering the film, where sintering includes thermal sintering. In some of these examples, thermal sintering includes sintering the film to a temperature of 1000° C. In the range of about 700°C to about 1200°C for about 1 to about 600 minutes, and with an oxygen partial pressure of 1e-1 atm to 1e-15 atm. This includes heating in an atmosphere containing

[0419] In some embodiments, disclosed herein is a method for producing an energy storage electrode. A method comprising providing a green thin film; The membrane comprises a garnet-type electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and In some examples, the composition includes at least one member selected from the group consisting of: In some embodiments, the method further includes removing the solvent, if present in the green thin film. In some examples, the method optionally includes laminating the film to a surface. In the method, the method includes removing the binder, if present in the film. In some examples, the method includes sintering the film, where sintering includes applying an electric field In some of these examples, FAST sintering is The method involves heating the film at a temperature in the range of about 500°C to about 900°C and applying a DC or AC electric field to the thin film. This includes adding

[0420] In any of the methods described herein, the green thin film comprises a garnet-type electrolyte. In other methods, the green thin film may include the active electrode material. In some methods, the green thin film may include a conductive additive. In some methods, the green thin film may include a binder.

[0421] In any of the methods described herein, the thermal sintering may comprise heating the film to a temperature of about 700° C. to about 700° C. About 1200°C; or about 800°C to about 1200°C; or about 900°C to about 1200°C; or about 1000°C to about 1200°C; or Any of the methods described herein may include heating to a temperature in the range of about 1100° C. to about 1200° C. In any of the above, the thermal sintering may be performed by subjecting the film to a temperature of about 700° C. to about 1100° C.; or about 700° C. to about 1000° C.; or may include heating in the range of about 700°C to about 900°C; or about 700°C to about 800°C. In any of the methods described herein, the thermal sintering may include subjecting the film to a temperature of about 700° C., about 7 50℃, about 850℃, about 800℃, about 900℃, about 950℃, about 1000℃, about 1050℃, about 1100℃, about 1150℃ or about 1200° C. Any of the methods described herein may include heating the In the above, thermal sintering is performed to form the film at 700°C, 750°C, 850°C, 800°C, 900°C, 950°C, 10 The method may include heating to a temperature of 100° C., 1050° C., 1100° C., 1150° C., or 1200° C. In any of the methods described herein, the thermal sintering step includes heating the film to 700° C. In any of the methods described herein, the thermal sintering may include and heating the film to 750° C. Any of the methods described herein may be used. In the present specification, the thermal sintering can include heating the film to 850° C. In any of the methods described in, the thermal sintering includes heating the film to 900° C. In any of the methods described herein, the thermal sintering can include: Heating the film to 950° C. Any of the methods described herein may be used. In the present invention, the thermal sintering may include heating the film to 1000° C. In any of the methods described, the thermal sintering includes heating the film to 1050° C. In any of the methods described herein, the thermal sintering may include In any of the methods described herein, the method may include heating the mixture to 1100° C. In the present invention, the thermal sintering can include heating the film to 1150° C. In any of the methods described herein, the thermal sintering includes heating the film to 1200° C. It is possible.

[0422] In any of the methods described herein, the method includes heating the membrane for about 1 to about 600 minutes. In any of the methods described herein, the method may include removing the membrane from the membrane for about 20 minutes. In any of the methods described herein, the method may include heating for about 600 minutes. The method may include heating the membrane for about 30 to about 600 minutes. In any case, the method may include heating the film for about 40 to about 600 minutes. In any of the methods described in the above, the method includes heating the film for about 50 to about 600 minutes. In any of the methods described herein, the method may include separating the membrane from about 60 to about 600 In any of the methods described herein, the method may include heating the Any of the methods described herein may include heating the film for about 70 to about 600 minutes. In the method, the method may include heating the film for about 80 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 90 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 100 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about In any of the methods described herein, the method may include heating for about 120 to about 600 minutes. The method may include heating the membrane for about 140 to about 600 minutes. In any of the above, the method may include heating the membrane for about 160 to about 600 minutes. In any of the methods described in the document, the method includes heating the film for about 180 to about 600 minutes. In any of the methods described herein, the method may include separating the membrane from about 200 to about 6 In any of the methods described herein, the method may include heating for 00 minutes. Any of the methods described herein may include heating the membrane for about 300 to about 600 minutes. In the method, the membrane may be heated for about 350 to about 600 minutes. In any of the methods described herein, the method may include heating the film for about 400 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 450 to about 600 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating for about 500 to about 600 minutes. The method may include heating the membrane for about 1 to about 500 minutes. In any of the above, the method may include heating the film for about 1 to about 400 minutes. In any of the methods described above, the method includes heating the film for about 1 to about 300 minutes. In any of the methods described herein, the method includes heating the membrane for about 1 to about 200 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating the mixture for about 1 to about 100 minutes. The method can include heating the membrane for about 1 to about 50 minutes.

[0423] (x. Lamination) In some of the methods described herein, the lamination is subjected to a pressure of 1000 pounds per square inch. In another embodiment, the method further comprises applying a pressure of less than 100 psi and heating the membrane. Lamination involves applying pressure of less than 750 pounds per square inch (PSI) and heating the film. In some other embodiments, the lamination is performed at a pressure of less than 700 pounds per square inch (PSI). In another embodiment, the lamination includes applying a pressure of 650 lbs. This involves applying pressure of less than 1000 psi and heating the membrane. In one embodiment, the lamination is performed by applying a pressure of less than 600 pounds per square inch (PSI) and In another embodiment, the lamination is performed at a pressure of 550 pounds per square inch (PSI). In some other embodiments, the method further comprises applying a pressure of less than 1000 psi and heating the membrane. The lamination involves applying a pressure of less than 500 pounds per square inch (PSI) and heating the membrane. In another embodiment, the lamination applies a pressure of less than 450 pounds per square inch (PSI). In some other embodiments, the lamination includes heating the film to 400 lbs. The method includes applying a pressure of less than 1000 psi and heating the membrane. In this manner, the lamination is performed by applying a pressure of less than 350 pounds per square inch (PSI) and heating the membrane. In some other embodiments, the laminate is heated to 300 pounds per square inch (PS I) and heating the film. This involves applying a pressure of less than 250 pounds per square inch (PSI) and heating the membrane. In some other embodiments, the lamination is performed under pressure of less than 200 pounds per square inch (PSI). In another embodiment, the lamination includes applying 150 pounds per square inch (psi) of pressure to the film. The method involves applying pressure of less than 1000 psi and heating the membrane.

[0424] In some other embodiments, the lamination is performed at a pressure of less than 100 pounds per square inch (PSI). In another embodiment, the lamination comprises adding 50 pounds per square meter of water and heating the film. Some other experiments involve applying pressure of less than 1000 psi and heating the membrane. In an embodiment, the lamination is performed by applying a pressure of less than 10 pounds per square inch (PSI) and applying pressure to the membrane. Some of the lamination methods described herein involve heating the film. Some of the lamination methods described herein involve heating the The method includes heating the heated film to about 25°C to about 180°C.

[0425] In some of the methods disclosed herein, the deposition step includes depositing a green thin film electrolyte. into a composite electrode; wherein the composite electrode comprises an electrolyte, an active electrode material, a conductive The composition further comprises at least one member selected from the group consisting of: a thermal expansion agent, a thermal expansion coefficient agent, a thermal expansion coefficient additive, and combinations thereof. In some of these embodiments, the composite electrode includes an electrolyte. In certain other of the embodiments, the composite electrode includes an active electrode material. In some other embodiments, the composite electrode includes a conductive additive.

[0426] (xi. Setter plate) In some of the methods disclosed herein, sintering is performed using an inert setter plate. In some instances, sintering is performed between inert setter plates. In some cases, pressure is applied to the membrane during sintering by a setter plate. The pressure may be between 1 and 1000 pounds per square inch (PSI). In some instances, the pressure may be 1 PSI. In another example, the pressure is 10 PSI, and in another example, the pressure is 20 PSI. In some other instances, the pressure is 30 PSI. In some instances, the pressure is 40 PSI. In yet other instances, the pressure is 50 PSI. In some instances, the pressure is 60 PSI. In yet another embodiment, the pressure is 70 PSI. In one embodiment, the pressure is 80 PSI. In some examples, the pressure is 90 PSI. In other examples, the pressure is 100 PSI. In some instances, the pressure is 110 PSI. In other instances, the pressure is 120 PSI. In some examples, the pressure is 130 PSI. In some other examples, the pressure is 140 PSI. In one example, the pressure is 150 PSI. In yet another example, the pressure is 160 PSI. In some instances, the pressure is 170 PSI. In yet other instances, the pressure is 180 PSI. In one example, the pressure is 190 PSI. In another example, the pressure is 200 PSI. In another example, the pressure is 210 PSI.

[0427] In some of the above examples, the pressure is 220 PSI. In other examples, the pressure is 23 In some other examples, the pressure is 240 PSI. The force is 250 PSI. In one example, the pressure is 260 PSI. In yet another example, the pressure is In some instances, the pressure is 280 PSI. In other instances, The pressure is 290 PSI. In some instances, the pressure is 300 PSI. In other instances, the pressure is 31 0 PSI. In yet another example, the pressure is 320 PSI. In some examples, the pressure In another example, the pressure is 340 PSI. In yet another example, the pressure is 35 In some other instances, the pressure is 360 PSI. In some instances, the pressure is In still other examples, the pressure is 380 PSI. In some examples, the pressure is The force is 390 PSI. In yet another example, the pressure is 400 PSI. In one example, the pressure In another example, the pressure is 420 PSI. In yet another example, the pressure is In some other instances, the pressure is 440 PSI. In yet another example, the pressure is 460 PSI. The pressure is 470 PSI. In yet another example, the pressure is 480 PSI. In another example, the pressure is 500 PSI. In yet another example, the pressure is is 510 PSI.

[0428] In some of the above examples, the pressure is 520 PSI. In other examples, the pressure is 53 In some other examples, the pressure is 540 PSI. The force is 550 PSI. In one example, the pressure is 560 PSI. In yet another example, the pressure is In some instances, the pressure is 570 PSI. In some instances, the pressure is 580 PSI. In still other instances, The pressure is 590 PSI. In some instances, the pressure is 600 PSI. In other instances, the pressure is 61 0 PSI. In yet another example, the pressure is 620 PSI. In some examples, the pressure In another example, the pressure is 640 PSI. In yet another example, the pressure is 65 In some other instances, the pressure is 660 PSI. In some instances, the pressure is In still other examples, the pressure is 680 PSI. In some examples, the pressure is The force is 690 PSI. In yet another example, the pressure is 700 PSI. In one example, the pressure In another example, the pressure is 720 PSI. In yet another example, the pressure is In some other instances, the pressure is 740 PSI. In yet another example, the pressure is 760 PSI. The pressure is 770 PSI. In yet another example, the pressure is 780 PSI. In another example, the pressure is 800 PSI. In yet another example, the pressure is is 810 PSI.

[0429] In another example, the pressure is 820 PSI. In one such example, the pressure is 830 PSI. In other instances, the pressure is 840 PSI. In some other instances, the pressure is 850 PSI. In one example, the pressure is 860 PSI. In yet another example, the pressure is 870 PSI. In some instances, the pressure is 880 PSI. In yet other instances, the pressure is 890 PSI. In one example, the pressure is 900 PSI. In another example, the pressure is 910 PSI. In yet other instances, the pressure is 920 PSI. In some instances, the pressure is 930 PSI. In another embodiment, the pressure is 940 PSI. In yet another embodiment, the pressure is 950 PSI. In some other instances, the pressure is 960 PSI. In some instances, the pressure is 970 PSI. In yet other instances, the pressure is 980 PSI. In some instances, the pressure is 990 PSI. In yet another example, the pressure is 1000 PSI.

[0430] In some instances, garnet-based setter plates provide beneficial surface properties for sintered films. These beneficial surface properties include flatness and surface roughness useful in battery applications. These beneficial properties include the prevention of Li evaporation during sintering. These beneficial properties include a preference for specific garnet crystal structures. It is also possible.

[0431] In certain methods disclosed herein, the inert setter plate is made of porous zirconia. The method is selected from the group consisting of alumina, graphite, or conductive metal plate. In some, the inert setter plate is porous zirconia. In some others, the inert setter plate is graphite. In yet another approach, the inert setter plate is a conductive metal plate.

[0432] (h. Oxygen Partial Pressure) In some instances, the sintering method includes adding an acid to the atmosphere in contact with the garnet material being sintered. In some examples, the oxygen partial pressure is controlled by controlling the concentration of argon and water. By flowing a mixture of nitrogen and water (i.e., H2O) in contact with the garnet material being sintered. In some examples, the oxygen partial pressure is controlled by the flow rate of argon, hydrogen, or water, Alternatively, by adjusting the flow rate of all three gases or any combination of these gases. In some instances, the oxygen partial pressure is 2E-1 (i.e., 20% O2). In other instances, the oxygen partial pressure is 1E-2. In some instances, the oxygen partial pressure is 1E-3. In other instances, the oxygen partial pressure is 1E-4. In some other instances, the oxygen partial pressure is 1E In some instances, the oxygen partial pressure is 1E-6. In other instances, the oxygen partial pressure is In some other instances, the oxygen partial pressure is 1E-8. In some other examples, the oxygen partial pressure is 1E-9. In other examples, the oxygen partial pressure is 1E-10. In some instances, the oxygen partial pressure is 1E-11. In some instances, the oxygen partial pressure is 1E-3. In some examples, the oxygen partial pressure is 1E-12. In some other examples, the oxygen partial pressure is 1E-13. In other examples, the oxygen partial pressure is 1E-14. In some other examples, the oxygen partial pressure is In some instances, the oxygen partial pressure is 1E-15. In other instances, the oxygen partial pressure is 1E-16. In some other examples, the oxygen partial pressure is 1E-18. In some instances, the oxygen partial pressure is 1E-19. In other instances, the oxygen partial pressure is 1E-20. In other instances, the oxygen partial pressure is 1E-21. In some instances, the oxygen partial pressure is 1E-22. In other examples, the oxygen partial pressure is 1E-23. In some other examples, the oxygen partial pressure is is 1E-24. In some instances, the oxygen partial pressure is 1E-25.

[0433] (i. Grinding Method) As described herein, some of the recited methods include process steps related to mixing and and / or method steps relating to grinding. Grinding includes ball grinding. Grinding is not limited to However, ethanol, isopropanol, toluene, ethyl acetate, methyl acetate, acetone, Also included are methods of grinding using inert solvents such as acetonitrile, acetonitrile, or combinations thereof. Depending on the materials used, the solvent may not be inert. In some of these examples The grinding may be carried out in an aqueous solution, including but not limited to ethanol, isopropanol, toluene, ethyl acetate, Trituration using a solvent such as methyl acetate, acetone, acetonitrile, or a combination of these. include.

[0434] In some instances, the milling is ball milling. In some instances, the milling is In some examples, the grinding is attritor grinding. In some instances, the milling is immersion milling. In some instances, the milling is high energy milling. In some instances, the high energy milling process is 50 The crushed particle size is 100 nm. In some instances, the milling is a submerged milling.

[0435] In some instances, a high energy milling process is used to 50 Particle size distribution of about 100 nm In some examples, the solvent is toluene. The solvent is isopropyl alcohol (IPA). In some instances, the solvent is ethanol. In some instances, the solvent is diacetone alcohol. In the examples, the solvent is 50 A suitable polar solvent is used to achieve this diameter.

[0436] In some instances, the milling is performed using 0.3 mm yttria stabilized zirconium oxide grinding media. In some instances, this includes high energy wet milling processes using beads. Crushing, horizontal milling, attritor milling, or immersion milling can be used. Some examples are In this case, a high-energy grinding process is used to produce approximately d 50 has a particle size distribution of ~100 nm Glass. EXAMPLES

[0437] IV. EXAMPLES In the examples described herein, the product rich formed by the methods herein is The subscript values ​​of the um-filled garnets are used to make the claimed compositions. The molar ratios represent the elemental molar ratios of the precursor chemicals that are

[0438] a. Example 1 - Flux Deposition of Li Conductive Ceramics In one embodiment, preformed garnet material, i.e., a seed crystal, is used to grow other garnets. A net material is prepared. In this example, 100 grams (g) of Li7La3Zr2O 12 31.03g of Li2CO3 58.65 g of La2O3, and 29.57 g of ZrO2. The resulting mixture is dissolved in isopropanol. The mixture was then ball milled at 400°C for 24 hours. The mixture was then dried and calcined at 900°C for 12 hours. After that, it was sintered at 1100 °C for 12 hours. The obtained product was ground again in isopropanol to obtain , reducing the average particle size to 1 μm.

[0439] b. Example 2 - Flux Deposition of Li Conductive Ceramics In this embodiment, a thin film garnet electrolyte of 3 μm to 50 μm is produced. The garnet precursor was LiOH / Li2CO3 / LiO2 / La2O3 / ZrO2. 0.3 mm yttria stabilized The precursor was ground using zirconium oxide grinding media beads. The mixture was dispersed in a slurry formulation and the slurry was deposited on a metal foil. The slurry was then dried. The film was then pressed with a plate and heated to sinter the components therein. Doped compositions were prepared using Al2O3 as the source of Al, Nb2O5 as the source of Nb, and Ta. 2O5 was used as the source of Ta.

[0440] The garnet precursor slurry was deposited on a metal foil substrate. Nickel strips approximately 0.5 mil thick were The substrate was prepared using a cleaning method. In one case, the IPA solution was used. The residual organic matter on the surface of the metal foil was removed using a solvent. Gas plasma treatment, and chemical treatment (ammonium hydroxide or light acids such as citric acid / acetic acid / Using other surface cleaning methods, such as washing with a base solution, to prepare the surface for slurry application. It is also possible to use a doctor blade and adjust the doctor blade gap to 3um~100 A film thickness of 1 μm was achieved.

[0441] The deposited film was then dried. After the film was dried, the deposited film was calendered and heat treated. A dense membrane was achieved prior to the calendering process. Depending on the starting thickness, a thickness reduction of up to 50% was achieved This was achieved after the step. The next step involved applying pressure to the membrane. A maximum pressure of 20 MPa was applied.

[0442] A sintering process was then carried out. The size of the sintered grains varied depending on the degree of sintering carried out. Sintering was carried out at a temperature range of about 900°C to 1200°C with a dwell time of only 15 to 90 minutes. provided.

[0443] The sintering process increases the density and uniformity of the garnet thin film. The XRD graph of the thin garnet film processed as a sample is shown in Fig. 7. The garnet phase was confirmed by As shown by XRD.

[0444] (c. Example 3 - Densification with Bismuth Flux) In this example, the lithium-loaded garnet powder was composed of a 1:1 mixture of Li2CO3 and B2O3. The powder was densified using a flux that is known to be suitable for this purpose.

[0445] Figure 52 shows the results for lithium-loaded garnet films as a function of flux heating conditions. The densities obtained are shown: 900°C, 30 min (bottom curve); 950°C, 30 min (second-lowest curve). line); 950°C, 6 hours (third curve from the bottom); 100°C, 30 minutes (top curve).

[0446] (d. Example 4 - Preparation of Microcrystalline Li-Ion Conductive Garnet Ceramics) In this example, LiOH, La2O3, ZrO2, and Al(NO3).9H2O were combined in various ratios to form The mixture was mixed for 8 hours by dry ball milling, after which it was cooled in air in an alumina crucible. The mixture was calcined at 800 to 1000°C for 4 to 8 hours.

[0447] As mentioned above, Li7La3Zr2O 12 · To produce 0.35Al2O3 phase, the molar ratio of Li:La:Zr:Al2 The above reactants were mixed in a ratio of 7:3:2:0.35.

[0448] (Using yttria stabilized zirconia grinding media (approximately 2-10 hours) and an 80 mesh sieve) 64.6 grams (g) of dried and ground LiOH was mixed with 184.5 g of La2O3, 93.9 g of ZrO2, and 96.3 g of Al(NO3 )3·9H2O to prepare composition C, the XRD of which is shown in FIG. The reactant powder was dried at 120° C. for about 1 hour. The powder was then heated in an alumina crucible in air for 1 hour. The mixture was calcined at 800 to 1000°C for 4 to 8 hours.

[0449] The product (as measured by light scattering) 50 Grind with a solvent until the particle size is ~300 nm, then dry. This dry powder was dissolved in isopropanol at 4% w / w polyvinyl chloride. By mixing with Chiral, removing the isopropanol, and sieving through an 80 mesh sieve, A pellet was formed.

[0450] The binder is then added to pellets with a diameter of 13 mm and a thickness of about 1.2 to 1.4 mm, weighing about 3 metric tons. Pressure was applied from the applied powder. The pellets were placed between the setter plates and dried in aluminium. The powders were sintered in a tubular furnace with Ar (Ar; flow rate 315 sccm) flowing in. The sintering was carried out at 150-180°C for 1-4 hours. Then, heat sintering at 300-350°C for 1-4 hours, then at 1000-1200°C for 3-9 hours, and then The cooling was included.

[0451] The mass and dimensions of the sintered pellets were measured to determine the geometric density and scanning electron microscopy was performed. was used to determine the grain size on the fracture surface.

[0452] Figure 9 shows a map of the compositional space that was explored. Compositional variables include lithium and aluminum. The lanthanum to zirconium ratio was maintained at 3:2 throughout the study. Figure 9 shows that the phase space studied contains highly conductive (>10 -4 S / cm) region exists. This zone is larger for the lower sintering temperature (1075°C compared to 1150°C). The high temperature, short dwell conditions (1200°C, 15 min) were similar to those of the samples produced at lower temperatures. Some of the compositions disclosed in this study, e.g. For example, compositions A, B, C, and D produce high conductivity (as shown in FIG. 9).

[0453] Composition A is Li 6.3 La3Zr2O 12 Characterized by 0.35Al2O3.

[0454] Composition B is Li 6.3 La3Zr2O 12 Characterized by 0.67Al2O3.

[0455] Composition C is Li7La3Zr2O 12 Characterized by 0.67Al2O3.

[0456] Composition D is Li7La3Zr2O 12 Characterized by Al2O3.

[0457] FIG. 10 shows a cross section through the phase space map (FIG. 9) along with the associated density and grain size. do.

[0458] The processing and sintering of garnet ceramics described herein is comparable to other known techniques. In comparison, a relatively short reaction time and moderate temperature were utilized. The garnet grain size remains relatively small (i.e., <10um), above which the crystal grain size becomes too large (i.e., >100um), and lithium This indicates that Bell is present.

[0459] FIG. 11 is a comparative analysis of known garnet compositions and the garnet compositions described herein. These other studies show that for all aluminum contents examined, It is clear that the sintering temperature of garnet is in the "high lithium" region. Most of the processing was performed at temperatures above 1200°C and for long periods (e.g., over 10 hours). This results in large grain growth and is incompatible with the powders, films, and devices described in this application. The present application provides garnet films having conductivity values ​​suitable for use in secondary battery applications. It shows unexpectedly short processing dwell times and unexpectedly low temperature processing conditions.

[0460] The embodiments described herein limit the Li content and sintering temperature to reduce the amount of lithium. It has been shown that small grain sizes can be achieved in the zirconia-lanthanum-alumina system. The specific composition (composition B) with Li, Al=6.3, 0.67 is illustrative because The composition is found to be small grained after sintering at 1075°C, but after 1150°C This is due to the large grain size resulting from the selected processing conditions and This shows how specific the process is. A processing temperature of 1075°C was used. In the present study, compositions A, B, C, and D exhibited low grain size and high conductivity (>10 -4 S / cm) Note that this results in a fairly unique combination.

[0461] FIG. 12 shows a graphite alloy having fine grains as described herein and formed at a lower temperature, e.g., 1075° C. 1 shows an example of a scanning electron microscope image of a sintered lithium-filled garnet.

[0462] Figure 13 shows the bulk conductivity of * 10 -4 Li exceeding S / cm x La3Zr2O 12 ·yAl2O3 with Li:Al x:y The ratio is shown.

[0463] FIG. 14 illustrates various compositions that can be made using the methods described herein and the The compositions and associated densities are shown.

[0464] FIG. 49 shows the XRD of composition C.

[0465] e. Impedance Measurements of Pellets of Example 5-Composition C The pellet was polished to a thickness of approximately 1 mm and then platinum (Pt) electrodes were attached to either side. The electrical transport properties were determined by sputter deposition. Spectra were measured at several temperatures.

[0466] Figure 50 shows the impedance of a polished pellet of composition C. R1 is the impedance of the R2 is due to the interfacial impedance. The electrode effect is due to the Li This is due to the blocking of ions. The total resistance is equal to R1 + R2. The conductivity is given by

number

[0467] The reported conductivities include all resistances observed in the impedance spectrum. do.

[0468] (f. Example 6 - Charging and discharging a full cell) A pellet of garnet containing composition C and a 2 μm Li-evaporated negative electrode on one side of the pellet. a conductive additive comprising carbon and sulfur-containing catholyte on the other side of the pellet; An electrochemical cell was assembled containing a positive electrode containing NCA along with the reagent.

[0469] The charge / discharge curves are shown in FIG.

[0470] (g. Example 7-Plating and Stripping) Garnet bilayer thin films: Lithium plating and delamination for plating and stripping Li on Ni|G|eLi The initial open circuit voltage is ~2.5 V. First, the current is set to 1 mA / cm 2 Percentage of The cell voltage is gradually decreased toward 0 by passing the current through the cell. When the voltage drops below 0 (t=500 seconds), Li begins to plate at the nickel interface. At t=800 s, the current is turned off. The voltage is At t=900 s, the 4-step cycle is initiated and the voltage is 0 V, which indicates that the voltage is 0 V (i.e., Li is on both sides). Repeat several times. 2 The current is then turned on again and plating is continued for 2 minutes. The sample is then left for 1 minute. Then, 1mA / cm 2The Li is stripped off for 2 minutes by passing the wire through the wire in the opposite direction. After repeating this sequence 10 times, Li is finally removed from the Ni side by the final peeling current. When the lithium is completely removed from the battery and, as a result, the lithium is depleted, the voltage rises sharply (t=2800 seconds).

[0471] The results are shown in Figure 48.

[0472] h. Example 8 - Powders, Slurries, Tapes, and Bilayers Example 4: Preparation of fine-crystalline Li-ion conducting garnet ceramics We have produced um-filled garnets.

[0473] The powder was formulated as a slurry by milling the powder. 20 g of the dry milled powder was , YSZ grinding media, and toluene, ethanol, and a phosphate ester as a dispersant. Then, 8 g of this powder was mixed with a 33% w / w solution of polyvinyl butyral in toluene and 4 g of soluble Mixed with plasticizer (dibutyl phthalate).

[0474] This slurry was then coated with silicone using a doctor blade (blade height set to ~250 μm). The solution was tape cast onto the green coated substrate and had a dry tape thickness of approximately 70 μm.

[0475] An electrode ink having 12.74 g of Ni powder and 3.64 g of a 7% w / w ethylcellulose solution in solvent. The electrodes were screen printed using a 400 mesh screen. The crust was dried in air and also in an oven at 120°C.

[0476] The bilayer film was fired in a tube furnace with a setter plate and an argon, H2, and H2O flow. The oxygen pressure within the tube is controlled by adjusting the relative flow rates of these three species. The binder is removed at 500° C. The film is sintered at about 1000-1200° C.

[0477] The bilayer membranes produced are shown in Figures 54, 55, and 56.

[0478] i. Example 9 - Powders, Slurries, Tapes, and Bilayers 1 molar equivalent of Al2O3 with the required molar ratios of lithium hydroxide, zirconium oxide, and lanthanum oxide , and aluminum nitrate to obtain Li7Li3Zr2O 12 (LLZ) and alumina powder The end was produced.

[0479] Dry the powder in an oven for 45 minutes to an hour, then ball mill it with 25% medium by volume. The mixture was then dry-milled for 8 hours using the grinding technique. The media was separated using a sieve and then heated at 900°C in air. The mixture was calcined at 40° C. for 6 hours to produce garnet powder.

[0480] Then, 300 g of the calcined garnet powder was used to prepare a slurry, which was then heated for 30 g of dispersant, the particle size (d 50 Add 300 g of isopropanol or tetrahydrofuran until the chromatogram is 300-400 nm. The mixture was ground at low temperature in toluene:ethanol (4:1).

[0481] 35 g of this slurry was added to 2.65 g of a dispersing agent (e.g., Rhodoline 4160) and mixed with the zirconia catalyst. The mixture was crushed in a bottle (1 / 4 of the bottle volume) for 8 hours. 1.75 g of the plasticizer dibutyl phthalate and 1.75 g of the Indah was added to the slurry and milled for an additional 12 hours. 1.5 g of toluene was added and Mix for 2 hours.

[0482] Using a doctor blade setting and a blade height setting of 20 mils, apply the tape to the Mylar. A green tape was produced by casting the film onto a tape. The film was dried and then The film was separated from the Mylar. Ni was screen printed as Ni ink onto the dried film. Film disc was cut for sintering.

[0483] By placing the cut membrane with Ni on it between ceramic setter plates, The samples were sintered inside a tube furnace. The furnace was heated to 200 °C at 5 °C / min in moist Ar. Heat to 200°C and hold for 4 hours, then heat to 600°C at 5°C / min and hold for 4 hours, then The furnace was heated at 1100 °C / min and held for 1 hour at 315 sccm Ar and 10 sccm Ar / H. Cooled.

[0484] (j. Example 10 - Bilayer Membrane) As shown in Figure 59, by evaporating ~2um of Li on one side of the garnet side, A two-layer half-cell was fabricated.

[0485] Impedance (EIS) and plating were examined. Plating was examined using EIS with a linear voltage sweep. The plating started with the voltage at 0V (vs. OCV). After a pause, the initial plating was done at 200uA. The deposition and peeling were performed at 100uA with rest periods in between, followed by a final peel at 200uA. The results are shown in Figures 53 and 61.

[0486] (k. Example 11 - Freestanding Membrane) Lithium hydroxide, zirconium oxide, lanthanum oxide, and aluminum nitrate in the required molar ratios. The powder was produced by batch processing of 1000g ... The powder was dried in an oven for 45 minutes to an hour, and then the volume was 25% media using ball milling technique at 40° C. for 8 hours, and the media was separated. The powder was then calcined in air at 900° C. for 6 hours to produce garnet powder.

[0487] A slurry was prepared using 300 g of this calcined garnet powder, and the particle size (d 50 ) is 300~400nm The slurry was attrition milled in 200 g of isopropanol and 30 g of dispersant until 60 g of the slurry was obtained. 5.35 g of dispersant (e.g., Rhodoline 4160) was added and milled with zirconia media for 8 hours. 3. 57g of the plasticizer dibutyl phthalate was added to 3.57g of the binder and milled at low rpm for an additional 12 hours. Then, 6.5 g of toluene was added and mixed for 2 hours.

[0488] Using a doctor blade setting and a blade height setting of 20 mils, the green tape was The film was manually cast taped onto Mylar tape. The film was allowed to dry and separated from the Mylar. The membrane was cut to form discs for sintering.

[0489] The disks were sintered between ceramic setters in a tube furnace.

[0490] The samples were sintered by placing the cut membrane between ceramic setter plates. Sintering was carried out inside a tube furnace, which was heated to 200° C. at 5° C. / min in humid Ar and held at 200° C. for 4 h. Hold for 4 hours, then heat to 600°C at 5°C / min, hold for 4 hours, then heat to 1100°C at 10°C / min. The furnace was heated and held at 315 sccm Ar and 10 sccm Ar / H2 for 1 hour, after which the furnace was cooled.

[0491] (l. Example 12 - Reaction Sintering) The required molar ratios of lithium hydroxide, zirconium oxide, lanthanum oxide, and aluminum nitrate A powder containing LLZ with 1 molar equivalent of Al2O3 was produced by batch processing of the powder. The powder is dried in an oven for 45 minutes to an hour, and then ball milled using 25% media by volume. The mixture was then dried and ground for 8 hours using a sieve, and separated from the media. The powder was calcined in air at 900° C. for 6 hours to produce garnet powder.

[0492] 300 g of calcined garnet powder was used with the reaction sintering precursor to prepare a slurry, and the particle size was (d 50 ) until the particle size is 300-400 nm, add 300 g of dispersant and 300 g of toluene / ethanol (4:1) or attrition ground in diacetone.

[0493] 10 g of this slurry was mixed in a flactek mixer for 15 minutes, after which 0.2 g of binder was added. The slurry was added and mixed for an additional 15 minutes.

[0494] Using a doctor blade setting and blade height setting of 5 or 10 mils, slurries were sprayed with N A green tape was produced by casting the film onto a 100% ZnO foil. The film was then dried and cut into a circular disk. was cut off.

[0495] Sintering was carried out by placing the membrane between ceramic setters in a tube furnace.

[0496] The samples were sintered by placing the cut membrane between ceramic setter plates. Sintering was carried out inside a tube furnace, which was heated to 200° C. at 5° C. / min in humid Ar and held at 200° C. for 4 h. Hold for 4 hours, then heat to 600°C at 5°C / min, hold for 4 hours, then heat to 1100°C at 10°C / min. The furnace was heated and held at 315 sccm Ar and 10 sccm Ar / H2 for 1 hour, after which the furnace was cooled.

[0497] (m. Example 13 - Low Area Specific Resistance (ASR)) In this example, a ceramic setter was compared to a metal setter. The films were prepared according to Example 12 in some cases, resulting in garnet films with lower ASR. In some cases, a Pt setter plate is used, in other cases, a ceramic setter plate is used. The mixture was then sintered.

[0498] As shown in Figure 61, the films sintered using the ceramic setter plate had a lower AS It had R.

[0499] The results are also shown in the table below.

[0500] Table 1 [Table 1]

[0501] These examples form a high resistance layer at the interface between the garnet and the solid electrolyte with a Li anode. This shows a balance between the low tendency to

[0502] (n. Example 14 - Low Area Specific Resistance (ASR) at the Pellet Surface) Lithium-loaded garnet pellets were prepared as detailed above. The pellets were heated in Ar The samples were sintered either in a mixture of Ar / H2 or in air. The impedance results are shown in Figure 6. 2. The ASR is lower for Ar and Ar / H2 than for air.

[0503] Although the foregoing embodiments have been described in some detail for purposes of clarity of understanding, certain It will be apparent that changes and modifications can be practiced within the scope of the appended claims. It should be noted that there are many alternative ways of implementing such processes, systems, and apparatus. The present embodiments are therefore to be considered as illustrative and not limiting. and the embodiments should not be limited to the details given herein. This application provides an invention having the following configuration. (Configuration 1) A composition comprising a lithium-filled garnet and Al 2 O 3 wherein the lithium-filled garnet is characterized by the empirical formula Li A La B M' c M'' D Zr E O F wherein 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2, 0 ≤ E ≤ 2, 10 < F ≤ 13; M' and M'' are each independently either non-existent or each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; and the molar ratio of garnet:Al is 0.05 to 0.7, said composition. 2 O 3 (Configuration 2) Characterized by the empirical formula (Formula 1) wherein 5.0 < x < 9 and 0.1 < y < 1.5, the composition according to Configuration 1. TIFF0007608306000006.tif7170 (Configuration 3) Characterized by the empirical formula Li La 7.0 +Nb 3 (Zr t1 +Ta t2 wherein t3 )O 12 +0.35Al 2O 3 the molar ratio of La to the combined amount of (Zr + Nb + Ta) is 3:2 and t1 + t2 + t3 = 2 wherein, the composition according to Configuration 1. (Configuration 4) Characterized by the empirical formula Li La 7 the composition according to Configuration 1. 3 Zr 2 O 12 ·0.35Al 2 O 3 (Configuration 5) The composition according to Configuration 1, wherein A is 5, 6, 7, or 8. (Configuration 6) The composition according to Configuration 5, wherein A is 7. (Configuration 7) The composition according to Configuration 1, wherein M' is Nb and M'' is Ta. (Configuration 8) The composition according to Configuration 1, wherein E is 1, 1.5, or 2. (Configuration 9) The composition according to Configuration 8, wherein E is 2. (Configuration 10) The composition according to Configuration 1, wherein C and D are 0. (Configuration 11) The composition according to Configuration 1, wherein the molar ratio of garnet:Al is 0.1 to 0.65. 2 O 3 (Configuration 12) The molar ratio of garnet:Al ​ 2 O 3 The composition according to aspect 1, wherein the molar ratio of is 0.15 to 0.55. (Configuration 13) Garnet: Aluminum 2 O 3 The composition according to aspect 1, wherein the molar ratio of is 0.25 to 0.45. (Configuration 14) Garnet: Aluminum 2 O 3 The composition of claim 1, wherein the molar ratio of is 0.35. (Configuration 15) The composition of claim 1, wherein the molar ratio of Al to garnet is 0.35. (Configuration 16) The lithium-filled garnet has an empirical formula of Li 7 La 3 Zr 2 O12 It is characterized by 0.1 to 1 mo 2. The composition of claim 1, wherein the composition is doped with at least one alumina. (Configuration 17) 17. An electrochemical device having an electrolyte made of the composition according to any one of claims 1 to 16. (Configuration 18) 17. An electrochemical device having a catholyte made of the composition according to any one of claims 1 to 16. (Configuration 19) The subscript values ​​represent the precursor chemicals used to make the claimed compositions. 17. The composition of any one of claims 1 to 16, wherein the molar ratio of elements is represented. (Configuration 20) 17. The composition according to any one of claims 1 to 16, which is a thin film having a thickness of about 10 nm to about 100 μm. thing. (Configuration 21) 21. The membrane of claim 20, wherein the thickness is less than 50 μm and greater than 10 nm. (Configuration 22) 21. The membrane of claim 20, wherein the thickness is less than 40 μm and greater than 10 nm. (Configuration 23) 21. The membrane of claim 20, wherein the thickness is less than 30 μm and greater than 10 nm. (Configuration 24) 21. The membrane of claim 20, wherein the thickness is less than 20 μm and greater than 10 nm. (Configuration 25) 21. The membrane of claim 20, wherein the thickness is less than 10 μm and greater than 10 nm. (Configuration 26) 21. The membrane of claim 20, wherein the thickness is less than 5 μm and greater than 10 nm. (Configuration 27) 21. The membrane of claim 20, wherein the thickness is less than 1 μm and greater than 10 nm. (Configuration 28) 21. The membrane of claim 20, wherein the thickness is less than 0.5 μm and greater than 10 nm. (Configuration 29) d less than 10μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 30) d less than 9μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 31) d less than 8μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 32) d less than 7μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 33) d less than 6μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 34) d less than 5μm 50 21. The membrane of embodiment 20 having grains with a diameter. (Configuration 35) The membrane has a d 50 21. The composition of embodiment 20, having grains having a diameter. (Configuration 36) The membrane has a d 50 21. The composition of embodiment 20, having grains having a diameter. (Configuration 37) The membrane has a d 50 21. The composition of embodiment 20, having grains having a diameter. (Configuration 38) The membrane has a d 50 21. The composition of embodiment 20, having grains having a diameter. (Configuration 39) 1. A method for making an aluminum doped lithium filled garnet comprising the steps of: providing a predetermined combination of garnet precursors; Optionally, drying the precursor at about 80° C. to about 200° C. for about 10 minutes to about 10 hours; milling the combination for 5 to 10 hours; The combination is calcined in a vessel at about 500° C. to about 1200° C. for about 4 to about 10 hours to form a garnet phase. To form; The formed garnet is called d 50 Grinding to a particle size of 100-1000 nm; The crushed formed garnet is mixed with a binder to add plasticizers, dispersants and garnet chemicals. and optionally at least one member selected from the group consisting of precursors, forming a slurry comprising: Optionally, filtering the...

Claims

1. A bilayer comprising a metal foil or metal powder disposed in contact with a lithium-filled garnet thin film, the lithium-filled garnet thin film is a thin sintered garnet film, The lithium-filled garnet thin film has a thickness of less than 50 μm and more than 10 nm; and the lithium-filled garnet thin film is bonded to the metal foil or powder on at least one side of the film; The lithium-filled garnet is characterized by one of the following formulas: Li A La B M' C M'' D Zr E O F , Li A La B M' C M'' D Ta E O F , Li A La B M' C M'' D Nb E O F wherein 4<A<8.5, 1.5<B<4, 0≦C≦2, 0≦D≦2, 0≦E<2, 10<F≦13, and M′ and M″ are each independently selected at each occurrence from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; Li a La b Zr c Al d Me'' e O f wherein 5<a<7.7, 2<b<4, 0<c≦2.5, 0≦d<2, 0≦e<2, 10<f≦13, and Me″ is a metal selected from Nb, Ta, V, W, Mo, or Sb; Al2O3 doped Li A La B M' c M'' D Zr E O F (In the formula, Al 2 O 3 to the lithium-loaded garnet is 0.05-0.7); Li g La 3 Zr 2 O 12 -Al 2 O 3 (Wherein, 5.5<g<8.5 and Al 2 O 3 to the lithium-loaded garnet is 0.05-1.0); 【Chemistry 1】 where 5.0<x<9 and 0.1<y<1.5; or Li x La 3 Zr 2 O 12 +yAl 2 O 3 (wherein 5.5≦x≦9 and 0≦y≦1).

2. 2. The bilayer of claim 1, wherein the metal is Ni; Al; Fe; stainless steel; an alloy of Ni, Cu, Al, or Fe; or a combination of Ni, Cu, Al, or Fe.

3. 13. An electrochemical stack comprising at least two or more bilayers according to claim 1.

4. 2. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a thickness of 1 μm to 150 μm.

5. 10. The bilayer of claim 1, wherein the bilayer comprises a metal foil, and the metal foil is a current collector.

6. 10. A trilayer comprising the bilayer of claim 1, further comprising a second lithium-filled garnet thin film in contact with the metal foil or metal powder of the bilayer.

7. 10. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a thickness of less than 20 μm.

8. 10. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a surface roughness of less than 5 μm.

9. 2. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a median grain size of 0.1 μm to 10 μm.

10. 2. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a median grain size of 1.0 μm to 5.0 μm.

11. The lithium-filled garnet has the empirical formula 【Chemistry 2】 2. The bilayer of claim 1, characterized by: wherein 5.0<x<9 and 0.1<y<1.

5.

12. The lithium-filled garnet is Li a La b Zr c Al d Me'' e O f 2. The bilayer of claim 1, characterized by: wherein 5<a<7.7, 2<b<4, 0<c≦2.5, 0≦d<2, 0≦e<2, 10<f≦13, and Me″ is a metal selected from Nb, Ta, W, Mo, or Sb.

13. 13. The bilayer of claim 12, wherein e=0.

14. 13. The bilayer of claim 12, wherein 10<f<13.

15. 13. The bilayer of claim 12, wherein a<7.

16. 13. The bilayer of claim 12, wherein 0.3<d<1.

17. The lithium-filled garnet is Li x La 3 Zr 2 O 12 .Al 2 O 3 2. The bilayer of claim 1, comprising at least one member selected from the group consisting of:

18. The bilayer of claim 5, wherein the metal is Cu.

19. 6. The bilayer of claim 5, wherein the metal is Ni.

Citation Information

Patent Citations

  • Ceramic material and process for producing the same

    JP2011051800A

  • Ceramic material and preparation method therefor

    JP2011073962A